Interface evolution unlocks the anti-poisoning capability of trace B-site excessive medium-entropy air electrodes for tubular reversible solid oxide cells - Yuan Gao; Bo Wei; Yanan Liu; Tian Li; Xu Han; Abdalla M. Abdalla; Zhe Lv; Yihan Ling (Fuel, 2026)

Beyond direct pathway engineering: reprogramming Fusarium fujikuroi from a GA3 producer into a GA4+7 factory - Hang Xiao; Tao-Xu Lu; Ming-Han Li; Ya-Ling Yi; Hao-Yang Li; Yu-Ke Cen; Zhi-Qiang Liu; Yug-Guo Zheng (Bioresource Technology, 2026)

A kinetic-based framework for the selection of in vitro osteoarthritis models: integrating temporal dynamics of inflammatory inducers - Guoyun Cheng; Nur Atheeqah-Hamzah; Xiaoqian Liu; Fengyang Lv; Kwong Weng Loh; Atiqah Aziz; Han Ling Tan; Kamarul Tunku (Molecular Biology Reports, 2026)

Correction to: Spil mediated sEH overexpression contributes to the senescence of alveolar epithelial cells during pulmonary fibrosis in mice - Chen-Yu Zhang; Wen-Jing Zhong; Jin-Tong Yang; Yan-Ling Qiu; Han-Xi Sha; An-Jun Ou; Yu-Biao Liu; Xiao-Ting Huang; Yong Zhou; Jia-Xi Duan; Cha-Xiang Guan (Journal of Molecular Medicine, 2026)

Spil-mediated sEH overexpression contributes to the senescence of alveolar epithelial cells during pulmonary fibrosis in mice - Chen-Yu Zhang; Wen-Jing Zhong; Jin-Tong Yang; Yan-Ling Qiu; Han-Xi Sha; An-Jun Ou; Yu-Biao Liu; Xiao-Ting Huang; Yong Zhou; Jia-Xi Duan; Cha-Xiang Guan (Journal of Molecular Medicine, 2026)

A mechanism-constrained large language model-based intelligent diagnosis framework for bridge defects - Hui Jin; Si-Ming Zhou; Han Chen; Zhi-Yu Xie; Feng Li; Yong Li; Jian-Feng Zhu; Yi-Feng Ling; Zhi-Min Wu; Xiang-Ming Zhou (Engineering Structures, 2026)

Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; Dave W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Elucidating dynamic migration mechanism of oxygen species in lanthanum oxide catalytic oxidative coupling of methane reaction based on developed deep potential function - Yurong Liu; Yuhao Wang; Zijie Cheng; Bingying Han; Riguang Zhang; Lixia Ling; Pengyu Niu; Litao Jia; Maohong Fan; Xiangyuan Li; Xianxian Hu; Baojun Wang (Fuel, 2026)

Study on surface morphology characteristics and tensile properties of non-uniformly corroded stud connectors - Yachuan Kuang; Kui Wang; Zhiwei Peng; Wenjun Li; Tianyu Wang; Huan Chen; Han Ling; Yushuo Hu (Engineering Structures, 2026)

Study on the mechanical behavior of helical anchors in soft soil sites under horizontal cyclic loading - Hang Cen; Zhong-ling Zong; Yun-han Huang; De-long Huang; Shi-li Ma; Jun-nan Zhao (Computers and Geotechnics, 2026)

Microtopographic and runoff-sediment responses to check-dam configurations under consecutive rainfall: Laboratory experiments in a simulated loess watershed - Zhiwei Cui; Peng Li; Shengde Yu; Songsong Ling; Chenyang Li; Jianchun Han; Chaoya Zhang; Jingjing Pan; Huiyuan Zhang; Shu Yu (CATENA, 2026)

Potential carbon sequestration promoted by subsoiling: Tracing the fate of exogenous glucose and priming effect in soil aggregates - Xinkun Liu; Yi Lv; Xiaochun Li; Yecheng Zhang; Jingyi Shao; Ruxin Li; Fiston Bizimana; Xiaowen Xu; Xianfeng Zhang; Qisong Gao; Xiaohan Duan; Huifang Han; et al. (Agriculture, Ecosystems & Environment, 2026)

Coupled geochemical profiling and metagenomics reveal controls on phosphine preservation and emission in a eutrophic Estuary - Ye Zheng; Chen Wang; Xiaojun Niu; Chao Han; Zhihong Zhang; Huirong Yang; Shuping Zhang; Xingyao Ye; Ling Li; Jingyuan Lv; Zihong Ma; Hang Liu; et al. (Water Research, 2026)

Cold island networks in metropolitan areas under multi-objective land-use scenarios: Scenario simulation, resilience assessment, and spatial planning implications - Kaili Zhang; Bin Fang; Xuanyun Zhang; Chunhua Xia; Yun Ling; Han Liu (Sustainable Cities and Society, 2026)

U-AsymSeg: Asymmetric dual-stream RGB-Polarization network for underwater semantic segmentation - Yiming Gao; Qi Ling; Ruxin Han; Hongming Chen; Yafei Wang; Guoliang Yuan; Xianping Fu (Ocean Engineering, 2026)

Linking street-level greenery to environmental microbial diversity: A multiscalar analysis in the Taipei metropolitan area - Long Xie; Jussi Torkko; Marja Roslund; Tzen-Ying Ling; Juulia Manninen; Shih-Han Hung; Aki Sinkkonen; Tuula Jyske (Landscape and Urban Planning, 2026)

Metamorphism of the high-pressure pelitic granulites from the Luxia, Danniang and Baga valleys, Namche Barwa Complex, southeastern Tibet, China - Tao Peng; Ling-Sen Zeng; Guang-Ming Hao; Ying Xia; Han-Wen Dong; Juan Wang (Journal of Asian Earth Sciences, 2026)

Metal-polyphenol network-coated probiotic microcapsules: Enhancing Limosilactobacillus fermentum storage stability and yogurt characteristics - Yi-han Cai; Fang Huang; Si-ying Yan; Xiao-jin Lin; Shu-ling Huang; Shao-fu Feng; Jie-ying Chen; Yan-yan Huang; Xin-An Zeng; Xiang-ze Jia (International Dairy Journal, 2026)

Ultrasound-induced modifications in egg-milk yogurt: a comprehensive study on physicochemical stability, lipidomic restructuring, and flavor profile enhancement - Danrong Yu; Yaogui Sun; Ni Zhang; Yutong Han; Bohan Wang; Shurong Wang; Ling Ma; Zhihui Yu (Food Chemistry, 2026)

Deep placement of reduced nitrogen input strengthens soil water–nitrogen coupling and root–shoot coordination to enhance grain yield in dryland maize - Fu Liu; Jing Ling; Lan Luo; Xiaozhou Li; Yunfei Ren; Yi Zhou; Xiangyang Zhao; Xiaogang Yin; Shikun Sun; Juan Han; Youcai Xiong; Yuncheng Liao; et al. (Field Crops Research, 2026)

Color-tunable and multi-stimuli-responsive room temperature phosphorescence based on an efficient supramolecular approach - Huan Yao; Yu-Ling Hu; Jun-Fu Chen; Han-Yu Luo; Wen-Jie Chen; Liu-Pan Yang; Li-Li Wang (Chemical Engineering Journal, 2026)

Direct upcycling spent LiCoO2 into self-supporting cathodes via cobalt-seed induced slurry electrolysis - Yunhui Han; Xiangfei Zeng; Dejun He; Jiqin Wang; Kun Li; Qian Liang; Ling Hu; Anlong Han; Hao Li; Mengjun Chen (Chemical Engineering Journal, 2026)

Zn isotopic evidence for the role of recycled sedimentary carbonate in generating carbonatites and alkaline rocks associated with rare-metal mineralization - Juan Wang; Ling Han; Peilong Cui; Yu Kang; Shuaijun Wang; Ganglan Zhang; Xiangfa Wang (Chemical Geology, 2026)

Microalgae bioenergy with carbon capture, utilization and storage: A sustainable technology to net-negative emissions and circular economy - Chao-Wen Wang; Kai Ling Yu; Hwai Chyuan Ong; Brandon Han Hoe Goh; Cheng-Tang Pan (Biomass and Bioenergy, 2026)

Development and validation of an E2 based indirect ELISA for serological detection of porcine Getah virus - Zijun Xiang; Wenjing Tian; Dong Li; Meiqi Liu; Zhicheng Han; Qiong Wu; Zhong Peng; Ling Zhao; Bin Wu; Danna Zhou (Veterinary Research Communications, 2026)

Geological augmented clustering enhanced intelligent prestack seismic inversion - Ling-Qian Wang; Ming-Yu Yang; Han-Ming Chen; Hui Zhou (Applied Geophysics, 2026)

Recent advances on MXene nanomaterials-based biosensing technologies and portable analytical devices for detection of food hazard factors - Haofang Liu; Ling Li; Biru Han; Yina Zhao; Manyan Qiu; Qianyu Zhao; Bo Qu; Xianlong Zhang; Yujun Jiang (Trends in Food Science & Technology, 2026)

Cadmium induced ferroptosis of TM4 cells through PERK-ATF4-CHOP signaling pathway - Xuan Li; Juan Dai; Jiaoyang Wei; Yan He; Yue Han; Ting Zhou; Rui Li; Ling Zhang; Yuqin Shi (Reproductive Toxicology, 2026)

Integrative transcriptomic and functional analysis reveals fatty acyl elongases involved in sex pheromone biosynthesis in rice leaffolder, Cnaphalocrocis medinalis (Lepidoptera: Pyraloidea) - Ling-Yue Chen; Xiao-Yang Lin; Ke-Xin Wang; Xiao Feng; Hong-Ting Tang; Shuang-Lin Dong; Ling-Ling Zheng; Yi-Han Xia (Insect Biochemistry and Molecular Biology, 2026)

Fractal characteristics of roughness in inclined self-supported fractures of shale with embedding multi-layer proppants - Han Cao; Ziyi Zhang; Ling Zhu; Junsheng Zhu; Yan Lv; Ting Bao (Geomechanics for Energy and the Environment, 2026)

Unveiling the molecular interplay: phosvitin as a stabilizer of lactoferrin against thermal denaturation - Ling Zhang; Wenduo Han; Han Sun; Wenqi Ge; Jiawen Pei; Jiajing Liu; Shubo Luo; Xiang Duan; Xuebo Liu (Food Chemistry, 2026)

Fluorescence and SERS dual-mode sandwich lateral flow test strip utilizing concanavalin A modified trimetallic polydopamine with rhodamine B loaded UiO-66 immunoprobe for visual and sensitive detection of Escherichia coli - Wen-Bo Zhao; Xiao Liang; Zi-Tao Zhong; Liu Yuan; Ji-Tao Li; Qiu-Lan Li; Qin-Qin Han; Ya-Ling Yang (Food Bioscience, 2026)

Ecological and taxonomic significance of SEM‑based micromorphology in Gentiana (Gentianaceae) on the Qinghai‑Tibet Plateau - Ling Zheng; Yaqi Han; Xinyue He; Xiaoyu Zhou; Jingle Li; Peng-Cheng Fu (Flora, 2026)

Benchmarking backbone neural networks for HVAC fault diagnosis and regression: Insights into spatiotemporal, graph, and attention-based architectures - Zhe Sun; Peng Yang; Ling Shi; Qiwei Yao; Lin Li; Han Xiao; Xiangwei Zheng; Xi Shen (Energy and Buildings, 2026)

Interactions between medicinal plants and rhizospheric microbial secondary metabolites: Mechanisms, effects, and biotechnological applications - Karlia Meitha; Chen-Hui Kuo; Tu-Trinh Thi Truong; Chieh Chang; Tsai-Wen Hsu; Miaw-Ling Chen; Chao-Li Huang; Takashi Gojobori; Cheng-Han Yang (Ecological Genetics and Genomics, 2026)

Tellurium vacancies enable efficient polysulfide anchoring and bidirectional conversion for enhanced LiS battery performance - Zhen Wei; Zhi Liu; Ruinan He; Han Qin; Kanakaraj Aruchamy; Philip Wortman; Ling Fei (Chemical Engineering Journal, 2026)

Landsat observation reveals upward trend of surface water temperature in the Three Gorges Reservoir over the past quarter century: divergent effects of climate changes and dam constructions - Han Peng; Botian Zhou; Dongmin Wang; Yue Yuan; Guang Li; Meiling Liu; Ling Wu; Mingsheng Shang (Journal of Oceanology and Limnology, 2026)

Efficacy and safety of vunakizumab in patients with moderate-to-severe plaque psoriasis with a high drug interruption rate during the COVID-19 pandemic: a post hoc analysis from a single center of a phase III trial - Shangshang Wang; Zhenghua Zhang; Ling Han; Kexiang Yan; Jinhua Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Long-term subsoiling enhanced soil organic carbon sequestration via macropore optimization and iron-aluminum oxides enrichment - Yecheng Zhang; Fiston Bizimana; Kun Han; Xiaohan Duan; Shaobo Wang; Jingyi Shao; Xinkun Liu; Qisong Gao; Xianfeng Zhang; Keqiang Li; Ling Liu; Huifang Han (Soil and Tillage Research, 2026)

A unified solution to the low-mass X-ray binary diversity puzzle: saturated magnetic braking coupled with irradiation-driven winds - Zhu-Ling Deng; Xiang-Dong Li; Bo Wang; Philipp Podsiadlowski; Yong Shao; Dong-Dong Liu; Zhan-Wen Han (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Mechanical response and optimized design of steel pipe composite piles in coastal soft-over-hard strata - Zengming Hao; Xiaoyu Bai; Nan Yan; Jianyong Han; Ling Zhang; Lin Cui; Yamei Zhang (Ocean Engineering, 2026)

Decoding genetic basis of nitrogen use efficiency in maize using AI-generated deep phenotypes - Haoyan Yang; Lingju Zeng; Xiangjian Gou; Yang Shao; Xianlong Song; Shuang Zhang; Xiaoyan Qian; Zhenwei Zhang; Xiao Wang; Haitao Li; Bo Peng; Juliet Nkiruka Anyanwu; et al. (Molecular Plant, 2026)

Phosphate-solubilizing bacteria-loaded biochar alleviates microplastic–cadmium co-contamination by reshaping the soil phosphorus cycling network - Meng Wang; Yan Chen; Yue-Liang Meng; Shan-Shan Gao; B. Larry Li; Yu-Ying Li; Xue-Min Ren; Hui Han; Ling Liu; Zhao-Jin Chen (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations” [Geomorphology 512 (2026) 110490] - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; David W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Self-assembled micelles stabilized by covalent α-lipoic acid-carboxymethyl chitosan conjugates: Enabling stable delivery and glutathione-responsive release of coenzyme Q10 - Ling Liu; Jiangyue Wang; Rui Zhao; Meihan Wang; Qingzhuo Gu; Jiaqi Han; David Julian McClements; Xuebo Liu; Fuguo Liu (Food Research International, 2026)

A thermodynamic constraint for parameter reduction in reacting flows: Theory and experimental validation in methane-air flames - Xinlu Han; Kaidi Wan; Dingkun Yuan; Zhongqian Ling (Chemical Engineering Journal, 2026)

New Understanding of the Progressive Failure Process of the 2018 Baige Landslide, Tibet, China: A Role of Intermittent Rainfall - Ling Zhu; Shenghua Cui; Zicheng Lu; Xiangjun Pei; Han Cao; Shuang He; Hui Wang; Hailong Yang (Journal of Earth Science, 2026)

The Antiviral Activity and Underlying Mechanisms of Quercetin in Combating Largemouth Bass Virus Infection - Lin Huang; Wenyu Liao; Mingquan Peng; Jieying Yu; Mingzhu Liu; Junxiang Lai; Ermeng Yu; Ying Pan; Fei Ling; Shuyu Han; Qing Yu; Pengfei Li (Journal of Fish Diseases, 2026)
Largemouth bass virus (LMBV), a member of the Ranavirus genus within the Iridoviridae family, is a significant pathogen causing high mortality and substantial economic losses in largemouth bass aquaculture. Therefore, developing effective antiviral agents against this viral infection is crucial for the largemouth bass aquaculture industry. Quercetin, a widely utilised flavonoid known for its therapeutic and prophylactic properties, was investigated for its antiviral efficacy against LMBV and underlying mechanisms in this study. The results demonstrated that quercetin significantly inhibited LMBV propagation in vitro and in vivo, and was effective in both prevention and treatment stages. Specifically, quercetin at 6.25 μg/mL suppressed LMBV (major capsid protein) MCP gene transcription by up to 92.09%, with the post‐infection treatment achieving 99.33% inhibition in vitro. Mechanistic studies revealed that quercetin reduces LMBV infectivity by disrupting viral internalisation and replication, while also potentiating cellular immune responses mediated by the IFN system. In vivo experiments further confirmed that quercetin treatment reduced viral transcription in the liver, spleen and kidney by 97.49%, 47.45% and 98.42%, respectively, at 48 h post‐infection and significantly enhanced the survival rate of infected juveniles. In conclusion, quercetin demonstrated potent antiviral activity against LMBV and might serve as a promising, eco‐friendly antiviral agent.

Fish diversity and community turnover across protection zones in multiuse marine protected areas - Xu Zeng; Cong Zeng; Yongfeng Zhou; Yue Liu; Zheying Lin; Jihao Peng; Yihui Jiang; Han Dong; Guodong Li; Shuangzhao Li; Hengyu Li; Ling Cao (Conservation Biology, 2026)
Multiuse marine protected areas (MMPAs) with varying levels of protection in different zones are increasingly being adopted to balance conservation and socioeconomic goals. However, the effect of these zone‐based strategies on fish diversity is not well understood. We used environmental DNA surveys across zones with different protection levels (fully protected, highly protected, and lightly protected) in three typical Chinese MMPAs, while controlling for environmental factors and human activities, to examine fish species composition and richness among zones. Contrary to expectations, sites with high levels of protection had lower fish species richness than sites with lower levels of protection. Turnover in community composition between fully protected and less protected zones was 88.4% and accounted for 96.4% of pairwise dissimilarities. Rather than diminishing the importance of high‐level protection, our results showed that a tiered zoning approach can sustain fish species richness and limit biotic homogenization. Our results challenge the assumption that strict protection universally leads to high species richness and demonstrate that nuanced multilevel protection zoning may be more effective at preserving marine biodiversity and ecosystem functions at broader spatial scales.

Cold-induced shifts along the fast–slow continuum in Brachionus rotifers: adaptive integration of life history, reproduction, and behavior - Chengyan Han; Hang Yu; Yukina So; Zhan Ling; Takafumi Okaue; Shuang Han; Atsushi Hagiwara; Yoshitaka Sakakura (Hydrobiologia, 2026)

Compartment-specific Zinc Misallocation in Diabetic Foot Ulcers: Mechanistic Coupling Between Macrophage M1 Locking and MMP-9 Hyperactivation - Aiden Yi-Fei Wang; Atiqah Aziz; Han-Ling Tan; Xiu-Wen Ling; Terry Hao-Yu Qin (Biological Trace Element Research, 2026)

Targeting the GLIS1/DNMT3B-mediated DNA Methylation of HOXA9 to Suppress Metastasis in Lung Adenocarcinoma - Ling Jiang; Xiaolin Zhang; Meng Dai; Ying Bi; Lingling Han; Xiaofeng Tao; Qi Wang (Molecular and Cellular Biochemistry, 2026)

An adaptor protein CRK mediates antiviral immunity against white spot syndrome virus via JAK/STAT signaling pathway in Cherax quadricarinatus - Zi-Han Fan; Ling-Ke Liu; Wen-Lin Wu; Hai-Peng Liu (Fish & Shellfish Immunology, 2026)

Boosting aqueous Zn-ion battery performance with Co2+-doped δ-MnO2/Ti3C2Tx cathode through enhanced ion transport and structural stabilization - Shuo Li; Jing Zhu; Longkun Wu; Yasong Han; Ningning Zhao; Bin Li; Shaaban M. Shaaban; Lei Dai; Ling Wang; Zhangxing He (Chemical Engineering Journal, 2026)

Pilot-scale treatment of wool scouring wastewater in two-stage anoxic/oxic moving bed biofilm reactor: Performance and nitrogen removal mechanism - Xing Fan; Xueqing Shi; Jiahua Wu; Wenxuan Qiu; Xifeng Zhao; Jiazhong Zhou; Wenjie Han; Hongrui Lu; Ling Wang; Xuejun Bi (Bioresource Technology, 2026)

Metabolic process and mechanistic model of white-rot fungi degrading plastic films by solid-state fermentation - Zhi Guo; Lin Yao; Xingpan Guo; Lishou Han; Yuanyuan Zha; Xinlei Ling; Fan Yang (Bioresource Technology, 2026)

Characteristics of the radar bright band observed over a high-altitude lake - Run Han; Yingying Chen; Xiaoyan Ling; Kun Yang; Xin Li; Junbo Wang; Changhui Zhan; Xu Zhou; Ming Chen (Atmospheric Research, 2026)

Pseudostellaria heterophylla Extract Enhances the Immune Responses in Larimichthys crocea Against Pseudomonas plecoglossicida Infection - Kun Huang Han; Zi Min Li; Li Zhou; Dong Ling Zhang; Ying Li; Zhao Han Sun; Jia Chen; Zhi Deng Lin; Yan Bin Dai; Peng Fei Zou (Fishes, 2026)
Visceral white spot disease caused by Pseudomonas plecoglossicida poses a severe threat to large yellow croaker (Larimichthys crocea) aquaculture. This study investigated the immunomodulatory effects and underlying mechanisms of Pseudostellaria heterophylla extract against P. plecoglossicida infection in L. crocea. Fish were fed a basal diet supplemented with 1% P. heterophylla extract for 30, 45, and 60 days, followed by intraperitoneal injection with 200 μL P. plecoglossicida (1 × 104 CFU/mL). When the control group reached about 50% mortality, transcriptome sequencing of head kidney tissues was performed on the 45 and 60 days post-feeding of the treatment groups to analyze gene expression changes following bacterial infection. Survival rates of the treatment groups were 33.33%, 13.33%, and 20% higher than those of the control group at 30, 45, and 60 days post-feeding, respectively. Transcriptomic analysis revealed time-dependent transcriptional responses: in one group, 45 days post-feeding, 10 differentially expressed genes (DEGs) were identified (2 up-regulated and 8 down-regulated), whereas in another group, 60 days post-feeding, 893 DEGs were detected (417 up-regulated and 476 down-regulated). Functional enrichment analysis (GO, KEGG, and GSEA) demonstrated that DEGs were significantly enriched in immune-related pathways, including Toll-like receptor signaling, chemokine activity, Th1 and Th2 cell differentiation, hematopoietic cell lineage, and cytokine–cytokine receptor interaction. Key immune genes, including chemokines, Toll-like receptors, and T cell regulators, were significantly up-regulated. These findings indicate that P. heterophylla extract enhances both the specific and non-specific immune capabilities of L. crocea in a time-dependent manner, with prolonged supplementation eliciting more robust transcriptional activation of immune defense pathways. This study provides a scientific foundation for developing immunological prevention strategies against P. plecoglossicida infection in aquaculture.

Efficacy and safety of baloxavir marboxil vs. oseltamivir in Chinese outpatients with influenza B: an IPTW-adjusted real-world cohort study - Zhixiang Gong; Xiaonan Yu; Qiaoli Han; Ling Lu; Yang Liu; Bin Pei; Zi Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Extracting cropping patterns from remotely sensed images in a mixed single-, double-, and triple-cropping region of Southern China - Yifan Li; Chen Cheng; Xiaoming Shi; Hong Chi; Yifei Han; Fei Zhao; Jinliang Huang; Feng Ling (Environmental Monitoring and Assessment, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

High-resolution temporal biogeochemical variations in a seagrass-coral cohabitate ecosystem: day-night, rain, and coral spawning - Huei-Ting Lin; Yu-Chen Yen; Chih-Chiang Hsieh; Hirofumi Watanabe; Yiing-Jang Yang; Hui-Yu Wang; Han Song Ong; Shi-Ming Chen; Pei-Ling Wang (Science of The Total Environment, 2026)

Two new p-hydroxyphenethyl dimeric derivatives from alhagi sparsifolia and their cytotoxic activities - Yi-wei Gao; Xiao-ling Ma; Hai-long Song; De-gang Qing; Lei-Ling Shi; Li-li Han; Jing Zhang (Phytochemistry Letters, 2026)

Crotiglianoids A−M, tigliane-type diterpenoids from the seeds of Croton tiglium and their anti-hepatic fibrosis activity - Guang-Hai Zhu; Zhen-Zhou Han; Rong Huang; Li-Fen Ma; Xin-Yi Hu; Fei-Yu Zhang; Yi-Ling Liao; Lu Gan; De-an Guo; Wei Li (Phytochemistry, 2026)

Effects and mechanisms of a novel multi-target regulator on serum uric acid reduction and renal injury improvement in rats with hyperuricemia and renal damage - Zhihua Xing; Yue Xu; Wen Jiang; Zhiyuan Xu; Guanghuan Shen; Na Ling; Mingyu Gao; Weina Han; Yingjie Liu; Linlin Cui (PharmaNutrition, 2026)

Effects of check dam construction on runoff–sediment processes and sediment deposition patterns in small watersheds under continuous rainfall conditions - Zhiwei Cui; Peng Li; Tian Wang; Chenyang Li; Songsong Ling; Jingjing Pan; Shengde Yu; Chaoya Zhang; Jianchun Han; Shu Yu (Journal of Hydrology, 2026)

Mechanistic insights into UV/H2O2-aged polystyrene enable an optimized protocol for fungal biodegradation - Zhi Guo; Yuanyuan Zha; Xingpan Guo; Xinlei Ling; Lin Yao; Lishou Han; Fan Yang (Journal of Environmental Chemical Engineering, 2026)

Liquid-phase hydrogenation of benzaldehyde to benzyl alcohol over NiCoAl‑R catalysts: Synergistic metal–metal oxide interfaces for enhanced catalytic performance - Lingmei Yang; An Wei; Ru kuan Liu; Guo ling Zhang; Bing Han; Baining Lin; Lianhua Li (Journal of Environmental Chemical Engineering, 2026)

Preparation of phosphorus tailings-based lightweight aggregates via two-step sintering: Microstructure, heavy metal environmental risk, and circular economy potential - Rubin Han; Hongxiu Leng; Hui Luo; Wenbo Wu; Bukai Song; Yunrui Zhao; Bao-Jie He; Zhong-ling Zong (Journal of Environmental Chemical Engineering, 2026)

Differentiated biogeochemical pathways of antimony and arsenic immobilization: A comparative study on soil amendments under different remediation strategies - Yuezhong Chen; Han Tu; Pan Wu; Xuexian Li; Ling Li (Journal of Environmental Chemical Engineering, 2026)

Phosphorus source-sink distributions and fluxes in shallow-water wetland sediments: Insights from multiple habitats, varying water quality, and microbial communities - Yuwei Zhang; Shengqi Zhang; Yangyang Han; Cheng Guo; Ling Liu; Hongjie Wang (Journal of Environmental Sciences, 2026)

Non-uniform gradient depressurization strategy for balancing heat transfer and gas production in Dual-Gas Co-Production systems - Xian Sun; Hang Zheng; Hui Yang; Fu-Jun Cheng; Zhen Pan; Wen-Chen Han; Hao-Xiang Sun; Yang Yu; Ling-Ban Wang; Chang-Yu Sun (Fuel, 2026)

Efficacy optimization of electric field combined therapy on lung tumor microspheres using 3D micro-tissue impedance model-based platform - Yuqing Jiang; Xinru Luo; Acan Jiang; Bin Qiu; Shuang Ling; Huiquan Wu; Chenrui Xu; Han Chen; Xu Zhang; Hong Chen; Songyue Chen; Daoheng Sun (Chemical Engineering Journal, 2026)

Delocalized-electron engineered 2D mesoporous COFs boosting interfacial desolvation toward low-temperature zinc metal batteries - Yidan Duan; Yongzheng Zhang; Zhiyan Wang; Yue Liu; Rui Han; Cheng Ma; Duan Bin; Hongbin Lu; Wenming Qiao; Jitong Wang; Licheng Ling (Chemical Engineering Journal, 2026)

Virus-inspired Ganoderma lucidum polysaccharide-functionalized adjuvant with pseudo-zwitterionic interface for potentiated nasal immunization - Xu-Han Liu; Zhe Zhai; Ling-Ling Tao; Nan-Yu Chen; Yong-Xian Cheng (Carbohydrate Polymers, 2026)

Machine learning-enhanced UAV multispectral remote sensing for monitoring rice leaf area index across critical growth stages - Chao Su; Zaiying Ling; Liwang Han; Yanmin Shuai; Jianguang Wen; Xingwen Lin; Haifeng Tang; Alexandre Maniçoba da Rosa Ferraz Jardim; Hoi Leong Lee; Xuguang Tang (Precision Agriculture, 2026)

Corrigendum to “Acanthoic acid protectsagainst ethanol-induced liver injury: Possible role of AMPK activation and IRAK4 inhibition” [Toxicol. Lett. 281 (2017) 127–138] - You-Li Yao; Xin Han; Jian Song; Jing Zhang; Ya-Mei Li; Li-Hua Lian; Yan-Ling Wu; Ji-Xing Nan (Toxicology Letters, 2026)

Uranium adsorption by extracellular polymeric substances from Desulfovibrio vulgaris UR1: Extraction optimization and binding mechanisms - Juncheng Han; Jing Zou; Guangming Xu; Xinyao Liu; Likun Jiang; Haotian Yang; Guangsheng Zhu; Jiaxin Bai; Yanqing Guo; Peng Wang; Ling Luan; Junfeng Dou (Journal of Hazardous Materials, 2026)

The binding effect of biochar with polycyclic aromatic hydrocarbons and their derivatives: Role in carbon sequestration and pollutant removal efficiency - Muhammad Fawad; Lingyu Zhang; Abdelrahman Ibrahim; Xinyi Xu; Tong Wu; Miao Han; Vishnu D. Rajput; Chao Qin; Wanting Ling (Journal of Environmental Management, 2026)

In vitro and in vivo antiviral effects of myrcene on MSRV infection in largemouth bass (Micropterus salmoides) - Zhengzhao Liu; Lin Huang; Jieying Yu; Qing Yu; Mingzhu Liu; Yanxia Gao; Xiangmou Qin; Junxiang Lai; Fei Ling; Yanlei Chang; Shuyu Han; Jia Cai; et al. (Fish & Shellfish Immunology, 2026)

Pleurotus citrinopileatus polysaccharide inhibits glioma growth by downregulating the expression of CHI3L1--- CHI3L1 as a therapeutic target in glioma - Nuo-Ling Ye; Bing-Bo Zhuang; Hao-Dong Chen; Run-Qi Zou; Gang-Feng Cai; Jin-Hai Huang; Han Meng; Chun-Hua Wang; Jing Chen (Food and Bioproducts Processing, 2026)

Selectively regulating and UV–visible-NIR full spectrum blocked ECD based on single molecule-multivalences & resonances strategy - Huan Ling; Shuangdui Wu; Jingxin Han; Jie Zhang; Borong Lin; Xiping Zeng; Yu Wang (Chemical Engineering Journal, 2026)

Self-powered antimony oxide-coated palladium telluride/p-Silicon heterojunction DUV-MIR photodetector towards non-invasive diagnosis of diabetes - Jiayi Sun; Yuting Niu; Chen Rong; Zhikun Pang; Xinyi Han; Ningnuo Xiang; Lei Zhu; Xiaofang Li; Bo Peng; Cuicui Ling (Chemical Engineering Journal, 2026)

From species to therapeutic property: distribution differences of threatened Chinese medicinal plants under climate change - Yun-Han Chen; Rui Yang; Run-Han Jiang; Yu Xia; Ling-Feng Mao (Biodiversity and Conservation, 2026)

Simulation of Local Ultrasonic Intensity and Optimization of Sono-Reactors Geometry for Oily Sludge Treatment - Chenyang Li; Yimin Sang; Dading Zhang; Duan Zhao; Bengao Li; Dekun Ji; Ling Zhu; Yanhe Han (Environmental Modeling & Assessment, 2026)

Research on forest and grassland fire detection algorithm based on Himawari-8 geostationary satellite - Shan Zhang; Yong Xue; Xiaolu Ling; Chunlei Wu; Liying Han; Zhenglong Li (International Journal of Remote Sensing, 2026)

Colletotrichum aenigma causes anthracnose disease of Ficus carica L. in China - Yu-kun Qi; Wen-zhang Liu; Feng-ying Han; Wen-cheng Zhu; Shi-jun Sun; Qing-hai Wang; Ling-xi Zhou (Crop Protection, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Antifungal efficacy and mechanisms of slightly acidic electrolyzed water against Trichothecium roseum - Chenyang Li; Jun Ling; Yue Han; Xiaobing Li; Xueqiang Chai; Huali Hu; Hongsheng Zhou; Xuesong Liu; Chun Zhao; Yingtong Zhang; Pengxia Li (Postharvest Biology and Technology, 2026)

Development of a pH-responsive nanopesticide for efficient delivery of matrine and sustainable control of pine wood nematode - Linxi He; Zhiyi Zhao; Xixiang Xie; Jiahui Chen; Yaoyu Han; Bi Wu; Yang Li; Ling Ma; Jinsong Peng; Chunxia Chen (Pesticide Biochemistry and Physiology, 2026)

Numerical study of the effect of the pitch ratio of a helical strake on the vortex-induced vibration of a cylinder - Xiumei Ling; Xiangxi Han; Junlong Su; Hongqi Luo; Jiahao Zhang; Liping Fang; Zhanbin Meng; Youhong Tang; Di Ren (Ocean Engineering, 2026)

Chronology and geochemistry of radiolarian chert from Zhongba, southern Xizang (Tibet): Implications for the evolution of the Neo-Tethys Ocean - Han Yan; Han-Ting Zhong; Zong-Qi Lin; Chen-Yu Wang; Ling-Xue Gao; Cai Wang; Ming-Cai Hou (Palaeoworld, 2026)

Root traits determine the effects of organic amendments on soil aggregate organic carbon by regulating soil microbial multitrophic networks - Changdong HAN; Lin CHEN; Zhongjun JIA; Hongtao ZOU; Ling MA; Jingwang LI; Congzhi ZHANG; Guixiang ZHOU; Donghao MA; Jiabao ZHANG (Pedosphere, 2026)

Electrochemical oscillation on lead recovery from spent lead paste by suspension electrolysis - Xingyu Luo; Jiqin Wang; Dejun He; Yunhui Han; Xiangfei Zeng; Ling Hu; Qian Liang; Hao Li; Anlong Han; Jianchen Shu; Mengjun Chen (Journal of Environmental Chemical Engineering, 2026)

From waste PET to high-performance nanofiber-assembled adsorbent aerogels and their CO2 capture performance - Qi Jia; Ling Han; Yuqing Niu; Sen Yan; Jingli Zhang; Tao liu; Hui Zhang (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insights into the enhanced degradation of hydroxychloroquine by singlet oxygen in PMS and PMS/Cl2 systems: A comparative study - Zi-Han Feng; Zhen-Zhen Li; Dong-Su Bi; Fu-Xiang Tian; Ling-Yao Meng; Yan-Ting Jia; Yu-Qiong Gao; Xiao-Jun Hu (Journal of Environmental Management, 2026)

A pilot-scale certification for copper recovery from waste printed circuit boards by NH3-NH4Cl-CuSO4 slurry electrolysis: perspective but challenge - Qian Liang; Ling Hu; Xiangfei Zeng; Jinchuan Qin; Yunhui Han; Huimin Yang; Huan Li; Xingyu Luo; Shuyuan Chen; Shaoqin Chen; Jiqin Wang; Jiancheng Shu; et al. (Journal of Environmental Chemical Engineering, 2026)

Metabolomics-based reveals the relation between internal metabolism and storage quality of sesame harvested by machine at different speeds - Ling-Yu Qu; Shu-Guang Gao; Di-Chen Gong; Jing-Wen Zhao; Yun-Xuan Hu; Xiao-Tian Zhu; Han-Zhe Zhang; Hua-Min Liu; Hong-Mei Miao (Food Research International, 2026)

Modulation of gut microbiota by tangerine peel polysaccharide: A promising strategy for obesity management via acetic acid production - Chao-Yue Kong; Zhan-Ming Li; Bing Han; Yu-Qin Mao; Hui-Ling Chen; Jia-Ting Huang; Li-Shun Wang (Food Research International, 2026)

Robigenin in combating largemouth bass ranavirus: Investigating the antiviral potency and underlying mechanisms - Wenyu Liao; Lin Huang; Jieying Yu; Mingzhu Liu; Nijia Xue; Junxiang Lai; Ermeng Yu; Fei Ling; Shuyu Han; Ying Pan; Pengfei Li; Qing Yu (Fish & Shellfish Immunology, 2026)

Bacillus velezensis-derived methylmalonic acid inhibits Aspergillus flavus growth and aflatoxin biosynthesis by interfering with tryptophan metabolism - Ming Li; Qin Han; Xiulan Zhao; Yuxuan Hong; Ye Zhu; Can Liu; Jinyan Chai; Ling Cheng; Xiaofeng Yue; Xiaoqian Tang; Jing Mao; Qi Zhang; et al. (Chemical Engineering Journal, 2026)

Valorization of oily sludge with coal gasification slag via catalytic pyrolysis - Lei Han; Hai-Jie Hu; Jia-Xuan Liu; Tao Yu; Jin-Ling Li; Lan-Ting Ma; Cheng-Tun Qu; Zhong-Wen Liu (Bioresource Technology, 2026)

Simulation and analysis of CO2 concentration in China from 2009 to 2021 based on the WRF-Chem model - Wenhao Liu; Yong Xue; Xiaolu Ling; Botao He; Chenggang Li; Liying Han (Atmospheric Research, 2026)

Identification and validation of a QTL, QSNS.caas-3D.1, for spikelet number per spike in wheat - Xuezhong Liang; Junli Yang; Ze Liu; Fuping Zhang; Haiming Han; Shenghui Zhou; Jinpeng Zhang; Bing Han; Yida Lin; Hong-Qing Ling; Li Zheng; Junbo Yang; et al. (Theoretical and Applied Genetics, 2026)

Post‐Heatwave Coral Health Coincides With Host‐Specific Symbiodiniaceae‐Bacteria Consortia - Han Zhang; Xinqing Zheng; Qifang Wang; Xijie Zhou; Ling Cai; Liyang Zhan; Dingyong Huang; Tuo Shi (Environmental Microbiology, 2026)
Coral reefs are facing unprecedented damage due to climate‐driven marine heatwaves (MHWs). While coral response to elevated temperatures is inextricably linked to coral‐associated microalgae (Symbiodiniaceae) and bacteria, the role of algal‐bacterial interactions in affecting coral resilience to thermal stress remains obscure. Here we show coral health indicated by distinct compositions of Symbiodiniaceae‐bacteria consortia in two coral species, the massive Porites lutea and the laminar Duncanopsammia peltata , upon exposure to an unusual MHW. P. lutea exhibited thermal resilience by maintaining an obligate partnership with the heat‐tolerant Cladocopium C15 under both healthy and bleached states, alongside conservative bacterial community changes between the two states driven primarily by deterministic processes; whereas D. peltata associated with the heat‐sensitive Cladocopium C1 in bleached state but the heat‐tolerant Durusdinium D1/D4 in healthy state, with stochastically driven, more liberal bacterial community changes between the two states. This distinction between P. lutea and D. peltata in their Symbiodiniaceae‐bacteria consortia reflects a specialist/generalist strategy in partner selection given the status of coral health, underscoring an evolutionary trade‐off between high‐fidelity symbioses for persistence under chronic stress and rapid microbiome turnover for transient bleaching resilience. Broadly, the host‐specific, coordinated Symbiodiniaceae‐bacteria community differentiation following MHWs, may inform future coral conservation and restoration practises in an era of escalating climate change.

Moisture-Proof Herbal Extract Pellets Prepared via Asymmetric Liquid Layering Technology Combined with Mesoporous Silica and Magnesium Stearate - Shilin Ma; Yupeng Feng; Panao Yuan; Yunlong Xu; Ping Shao; Lifeng Lin; Zimin Wang; Ling Han; Xing Tang (AAPS PharmSciTech, 2026)

A replication-defective bivalent adenovirus-vectored vaccine provides robust and durable protection against both canine distemper virus and canine parvovirus - Ying Hu; Xiaohu Han; Shuo Zhu; Yuan Zhang; Yifan Peng; Chengguang Zhang; Ming Zhou; Ling Zhao (Veterinary Microbiology, 2026)

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Enhanced robust association for multi-object tracking in multibeam forward-looking sonar video - Xuyang Zhang; Han Pan; Kaiyao Ling (Ocean Engineering, 2026)

In-situ bioaugmentation of uranium-contaminated groundwater using Desulfovibrio vulgaris UR1: Mechanistic insights, laboratory validation, and field performance - Likun Jiang; Haotian Yang; Juncheng Han; Peng Wang; Xinyao Liu; Guangsheng Zhu; Ling Luan; Jiaxin Bai; Yanqing Guo; Junfeng Dou (Journal of Hazardous Materials, 2026)

Potential application prospects of white-rot fungi in composting degradation for plastic film waste - Zhi Guo; Lin Yao; Xingpan Guo; Yuanyuan Zha; Lishou Han; Xinlei Ling; Fan Yang (Journal of Environmental Sciences, 2026)

Decoupling of antimony and arsenic migration in a deep neutral legacy Technosol profile with implications for remediation - Yidan Shi; Ling Li; Han Tu; Xuexian Li; Pan Wu (Journal of Environmental Sciences, 2026)

Physical exercise mitigates the adverse effects of PM2.5 constituents on lung function: New evidence for inflammatory pathways from a crossover study - Pengpeng Wu; Qian Guo; Ling Qi; Yuchen Zhao; Mengyao Bian; Chen Wang; Bin Han; Junfeng (Jim) Zhang; Xiaoli Duan (Environmental Research, 2026)

Screening and Prioritization of Antibiotics in Drinking Water Source Based on Risk Assessment, a Case Study in Guangzhou - Lulu Zhang; Lingyun Yu; Qianqian Yu; Xuan Yu; Sijia Liu; Zhanlu Lv; Han Zhang; Qiusen Huang; Ling-Chuan Guo; Jingru Zhang (Environmental Management, 2026)

Study on CO 2 concentration assimilation by integrating a multi-source satellite fusion dataset based on the WRF-Chem model - Wenhao Liu; Yong Xue; Xiaolu Ling; Chenggang Li; Botao He; Liying Han (International Journal of Remote Sensing, 2026)

Pathogenicity of Porcine reproductive and respiratory syndrome virus in the reproductive system of female piglets: Pathological damage to the uterine horns and developmental arrest - Yi-Xin Yan; Ying Guan; Lei Zhao; Han-Yu Li; Tong Xu; Li-Na Shao; Si-Yuan Lai; Yi Qing; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; et al. (Veterinary Microbiology, 2026)

miR-207 mitigates silica-induced pulmonary fibrosis by suppressing fibroblast-to-Myofibroblast transition via multi-target modulation of the TGF-β1/SMADs signaling pathways in mice - Shu-ling Du; Yuan-yuan Cui; Xuan Zhou; Wei-Lei Gong; Zhao-qiang Zhang; Gui-zhi Han (Toxicology and Applied Pharmacology, 2026)

Waste treatment with waste: Preparation of cold-bonded artificial lightweight aggregates by alkali activation synergized with coastal saline soil and multi-source solid wastes - Rubin Han; Hongxiu Leng; Hui Luo; Wenbo Wu; Bukai Song; Yunrui Zhao; Bao-Jie He; Zhong-ling Zong (Sustainable Chemistry and Pharmacy, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Imbalance use of nitrogen and phosphorus accelerates food insecurity in Africa - Fiston Bizimana; Yecheng Zhang; Ling Liu; Arbindra Timilsina; Xianfeng Zhang; Xiaoxin Li; Yubo Cao; Chunsheng Hu; Huifang Han (Resources, Conservation and Recycling, 2026)

Bacterial assembly and succession during aerobic granulation stimulated by Fe3O4 nanoparticles with real municipal wastewater: The role of acyl-homoserine lactones mediated communication - Kailing Pan; Caixia Fang; Yuxuan Wei; Hengyuan Zhang; Di Wu; Jiazhong Zhou; Wenjie Han; Xiaoyan Fan; Ling Wang; Shujuan Huang; Xuejun Bi (Journal of Water Process Engineering, 2026)

Nano-bio interaction determines the early progression of lung cancer by reshaping pulmonary epithelial microenvironment - Yu-Han Zhang; Jun Zhang; Lei Shi; Meng Xiang; Xue Han; Ling Zhu; Jia-Cheng Xie; Yan Chen; Qi Gu; Jing-Yu Li; Zhen Zou; Jian-Yu Wang (Journal of Hazardous Materials, 2026)

Synthesis of M/MxOy@CA-CNFs(M=Ni, Co) electrostatically spun carbon nanofibers as highly efficient oxygen evolution electrocatalysts using an ultrafast high-temperature pulse method - Yanhuan Wang; Ling Hai; Tishi Shen; Li Li; Qingchun Han; Yujuan Zhai (Journal of Environmental Chemical Engineering, 2026)

Comparative analysis of laminar burning velocity of CH4 + H2 flame across a broad temperature range under atmospheric pressure - Jiayi Lin; Zhongqian Ling; Leilei Liu; Ye Yuan; Jiamin Li; Dingkun Yuan; Jiangrong Xu; Xinlu Han; Zhihua Wang (Fuel, 2026)

Raising the bar: Deep learning on comprehensive database sets new benchmark for automated fission-track detection - Samuel C. Boone; Ling Chung; Noel Faux; Usha Nattala; Thomas Church; Chenghao Jiang; Malcolm McMillan; Sean Jones; David Liu; Han Jiang; Kris Ehinger; Tom Drummond; et al. (Computers & Geosciences, 2026)

3D printing and in-situ polymerization enabled Interface-free double-layered polymer gel electrolyte for highly stable lithium metal batteries - Ling Liang; Shijian Zhu; Lei Gao; Liping Wang; Bingkai Zhang; Jing Liu; Jinlong Zhu; Songbai Han (Chemical Engineering Journal, 2026)

Synergistic effects and decomposition mechanisms of multi-component energetic materials under high-pressure conditions: Improving the ballistic performance of high-chamber-pressure weapons - Pei-chen Han; Jian-Wei Zhang; Ling Chen; Kun Yang; Xin-xin Tu; Shou-yu Wang; Fei-yun Chen; Ping Du (Chemical Engineering Journal, 2026)

Evaluating urban nighttime lighting and perceived safety in residential areas: An empirical investigation in Xi’an City - Chengwei Liu; Ling Liu; Xinxing Wang; Beilei Han; Leyi Chen (Building and Environment, 2026)

Whole-grain black rice diet rewires the single-cell transcriptomic landscape of age-related ovarian decline in mice - Yi-Xuan Tu; Dan-Yang Wang; Jun Ma; Ke-Chun Yu; Sheng-Hui Li; Bo-Han Li; Xin-Yin Deng; Shan Li; Hong-Kai Wang; Tailang Yin; Ling Wang; Zhen-Xia Chen (Science China Life Sciences, 2026)

Effects of phyllosphere and rhizosphere microbes on intraspecific competition of the invasive plant Ageratina adenophora and native plants - Zi-Qing Liu; Zhao-Ying Zeng; Ai-Ling Yang; Yong-Lan Wang; Chao Zhao; Han-Bo Zhang (Plant and Soil, 2026)

Inhibition of junctional protein disruption by 2,4,6-trihydroxy-3-geranyl acetophenone in lipopolysaccharide-induced endothelial hyperpermeability via GEF-H1/RhoA/ROCK pathway - Yee Han Chan; Kong Yen Liew; Kamal Rullah; Hanis Hazeera Harith; Ji Wei Tan; Daud Ahmad Israf; Khozirah Shaari; Mexmollen Marcus; Chau Ling Tham (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Triaxial creep test and damage model study of coarse-grained materials from red-bed soft rocks under freeze–thaw cycles: A multiscale analysis - Xiao Han; Shuang Tian; Xianzhang Ling; Liang Tang; Ruotong Sun; Chao Zhou; Luidmila Pestryakova (Transportation Geotechnics, 2026)

DEM-MBD-based study on mechanism of tamping-induced ballast breakage and tamping tine optimization in ballasted track beds - Yang Xu; Hongyang Han; Yike Yang; Luzhuang Li; Xing Ling; Luchao Qie; Chaozhi Ma (Transportation Geotechnics, 2026)

An Improved Tuna Swarm Optimization Algorithm based XGBOOST Classification Method for Food Risk Evaluation - Yongming Han; Fan Yu; Jiaxin Liu; Zhen Zhang; Bo Ma; Ling Wang; Zhiqiang Geng (Swarm and Evolutionary Computation, 2026)

SfFPPS genes mediate reproduction and insecticide-induced resurgence in Sogatella furcifera - Cao Zhou; Zi-Han Xu; Jiang-Ling Chen; Xin Li; Shi-Yan Zhang; Hong Yang; Dao-Chao Jin (Pesticide Biochemistry and Physiology, 2026)

A multi-domain BEM approach for hydrodynamic analysis of arbitrarily shaped 2D floating breakwaters with wide porous media - Jeong Cheol Park; Kyu Han Kim; Jing Hua Wang; Xiao-Ling Zhao (Ocean Engineering, 2026)

Red mud-mediated CO2 capture for enhanced carbon reduction and waste-to-resource: A review - Yanxiu Wang; Anqi Yang; Fan Wang; Dandan Huang; Ling Zhang; Chengwen Wang; Li Wang; Haisheng Han; Wei Sun; John L Zhou (Minerals Engineering, 2026)

Deciphering the effects of cascade reservoirs on phytoplankton communities in a karst river: Importance of super-large reservoirs - Jiang Wu; Xiao-Nan Wu; Xiao-Hui Zhao; Xu Han; En-Hang Liang; Rui An; Jia-Ju Liu; Wei-Ling Sun; Nan Xu; Ting Wang (Journal of Environmental Management, 2026)

Quantifying the response of bankfull channel width to active faulting in the Qianhe Graben on the southwest margin of Ordos Block, China - Zhiheng Liu; Sarah J. Boulton; Suiping Zhou; Jianhua Guo; Tingting Wu; Wenjie Zhang; Ling Han (Geomorphology, 2026)

Temperature-pressure field evolution of hydrate-bearing sediments: A comparative study of depressurization strategies for gas recovery using a novel fan-shaped simulator - Ling-Ban Wang; Yi-Fei Sun; Yu-Hao Bu; Zhen-Bin Xu; Xian Sun; Han-Feng Shao; Chang-Yu Sun; Guang-Jin Chen (Gas Science and Engineering, 2026)

Large-scale 3-D magnetotelluric modeling in anisotropic media using extrapolation multigrid method on staggered grids - Jinxuan Wang; Kejia Pan; Hongzhu Cai; Zhengguang Liu; Xu Han; Weiwei Ling (Computers & Geosciences, 2026)

Dual strategies for resisting thermal shock of highly stable tubular reversible solid oxide cells with a Fe-based high-entropy perovskite electrode - Yanan Liu; Tian Li; Xu Han; Wenjing Zhang; Yuan Gao; Yihan Ling (Chemical Engineering Journal, 2026)

Cu3P electrode catalyze degradations of metronidazole and chloramphenicol fast in high-amount Cl− over broad pH - Ruanshan Liu; Ling Zhang; Yuhe Shi; Guichuan Wei; Fanfan Guo; Yifan Wang; Bin Liang; Jing-Long Han; Ai Jie Wang (Chemical Engineering Journal, 2026)

Three eagles with one arrow: Multimode and dynamic luminescence from single non-conjugated polymer system induced by aromatic β-diketone - Wei Lv; Jingwen Han; Fan Wu; Shuaiqi Wang; Meijuan Lin; Qidan Ling; Zhenghuan Lin (Chemical Engineering Journal, 2026)

A universal, accurate natural compounds evaluation platform via cardiomyocyte based biosensing - Jie Chen; Jilin Zheng; Yuli Hu; Ling Zou; Han Yu; Bingyue Zhang; Xuelian Lyu; Hongchun Li; Dongxin Xu; Ning Hu; Yuqun Cai (Chemical Engineering Journal, 2026)

Top-down selection of pit mud local microbial community for efficient anaerobic digestion of distilled grain waste - Tao Xu; Mengya Han; Yan Zeng; Rujie Yang; Ling Xiang; Hanlan Tang; Xiaotong Liu; Yuanlong Chi; Zhenghong Xu; Suyi Zhang; Danqun Huo; Xiaozhong Zhong (Bioresource Technology, 2026)

Unveiling the synergistic mechanisms of multi-ionic removal in microbial desalination cells: Ion transfer, electrochemical behavior and microbial response - Chongtao Liu; Ran Ju; Chunxiao Han; Zhuangzhuang Liu; Yangyang Li; Xiaomei Jiang; Ling Wang; Yunfan Yang; Houkai Wu; Xiuping Tao (Bioresource Technology, 2026)

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

A novel multiplex RPA/CRISPR-Cas12a integrated biosensor for on-site detection of high-risk HPV genotypes - Yuying Bao; Wei Ding; Ling Zhang; Wei Wang; Jia Liu; Yiting Qu; Liguo Zhu; Kairui Zhang; Guanxi Zhong; Rong Han; Qiang Shen; Bo Wang; et al. (Analytica Chimica Acta, 2026)

A Fiber-Driven Finite Element Model for Predicting Residual Limb Soft Tissue Deformation: Applications in Prosthetic Socket Design - Ling Wang; Ziyan Qiu; Lei Tang; Fuhao Huang; Pingping Wei; Senay Mihcin; Changning Sun; Hongyuan Zhao; Lei Shi; Song Han; Dichen Li (Annals of Biomedical Engineering, 2026)

Deep learning inversion method for canopy height Based on collaborative modelling of GEDI waveforms and geographic environmental factors - Yi Yan; Ling Han; Liangzhi Li; Ying Jing (International Journal of Remote Sensing, 2025)

RAD-seq reveals Cenozoic shifts in the palaeogeographic distribution of Trigonobalanus verticillata across the Indochina Peninsula and Malay Archipelago - Ling Hu; Pei-Han Huang; Yi-Gang Song; Shook Ling Low; Guo-Xiong Hu; Shi-Shun Zhou; Lang Li; Yun-Hong Tan; Hong-Hu Meng; Yu-Peng Cun; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Combined toxicity of cesium and uranium on cyanobacterial growth and metabolism: Mechanisms and implications - Meng-wei Han; Xu Yang; Bin Dong; Jin-long Lai; Hai-ling Xi; San-ping Zhao (Journal of Environmental Chemical Engineering, 2025)

Coconut-shell biochar fixed-bed for groundwater remediation: Co-removal of microplastics and perfluorooctanoic acid - Xinle Han; Jing Xu; Yanfeng Shi; Lixingzi Wu; Ling Fu; Weina Xue; Yanhao Zhang; Xu Zhang; Xuli Jing; Zhibin Zhang (Journal of Environmental Chemical Engineering, 2025)

Using logarithmic multi-channel seismoelectric spectral ratios to estimate porosity and permeability - Ling Zeng; Hengxin Ren; Bo Yang; Kaiyan Hu; Xuzhen Zheng; Peng Han; Zuzhi Hu (Journal of Applied Geophysics, 2025)

Dry alkali-ball milling for high-solid conversion of biomass to sugar and ethanol: Comparison with conventional ball milling - Kaili Ding; Hao Lin; Xueli Chen; Xiwen Jia; Suan Shi; Xiaojun Guo; Ling Zhou; Lujia Han; Weihua Xiao (Fuel, 2025)

Postbiotics alleviate cognitive impairment and neuroinflammation via gut-brain axis and TLR4/MyD88/NLRP3 pathway - Longgang Jia; Ling Xiao; Xiaoyan Song; Xiaoxiao Zhang; Xuemei Han; Wu Liang; Tianmin Fu; Yufeng Xie; Yanping Wang; Weitao Geng (Food Research International, 2025)

Glycyrrhiza uralensis Fisch: A novel source of analgesic activity through NaV1.8 sodium channel modulation - Yalan Han; Shutong Wu; Hejiang Zhou; Xiancui Lu; Susu Cheng; Jiaojiao Li; Meiquan Li; Yin Nian; Ling-Yan Su (Food Research International, 2025)

Colloidal stability of Salvia officinalis essential oil nano-liposomes and its antioxidant and antibacterial dual effect in postharvest preservation of Agaricus bisporus - Jia Wang; Xin Jiang; Lei Feng; Jiali Han; Yueyuan Li; Xiangyou Wang; Hiroaki Kitazawa; Yanyin Guo; Ling Li (Food Control, 2025)

Galla Chinensis as an antiviral agent: Targeting Micropterus salmoides rhabdovirus infection - Jieying Yu; Mingzhu Liu; Qing Yu; Xiangmou Qin; Mingming Zhao; Ying Pan; Nijia Xue; Hao Wang; Songlin Li; Fei Ling; Gaoxue Wang; Shuyu Han; et al. (Fish & Shellfish Immunology, 2025)

Retraction notice to ‘Ancient forest plants possess cytotoxic properties causing liver cancer HepG2 cell apoptosis’ [Environ. Res. 241 (2024) 117474] - Xiaochen Yue; Nyuk Ling Ma; Jiateng Zhong; Han Yang; Huiling Chen; Yafeng Yang; Su Shiung Lam; Lijun Yan; Bjarne Styrishave; Tomasz Maciej Ciesielski; Wan-Xi Peng; Christian Sonne (Environmental Research, 2025)

Microbial drivers controlling arsenic mobilization in paddy soils and arsenic accumulation in rice grains - Zi-Kun Dong; Bao-Ling Han; Chuan Chen; A-Xiang Gao; Zhong Tang; Fang-Jie Zhao (Environmental Pollution, 2025)

Machine learning-aided design of adapted water treatment adsorbents: Advances, challenges, and opportunities - Ling Yuan; Sheng Li; Yujia Ma; Han Zhang; Chen Chen; Weiming Zhang; Yanyang Zhang; Ming Hua; Lu Lv; Bingcai Pan (Chemical Engineering Journal, 2025)

Interfacial polarization via spatially directed charge transfer at Cu/Co heterojunction for dual-enhanced CO2 photoreduction and biomass refining - Weikang Ling; Yushun Han; Huitong Jiang; Huanqiu Wei; Yuchen Ren; Min Hong; Hongdan Zhang; Jiliang Ma; Runcang Sun (Chemical Engineering Journal, 2025)

Vancomycin nanocomposite-functionalized M2 macrophages for precision targeting of MRSA in prosthetic joint infections - Ling Wu; Weijing Cheng; Bingkun Meng; Han Yan; Jun Liu; Fengze Miao; Tingrui Zhang; Xinyue Zhang; Nan Ding; Yujing Zhao; Quangang Zhu; Ziqiang Chen; et al. (Chemical Engineering Journal, 2025)

Linking temperature dependency of root litter decomposition to root order: a multi-species incubation study - Renshan Li; Fangfang Zhang; Xinkuan Han; Weidong Zhang; Liming Yin; Yongxue Yan; Ling Zheng; Xuedong Chen; Min Zhang; Silong Wang; Longchi Chen; Jianming Han; et al. (Plant and Soil, 2025)

Human umbilical cord mesenchymal stem cells improve the ovarian function through oxidative stress-mediated PERK/eIF-2α/ATF4/CHOP signaling in premature ovarian insufficiency mice - Pei-Ling Wu; Shi-Huan Tang; Han-Yue Wang; Hong-Mei Zhang; Lu Peng; Yao Liu; Yuan Yang; Chun-Bing Zheng; Xian-ping Zhang (Molecular Biology Reports, 2025)

Integrating network pharmacology with molecular docking and dynamics to uncover therapeutic targets and signaling mechanisms of vitamin D3 in Parkinson’s disease - Cheng Wang; Yi-Ling Wang; Qiu-Han Xu (Molecular Diversity, 2025)

Blocking triggering receptors expressed on myeloid cell-1 alleviates alveolar epithelial cell senescence by inhibiting oxidative stress in pulmonary fibrosis - Wen-Jing Zhong; Jian-Bing Xiong; Chen-Yu Zhang; Ling Jin; Nan-Shi-Yu Yang; Han-Xi Sha; Yu-Biao Liu; Jia-Xi Duan; Cha-Xiang Guan; Yong Zhou; Feng Su (Histochemistry and Cell Biology, 2025)

Combined transcriptome and metabolome analysis of tilapia response to hypoxia and Streptococcus agalactiae co‐exposure - Zaoya Zhao; Ling Wang; Yanjin Chen; Jinyu Liu; Qianxing Zou; Shuyu Han; Yi Yi; Jingu Shi (Journal of Fish Biology, 2025)
Deterioration of water quality, especially low dissolved oxygen, has contributed to outbreaks of streptococcal disease in tilapia. It has been reported that hypoxia increases the mortality of tilapia during Streptococcus agalactiae infection. However, the underlying mechanism of the increased susceptibility of tilapia to S. agalactiae caused by hypoxia remains unknown. In this study, the pathological effects of hypoxia and S. agalactiae co‐exposure in the liver of tilapia were investigated using transcriptome and metabolome analyses. When subjected to individual hypoxia or S. agalactiae exposure, the liver of tilapia exhibited significant pathological effects, including vacuolation, severe necrosis, nuclear and cellular polymorphism, hemocyte infiltration/leakage and abundant granular deposits. Moreover, these pathological effects became more severe under hypoxia and S. agalactiae co‐exposure. In addition, S. agalactiae exposure increased inflammation‐related gene expression, including CC1 , CC2 , IL‐1β , TNFα , but this effect was suppressed by hypoxia. Transcriptomic analysis revealed that carbohydrate, lipid and amino acid metabolic pathways were significantly altered in the hypoxia and S. agalactiae co‐exposure group compared to those in the control group. Among these metabolic pathways, only lipid metabolism was obviously altered at the metabolite level, as revealed by metabolomics analysis. Further combined analysis of the transcriptome and metabolome suggested that, in lipid metabolic pathways, glycerophospholipid metabolism should be a key pathway in S. agalactiae –infected tilapia under hypoxic conditions. Taken together, the results of the combined analysis of the global changes in the transcriptome and metabolome of the tilapia liver under hypoxia and S. agalactiae co‐exposure revealed important metabolic pathways involved in the pathological process by which hypoxia increases the susceptibility of tilapia to S. agalactiae .

Spatiotemporal dynamics of sea ice volume and their potential drivers in Liaodong Bay, China, using Sentinel-3 data over five ice seasons - Hongkun Ling; Jialing Wang; Lintai Zheng; Yue Lin; Jiashen Tian; Zhen Wang; Zhichuang Lu; Jiabo Han; Wenhua Liu; Liangliang Yang (Marine Geodesy, 2025)

Determination of dynamic shear stress and strain thresholds in frozen coarse-grained materials: experimental and M-K statistical analysis - Shanzhen Li; Shuang Tian; Liang Tang; Xianzhang Ling; Huijun Jin; Wenjian Zhao; Ke Wang; Xiao Han (Transportation Geotechnics, 2025)

How plants respond to salt stress: Lessons form RBOHs - MengYing Sun; Xiang Liu; Han Zheng; Ling Li; QiMeng Lv; GaoPeng Wang (Plant Science, 2025)

Inhibitory effect of licochalcone A on dual-species biofilms of Listeria monocytogenes and Staphylococcus aureus: mechanism involved in quorum sensing and application in beef - Ling Jiang; Yilin Han; Xianxuan Li; Kai Zhong; Yanping Wu; Hong Gao (International Journal of Food Microbiology, 2025)

Ni-Mo isotopes track marine metal cycling through early Cambrian redox shifts: Metalliferous black shales as paleo-environmental archives - Liu Willow Yang; Tao Yang; Huiyang Yu; Tao Han; Jian-Feng Gao; Hong-Fei Ling (Global and Planetary Change, 2025)

Comprehensive insights into the effect of color, texture, flavor and microbial community driven via yak bone-derived collagen peptides combined with tea polyphenols as a versatile additive in fermented sausages - Zhaoyang Song; Ya Zheng; Yabin Ma; Wenjing Ni; Yinjuan Cao; Ling Han; Qunli Yu (Food Research International, 2025)

Bacillus amyloliquefaciens B4 combined with a Fe2+@Fe3+composite film synergistically induces Penicillium expansum ferroptosis for fruit preservation - Jinyue Sun; Jia-Neng Pan; Hui-Ling Shen; Han-Xiao Zhuang; Xiaodong Zheng; Wen-Wen Zhou (Food Bioscience, 2025)

Isolation of largemouth bass virus (LMBV) and dominant immunogenic epitope screening of the major capsid protein of LMBV - Jie Leng; Ling-Yun Lin; Yun-Yao Tu; Cheng-Ke Zhu; Qun Lu; Ming-Ji Lv; Tao He; Jian-Yong Hu; Zhao-Fang Han; Song Zhu (Fish & Shellfish Immunology, 2025)

Efficient tanshinone metabolic engineering in Salvia miltiorrhiza through modified multiplex CRISPR/Cas9 system - Han Zheng; Qi Yao; Qi Liu; Badalahu Tai; Yi Ye; Ling Li; Yaojie Zhang; Yuyang Zhao; Xiaokai Gao; Shuai Liu; Xueqing Fu; Muyao Yu; et al. (Chemical Engineering Journal, 2025)

Effect of upper seawater infiltration on submarine natural gas hydrate exploitation: using a pilot-scale fan-column simulator - Ling-Ban Wang; Yi-Fei Sun; Yu-Hao Bu; Zhen-Bin Xu; Xian Sun; Han-Feng Shao; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2025)

A polysaccharide smart packaging materials: Anthocyanin microcapsules synergized with nanosilver co-filled gellan gum/sodium alginate film for monitoring chilled mutton freshness - Zhaoyang Song; Wenjing Ni; Ya Zheng; Yabin Ma; Yinjuan Cao; Ling Han; Qunli Yu (Carbohydrate Polymers, 2025)

Introduction of micro-nano bubbles in kaolin foams to facilitate the preparation of porous ceramics - Chengwen Wang; Yanxiu Wang; Haisheng Han; Li Wang; Yue Yang; Ling Zhang; Shipei Wang; Anqi Yang; Wei Sun (Applied Clay Science, 2025)

Carbon emissions and economic performance of high-density versus traditional Ctenopharyngodon idella aquaculture: evidence from life cycle assessment methodology and field measurements - Liang Xiao; Qiaomei Yuan; Wenhan Li; Jinghua Wu; Yueshi Li; Sijie Chen; Guodong Yuan; Tao Wang; Jiayin Ling; Fengxiang Han (Aquaculture International, 2025)

Novel arneomas A-B and other naphthoquinone active components in Arnebia euchroma I. M. Johnst - Li-Li Han; Yibanuer Reheman; Reyilanmu Maisaidi; Cong-Zhao Fan; Lei-Ling Shi; Sheng-Jie Jia (Natural Product Research, 2025)

Structures and antitumor activities of Arnegutones A–C: A study of three novel active components extracted from Arnebia euchroma - Li-Li Han; Guang-Jie Pan; Si-Qi Li; Yibanuer Reheman; Cong-Zhao Fan; Lei-Ling Shi; Sheng-Jie Jia (Phytochemistry Letters, 2025)

Structural changes, transfer trajectories, and driving forces of non-grain farmland in the main grain producing areas of central China - Shihong Long; Enxiang Cai; Ling Li; Fangjun Xie; Shuhui Lai; Han Hu; Yingchao Li; Ying Jing (Journal of Environmental Management, 2025)

Macrophage and keratinocyte cell assays suggest that the supercritical CO2 extract of black soybean possesses anti-inflammatory and skin barrier-protective effects - Ying Wu; Jia-Ying Wu; Jing-Xuan Bai; Xiao-Qi Wang; Amy Sze-Man Li; Xiao-Yun Fan; Rui-Xuan Han; Li Wang; Xiaobing Dou; Xiu-Qiong Fu; Zhi-Ling Yu (Food Research International, 2025)

Co-microencapsulation of Lactobacillus paracasei and Inonotus obliquus polysaccharide in alginate system: Physicochemical and functional properties - Yilin Sun; Jing Han; Huilin Zhang; Wenyan Li; Yujun Jiang; Yu Zhang; Ling Guo (Food Hydrocolloids, 2025)

Microstructure evolution and permeability of fine-grained loess subjected to freeze-thaw cycles - Chongyang Gao; Yulin Guo; Yan Han; Ling Xu (Engineering Geology, 2025)

Subsurface structure of a buried Eratosthenian crater on the far-side of the Moon - Ling Zhang; Chunyang Zhao; Xintong Dong; Shaoping Lu; Yi Xu; Yuqi Qian; Shuo Han; Zhijun Huo; Rui Gao (Earth and Planetary Science Letters, 2025)

Sources and potential health indicators in urban aerosols revealed by gas chromatography-mass spectrometry combined with nitrogen chemiluminescence detector: evidence from a megacity (Tianjin) of China - Jingying Ma; Yulin Qi; Yufu Han; Jinfeng Ge; Ling Wen; Xiaoli Fu; Wei Hu; Zongbo Shi; Dietrich A. Volmer; Pingqing Fu (Atmospheric Environment, 2025)

First Isolation of a Multi-azole-Resistant Aspergillus fumigatus cyp51A TR46/Y46F/F70L Mutant in a Patient with Fungal Keratitis - Xiang Han; Heng Zhang; Yuqi Mao; Wenhao Ling; Lu Ge; Menghua Tang; Yi Sun; Zhiqin Wu (Mycopathologia, 2025)

Integrated source apportionment and risk assessment prioritizes heavy metal control at an abandoned antimony smelter - Xiao-Hong Ma; Zhuan-Ling Shao; Yu-Han Wang; Wei-Di Tu; Li-Bang Ma; Jiao Wang (Environmental Geochemistry and Health, 2025)

Effects of physicochemical factors on transport and retention of polystyrene microplastics (PS-MPs) in homogeneous and heterogeneous saturated porous media - Lixingzi Wu; Yanfeng Shi; Ling Fu; Xinle Han; Yanhao Zhang; Xu Zhang; Weina Xue; Xuli Jing; Jing Xu; Zhibin Zhang (Environmental Geochemistry and Health, 2025)

Conditional Generative Adversarial Networks Enhance Atmospheric Thermodynamic Profile Retrieval from Ground-Based Microwave Radiometer Measurements - Disong Fu; Xia Li; Jingmiao Zhu; Dazhi Yang; Ruiting Liu; Hongrong Shi; Guangyu Gao; Xinlei Han; Xiang’ao Xia; Yunjie Xia; Maoling Ayitikan; Kai Cheng; et al. (Journal of Meteorological Research, 2025)

Multiple amplifications of NIR-I ECL signals of Au6PtAg nanoclusters and applications in fast detections of noradrenaline - Fanfan Guo; Yuanyuan Hu; Huiwen Zhou; Yuanjin Li; Jiadi Li; Guichuan Wei; Jing Long Han; Wenyue Gao; Sisi He; Wenxin Niu; Ling Zhang (Analytica Chimica Acta, 2025)

Sex-Associated Indels and Candidate Gene Identification in Fujian Oyster (Magallana angulata) - Yi Han; Yue Ning; Ling Li; Qijuan Wan; Shuqiong Li; Ying Yao; Chaonan Tang; Qisheng Wu; Xiang Guo; Jianfei Qi; Yizhou Ke; Hui Ge; et al. (Fishes, 2025)
Sex determination is a fundamental biological process governing animal reproduction. Although substantial progress has been made in elucidating its genetic basis, the genetic architecture underlying complex sex determination systems remains poorly understood. In this study, we identify sex-associated insertion–deletion (indel) variants, screen candidate genes, and compare sex-associated variation across populations with different genetic backgrounds in the Fujian oyster (Magallana angulata). Based on whole-genome resequencing data of a culture strain (designated FL), a total of 299,774 high-quality indels were identified. By integrating genome-wide association analysis (GWAS), fixation index (FST) analysis, and sex-biased genotype frequency comparisons, 77 overlapping sex-associated indels were identified, predominantly clustered within a 1.8 Mb (8.3–10.1 Mb) region on chromosome 9. Principal component analysis (PCA) based on the sex-associated markers and their subsets consistently separated male and female individuals in the FL strain. For two representative sex-associated indels, PCR-based genotyping methods were developed and validated. Functional annotation identified putative candidate genes for sex determination, including PKD1L1, 5-HTRL, SCP, and CCKRa. Comparative analysis of variants within PKD1L1 across wild, farmed, and selectively bred populations revealed a progressive enrichment of male-linked alleles in domesticated and selectively bred groups, particularly in male individuals. This study provides direct evidence that sex in the Fujian oyster is genetically determined and reveals that domestication and artificial selection may drive the emergence of major sex-determining loci, offering important insights into the genetic basis of sex determination in the Fujian oyster, and establishing a theoretical and practical foundation for molecular marker-assisted breeding of monosex lines for this species.

CDIP-ChatGLM3: A dual-model approach integrating computer vision and language modeling for crop disease identification and prescription - Changqing Yan; Zeyun Liang; Han Cheng; Shuyang Li; Guangpeng Yang; Zhiwei Li; Ling Yin; Junjie Qu; Jing Wang; Genghong Wu; Qi Tian; Qiang Yu; et al. (Computers and Electronics in Agriculture, 2025)

Rapid and simple detection of alfalfa mosaic virus using RT-RPA-CRISPR-Cas12a based lateral flow assay in alfalfa crops in China - Han Yan; Cheng Guo; Lijun Zhao; Ling Chen; Shuxia Yin (Crop Protection, 2025)

Dietary isoleucine requirement of grass carp (Ctenopharyngodon idella) based on growth performance, muscle nutritional value, and extracellular matrix gene expression - Kaixuan Ren; Lin Feng; Pei Wu; Yang Liu; Dong Han; Wenbing Zhang; Ling Tang; Shuwei Li; Shengyao Kuang; Xiaoqiu Zhou; Weidan Jiang (Aquaculture, 2025)

Nitrogen fixation in Pampinifervens, a new species-rich genus of Aquificaceae that inhabits a wide pH range in terrestrial hot springs - Marike Palmer; Nancy O. Nou; Lara A. Turello; Carolyn E. Power; John C. Ong; Jonathan K. Covington; Dengxun Lai; Xavier Mayali; Anna-Louise Reysenbach; Yan-Ling Qi; Jeremy A. Dodsworth; Jian-Yu Jiao; et al. (Systematic and Applied Microbiology, 2025)

Refining historical forest cover mapping and change analysis with time series algorithm-based samples transfer - Qianhuizi Guo; Ling Han; Liangzhi Li; Songjie Qu (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Biodegradation of poly(butylene adipate-co-terephthalate) film by heat-tolerant bacterium Bacillus sp. PBAT4 - Yulong SUN; Lei GE; Ling WANG; Han WU; Michael Gatheru WAIGI; Juan LIU (Pedosphere, 2025)

Gut microbiota induces host midgut immune response and contributes to defending against Bt Cry1Ac protoxin in Ostrinia furnacalis - Shuzhong Li; Zitian Wang; Fuyun Li; Ling Fang; Zhaoyang Han; Honglun Bi; Congjing Feng (Journal of Invertebrate Pathology, 2025)

Pressure makes diamonds: Enhanced permeation resistance to petroleum hydrocarbons of a novel in-situ mixed wall material - Zhe-Yuan Jiang; Xian-Lei Fu; Yu-Ling Yang; Wei-Yi Xia; Min Wang; Heng Zhuang; Zi-Han Lu; Yan-Jun Du (Journal of Hazardous Materials, 2025)

Metals link to diabetes: Insights from a national cross‐sectional investigation - Yang Zhou; Long Zhang; Tong Zheng; Hongyan Li; Yajing Han; Wenjie Meng; Hongxuan Kuang; Chenyin Dong; Zi ling Yu; Xiaohui Zhu; Guocheng Hu; Guang-Hui Dong; et al. (Journal of Environmental Sciences, 2025)

In-situ construction of BiOBr/UiO-66(Zr/Ce) S-scheme heterojunction for efficient selective photocatalytic CO2 reduction to CO - Mengting Shen; Ling Wang; Man Zhou; Liwei Lin; Han Li; Yanan Wang; Song Xu; Zhongyu Li (Fuel, 2025)

Optimizing patterned laser-induced graphene strain sensors via novel piezoresistive modeling and multi-objective analysis - Jia-Chen Shang; Wen-Feng Pan; Wen-Hao Zhao; Heng Yang; Yu-Yi Chen; Rui Wang; Ri-Han Wang; Ling-Yu Sun; Yao-Guang Cao; Shi-Chun Yang (Chemical Engineering Journal, 2025)

Potassium-doping double perovskite with improved oxygen reaction activity and durability cathode for dual-function ceramic electrochemical cells - Ao Zhao; Fangjun Jin; Wenjing Zhang; Yaqiong Guo; Zhen Wang; Ning Sun; Yuan Gao; Fangshen Liu; Xinxin Wang; Kun Zheng; Donglin Han; Yihan Ling (Chemical Engineering Journal, 2025)

Targeting mitochondrial dysfunction: an innovative strategy for treating renal fibrosis - Yi-Jin Wu; Yan-Rong Yang; Ya-Ling Yan; Han-Yinan Yang; Jun-Rong Du (Molecular and Cellular Biochemistry, 2025)

Harnessing bio-modified coal gangue for mine wastewater remediation: a sustainable approach - Kaili Xu; Wen Zhong; Ling Qian; Fumeng Xia; Xiaoqing Han; Xuan Yu; Xianbin Zhu (Environmental Geochemistry and Health, 2025)

Ecological security evaluation and early warning of ski tourism destinations - Chengcai Tang; Ying Han; Ling Jiang (Journal of Geographical Sciences, 2025)

Vertical bearing capacity of HSCM pile groups in marine soft clay - Jun-nan Zhao; Zhong-ling Zong; Yun-han Huang; Pai Jiang; Yi-min Fan; Hang Cen (Marine Georesources & Geotechnology, 2025)

Cadmium induces autophagy via IRE1 signaling pathway activated by Ca2 + in GC-2spd cells - Yue Han; Juan Dai; Jinxin Cheng; Yan He; Chengkun Zhao; Rui Li; Yaqin Zhang; Ling Zhang; Ting Zhou; Yuqin Shi (Reproductive Toxicology, 2025)

Machine learning based prediction by PlantCdMiner and experimental validation of cadmium-responsive genes in plants - Chaoqun Xu; Ling Sun; Lu-Dan Zhang; Ze-Jun Guo; Ji-Cheng Wang; Li-Han Zhuang; Dong-Na Ma; Ling-Yu Song; Jing Li; Qian-Su Ding; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2025)

Polarization of dryland vegetation response to spring flood - Shouguo Zhang; Han Wang; Xiwen Zhang; Guanglei Li; Ling Zhang; Chang Ge; Jiabin Wang; Jiansheng Wu; Jian Peng (Journal of Environmental Management, 2025)

Proteomic and transcriptomic analysis of the effects of SRBSDV infection on saliva secretion in WBPH - Qing-Ling Qi; Xiao-Han Xu; Shiqiang Xu; Jian-Ping Chen; ZongTao Sun; Wei Wu (Insect Biochemistry and Molecular Biology, 2025)

Role of macrophage ATP metabolism disorder in SiO2‑induced pulmonary fibrosis: a review - Hui-jie Hu; Yuan-yuan Fu; Shu-ling Du; Yu-han Zhang; Zhao-qiang Zhang; Gui-zhi Han (Purinergic Signalling, 2025)

Simultaneous high molecular weight PAHs degradation and chromate and arsenite detoxification by Altererythrobacter sp. H2 - Qun Han; Mei-Ling Yang; Ze-Shen Liu; Ying-Hao Zhao; Xue-Hui Liu; Guo-Min Ai; Wei-Hong Qin; Xing-Yu Liu; De-Feng Li (Journal of Hazardous Materials, 2025)

Deep learning in remote sensing image matching: A survey - Liangzhi Li; Ling Han; Yuanxin Ye; Yuming Xiang; Tingyu Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Potentially texture-modified food for dysphagia: Impact of Polygonatum sibiricum polysaccharide addition on gelling properties, microstructure and digestibility of bovine tendon collagen-cassava starch composite gels - Yuhong Lin; Zhuo Wang; Chaoxue Shi; Ling Han; Qunli Yu (Food Hydrocolloids, 2025)

Design of four-level phase-change memory Ge2Sb2Te5/Ge50Te50 bilayer films and study of their crystallization behaviors - Ling Liu; Han Gu; Qiyu Cai; Liqi Zhu; Jie Song; Weihua Wu; Zixin Wang; Tianshu Lai (Chemical Engineering Journal, 2025)

Diluted swine and aquaculture wastewater enhance carbon sequestration and nutrient removal by the red seaweed Agardhiella subulata - W.Sanjaya Weerakkody; Hsueh-Han Hsieh; Vicente G Abedneko; Ka Hin Ling; Tzu-Chieh Chung; Zih-Yi Wang; Yung-Yen Shih; Tse-Min Lee; Chen Xu; Peter H. Santschi; Chin-Chang Hung (Bioresource Technology, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Drying–rewetting cycles determine maize growth by shifting microbial community assembly and coexistence patterns - Ling Ma; Guixiang Zhou; Lin Chen; Zhongjun Jia; Hongtao Zou; Congzhi Zhang; Donghao Ma; Changdong Han; Jiabao Zhang (Plant and Soil, 2025)

Effect of hydrochemical conditions on transport of HFPO-DA in saturated quartz sand and limestone porous media - Yanfeng Shi; Xinle Han; Lixingzi Wu; Ling Fu; Weina Xue; Xuli Jing; Jing Xu; Zhibin Zhang; Botao Ding (Environmental Geochemistry and Health, 2025)

Bacteria in the Phylum Bacillota Degrade Nicotine Through the Variant of Pyridine and Pyrrolidine Pathway - Xiu-Ming Liu; Xuan Hai; Cong-Jian Li; Yu-Fan Han; Xing Chen; Yu-Jin Fan; Jian Wu; En-Min Zhou; Yuan-Dong Li; Ling-Ling Yang; Yan-Qing Duan; Xiao-Yang Zhi (Current Microbiology, 2025)

Correction to: Bud development, flower phenology and life history of holoparasitic Rafesia cantleyi - Suk Ling Wee; Shwu Bing Tan; Sue Han Tan; Bernard Kok Bang Lee (Journal of Plant Research, 2025)

Mapping of paddy field by Sentinel-1 SAR images and cadastre data in Yunlin, Taiwan - Jui-Han Yang; Kuo-Hsin Tseng; Shu-Ling Chen; Ya-Lun Tsai; Ray. Y. Chuang; Aive Liibusk; Chi-Farn Chen (International Journal of Remote Sensing, 2025)

Evaluation of the Products from Hydrothermal Liquefaction of Palm Empty Fruit Bunch - Brendan Ong Wei Ling; Han Hao Chon; Rui Hong Teoh; Suchithra Thangalazhy-Gopakumar (BioEnergy Research, 2025)

Integrated GWAS and transcriptome analysis reveals regulatory networks underlying growth in improved grass carp - Yakui Tai; Ling Liu; Yiyan Zeng; Mengdan Li; Mengxue Luo; Wuhui Li; Hailu Zhou; Jinhui Zhang; Xiaohuan Han; Conghui Yang; Ming Wen; Li Ren; et al. (Aquaculture, 2025)

Corrigendum to “Adaptive search based Grey Wolf optimization algorithm for multi-objective optimization of ethylene cracking furnace” [Swarm Evol. Comput. 92 (2025) 101,810] - Zhiqiang Geng; Weikang Kong; Xintian Wang; Ling Wang; Yongming Han (Swarm and Evolutionary Computation, 2025)

Incidence, risk factors, and prognosis of hospitalized mechanical eye injuries in China: data from China Ocular Trauma Study (COTS) 2021–2023 - Han Han; Yongjie Chen; Gao Si; Guowei Huang; Jiayi Song; Wenfang Zhang; Danyan Liu; Jie Zhong; Xuemin Jin; Dawei Sun; Shenwen Liu; Yanming Huang; et al. (Science Bulletin, 2025)

AMF and DSE diversity and colonization characteristics of Salvia miltiorrhiza in different genotypes and growth periods - Tingting Han; Wanyun Li; Ling Li; Chao He; Xianen Li (Rhizosphere, 2025)

Undescribed alkaloids, peptides and polyketides from marine sediment-derived fungus Aspergillus terreus PPS1 - Yao-Yao Zheng; Guang-Shan Yao; Jiao-Jiao Li; Na Han; Jun-Qiu Mao; Ya-Hui Zhang; Ling Lv; Yang Liu; Chang-Yun Wang (Phytochemistry, 2025)

Preparation of ZnWO4/Bi4O5I2 composite photocatalyst and study of its antibacterial properties - Ling Zhang; Zixin Wang; Ruolan Wei; Tengyuan Gao; Jingmei Li; Luyin Zhao; Deming Han; Xiulong Li (Journal of Water Process Engineering, 2025)

Newborn metabolomic signatures of maternal vanadium exposure and reduced birth size - Ya Xie; Gaga Mahai; Dejuan Zheng; Xinyu Zhang; Ling Yu; Hongxiu Liu; Yuanyuan Li; Shunqing Xu; Han Xiao; Wei Xia (Journal of Hazardous Materials, 2025)

Co-hydrothermal carbonization of polyvinyl chloride and shrimp shells for carbon materials: Synergistic conversion and electrochemical properties - Mengxue Ling; Dachao Ma; Qisong Zhong; Cheng Liao; Zheng Liu; Dongbo Wang; Biao Han; Qingge Feng (Journal of Environmental Chemical Engineering, 2025)

Regional responses of ecosystem service security to land use changes and driving mechanisms: Insights from nearly 40 years of observations in Shaanxi, China - Songjie Qu; Ling Han; Liangzhi Li (Journal of Environmental Chemical Engineering, 2025)

Diversity and dynamic response of anaerobic ammonia oxidation granular sludge - Jiahong Ye; Xiang Li; Yan Yuan; Yayi Wang; Yong Huang; Jun Ma; Han Wang; Pengze Dang; Pei-ling Xu (Journal of Environmental Sciences, 2025)

PDLSCs-ApoEVs enhance bone regeneration through MAPK1/3-induced STC1 upregulation in endothelial cells via the FOS pathway - Yadong Guo; Janak Lal Pathak; Yinyin Huang; Jingru Han; Junyan Zeng; Ling Chen; Yongshan Li; Wenbo Du; Liping Wang; Lan Yang (Chemical Engineering Journal, 2025)

The mouse resource at National Resource Center for Mutant Mice of China - Bingzhou Han; Dongshen Chen; Zhong Chen; Ting Wang; Kaiyuan Zi; Rui Feng; Xiaoliu Yang; Ling’en Li; Juan Liang; Xiang Gao (Mammalian Genome, 2025)

Rhizobacterium streptomyces sp. NEAU-383 as a potential biocontrol agent to control tomato bacterial wilt - Ling Ling; Tianxin Zhao; Shanshan Zhang; Yanfang Luo; Zhengke Song; Han Wang; Wensheng Xiang; Junwei Zhao; Xiangjing Wang (Brazilian Journal of Microbiology, 2025)

Epidemiological status and genome characteristics of canine parvovirus in China from 2022 to 2024 - Haoqi Li; Hu Zhou; Linfeng Li; Xiaohu Han; Qinghua Shang; Chengguang Zhang; Ming Zhou; Zhen F. Fu; Jianqing Zhao; Ling Zhao (Archives of Virology, 2025)

Enhancing the coupling coordination of soil–crop systems by optimising soil properties and crop production via subsoiling - Jingyi Shao; Ling Liu; Jichao Cui; Hong Yang; Yecheng Zhang; Ruxin Li; Yi Lv; Yifei Ma; Qin Fang; Shengkai Sun; Siyu Chen; Huifang Han (Soil and Tillage Research, 2025)

Experimental demonstration of reconstructing quantum states with generative models - Xuegang Li; Wenjie Jiang; Ziyue Hua; Weiting Wang; Xiaoxuan Pan; Weizhou Cai; Zhide Lu; Jiaxiu Han; Rebing Wu; Chang-Ling Zou; Dong-Ling Deng; Luyan Sun (Science Bulletin, 2025)

Two pathways for reducing soil aggregate organic carbon mineralisation via minimum tillage under a long-term field experiment - Xinkun Liu; Ruxin Li; Yi Lv; Xianfeng Zhang; Yecheng Zhang; Qisong Gao; Yuzhao Ma; Fiston Bizimana; Ling Liu; Huifang Han; Tangyuan Ning (Journal of Environmental Management, 2025)

Spice aldehydes improve emulsification stability of β-carotene by Schiff base reaction binding sodium caseinate as emulsion surface stabilizer - Ya Yu; Mengting Yuan; Ling Zhou; Yanan Liu; Ya Chen; Dongxu Wu; Zhihong Chen; Qingqing Yuan; Yang Han; Juhua Wang; Xiuheng Xue (Food Chemistry, 2025)

Probabilistic multi-hazard risk assessment of high-rise buildings subjected to concurrent earthquakes and strong winds - Qian-Qian Yu; Ling-Han Liu; Xiang-Lin Gu; Yao-Yao Zhang (Engineering Structures, 2025)

Formaldehyde oxidation reaction enhanced by interface engineering of Cu/Cu2O/Co(OH)2 composite electrocatalyst for bipolar hydrogen production - Zi Qiang Ma; Chang Bao Han; Wen Kang Zhao; De Cai Fang; Yi Lin Zhao; Chang Xin Liu; Xinxin Wang; Ling Sun; Xue Mei Song (Chemical Engineering Journal, 2025)

Correlation between the utilization of sodium-glucose cotransporter-2 (SGLT2) inhibitors and the risk of dementia: a nationwide population-based study in Taiwan - Wu-Lung Chuang; Stella Chin-Shaw Tsai; Yi-Chun Yang; Tsai-Ling Hsieh; Heng-Jun Lin; Yu-Han Huang; Fuu-Jen Tsai; Kuang-Hsi Chang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Zoning effects on fish populations in a key Chinese multi-use marine protected area - Xu Zeng; Yue Liu; Shouyu Zhang; Cong Zeng; Dongyan Han; Kisei R. Tanaka; Mackenzie D. Mazur; Ling Cao (Ocean & Coastal Management, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Seismic response and failure mechanism of caisson: A centrifuge shake-table investigation - Linlu Zhou; Zifei Han; Lei Su; Hua-Ping Wan; Xianzhang Ling (Soil Dynamics and Earthquake Engineering, 2025)

Exogenous NaHS maintains storage quality of Prunus salicina ‘Wushan plum’ by regulating the antioxidant system, endogenous H2S, ethylene and NO metabolism - Saiying Han; Ling Liu; Lilei Wang; Jin Han; Yeru Ai; Huali Wang; Kaifang Zeng; Jian Ming; Lili Deng (Postharvest Biology and Technology, 2025)

Ultrasound-assisted deep eutectic solvent extraction of kukoamine A and kukoamine B from Lycii cortex - Xiaomei Wang; Jinxia Hu; Ling Ma; Zhiming Han; Jianfei Liu; Zhibin Lu; Dong Pei; Ningli Wang; Duolong Di (Phytochemistry Letters, 2025)

Vertical and lateral bearing performance of bidirectional Helix-Stiffened cement mixing piles on marine soft soil sites: Field tests and numerical simulations - Jun-nan Zhao; Zhong-ling Zong; Yun-han Huang; Meng-meng Lu; De-long Huang; Cheng-yu Guo (Ocean Engineering, 2025)

Long-term conservation tillage changes the diversity, assembly and network stability of soil diazotrophic community - Ling MA; Guixiang ZHOU; Jiabao ZHANG; Zhongjun JIA; Hongtao ZOU; Lin CHEN; Congzhi ZHANG; Donghao MA; Changdong HAN (Pedosphere, 2025)

Efficient capture of 99TcO4-/ReO4- via node and linker bifunctional anion exchange covalent organic frameworks - Ling Yuan; Han Zhang; Hang Yu; Rongming Xu; Chenghan Ji; Weiming Zhang (Journal of Hazardous Materials, 2025)

Organic amendments enhance rhizosphere carbon stabilization in macroaggregates of saline-sodic soils by regulating keystone microbial clusters - Changdong Han; Lin Chen; Zhongjun Jia; Hongtao Zou; Ling Ma; Congzhi Zhang; Guixiang Zhou; Donghao Ma; Jiabao Zhang (Journal of Environmental Management, 2025)

Impacts of forest expansion on microbial diversity and community assembly in fragmented mountain ecosystems - Wen-Hui Lian; Wen-Sheng Zhao; Jia-Rui Han; Chao-Jian Hu; Guo-Yuan Shi; Fang Chen; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Mukhtiar Ali; Lei Dong; Ting Zhou; et al. (Environmental Research, 2025)

Electrospun groove shaped fibers with excellent hemocompatibility and highly selective capture of live bacteria from blood - Jianxu Bao; Shifan Chen; Xianda Liu; Ziyue Ling; Chunji Jiang; Zhaoxi Han; Wenjie Wang; Ran Wei; Changsheng Zhao; Weifeng Zhao (Chemical Engineering Journal, 2025)

Multiscale progressive 3D geological modeling based on isochronous stratigraphy identification in urban underground space - You Zhang; Ling-Ling He; Yu-Yong Jiao; Han-Fa Peng; Shun-Chang Liu; Qian-Bing Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Research progress of non-coding RNA regulating the role of PANoptosis in diabetes mellitus and its complications - Guangyu Han; Kaibo Hu; Tianfeng Luo; Wenting Wang; Deju Zhang; Liu Ouyang; Xiao Liu; Jianping Liu; Yuting Wu; Jianqi Liang; Jitao Ling; Yixuan Chen; et al. (Apoptosis, 2025)

Correction: Curzerenone inactivates the nuclear factor-kappa B signaling to suppress malignancy and immune evasion in cervical cancer by targeting CSNK2B - Yangyan Sun; Min Wang; Jing Ling; Qunying Wu; Guorong Han; Junxu Zhou (Human Cell, 2025)

Mid-to-late Cenozoic tectonostratigraphic archives of the Qingshuihe Basin, NW China: tracing northeastward stepwise growth of the Tibetan Plateau - Jingxiong Tian; Han Zheng; Yanyun Ma; Wenzhong Wu; Yu Ma; Shengjin Huang; Ling He; Mingtao Li; Fang Liu; Xuedong Ma (International Geology Review, 2025)

Dietary supplementation of Litsea cubeba oil promotes growth and intestinal immunity in GIFT tilapia - Fu-Yan Chen; Ying Bai; Gan Yang; Han-Jing Yan; Liu-Yang Li; Zhi-Mou Liu; Ju-Ping Wen; Zhen-Bin Wang; Jun-Hong Xia; Meng-Ling He (Aquaculture, 2025)

Molecular identification of three cytochrome P450 genes and their potential roles in insecticides tolerance in Grapholita molesta (Busck) - Hui Han; Ming-Gao Li; Kai-Yang Xing; Qi Wang; Jun Hu; Zhi-Guo Zhao; Qin Yu; Rui-Yan Ma; Ling-Ling Gao; Yan-Qiong Guo (Pesticide Biochemistry and Physiology, 2025)

Targeted isolation of lignans and triterpenoids from kadsura coccinea by molecular networking and anti-RA-FLS activity - Shi-qi Liu; Qing-ling Xie; Ya-si Deng; Ling Liang; Han-wen Yuan; Bin Li; Huang-he Yu; Xing Tian; Yi-xing Qiu; Guy Paulin Kemayou Mouthe; Nuzhat Shehla; Ye Zhang; et al. (Phytochemistry, 2025)

Carbonate composite materials for the leaching remediation of uranium-contaminated soils: Mechanistic insights and engineering applications - Juncheng Han; Guangming Xu; Xinyao Liu; Likun Jiang; Kexin Shao; Haotian Yang; Guangsheng Zhu; Aizhong Ding; Zhaorong Shang; Ling Chen; Junfeng Dou (Journal of Hazardous Materials, 2025)

Spatial differentiation of carbon emissions from energy consumption based on machine learning algorithm: A case study during 2015–2020 in Shaanxi, China - Hongye Cao; Ling Han; Ming Liu; Liangzhi Li (Journal of Environmental Sciences, 2025)

Extraction of short-chain fatty acid ethyl Ester in Baijiu using covalent organic framework–based magnetic nanoparticles: Theoretical screening and experimental validation - Xiaolong Shang; Ying Han; Xudong Lian; Siting Ye; Ling Ao; Baoguo Sun; Rong Liu; Pan Zhen; Yongqing Zhang; Yintao Jia; Wei Dong; Xiaotao Sun; et al. (Food Chemistry, 2025)

Characterization of microplastic distribution, sources and potential ecological risk assessment of domestic sewage from ships - Na Lu; Qing Su; Yuxia Li; Ling Qu; Lingna Kong; Jiayi Cheng; Chao Wang; Jian Sun; Jianbo Han; Xiaomeng Wang (Environmental Research, 2025)

Evaluating the influence of topography data resolution on lake hydrodynamic model under a simulation uncertainty analysis framework - Quan Han; Ling Zhou; Wenchao Sun; Jinqiang Wang; Chi Ma (Environmental Modelling & Software, 2025)

Efficient glycolysis of Poly(ethylene terephthalate) to bis(hydroxyethyl) terephthalate catalyzed by non-metallic deep eutectic solvent - Xin Wei; Jingwen Qiu; Han Wang; Weizhong Zheng; Weizhen Sun; Ling Zhao (Chemical Engineering Journal, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Synthesis and antitumor activity of ultra-low molecular weight hyaluronic acid-decorated camptothecin conjugates - Changsheng Chen; Henan Zhang; Jingjun Han; Lin Yang; Shuang Li; Qingwen Jia; Junqiang Fang; Peixue Ling; Shuaishuai Wang (Carbohydrate Polymers, 2025)

Polymeric saccharides: Effect on physical characteristics and creaminess perception of non-fat whipped cream analogue - Yameng Han; Ling Zhu; Hui Zhang; Tongtong Liu (Carbohydrate Polymers, 2025)

Growth trajectory of Yiling sheep and its related genetic parameters - Yumeng Shen; Zhan Xu; Guiqiong Liu; Xunping Jiang; Xu Wang; Jihua Li; Ling Sun; Yan Chen; Shiping Yang; Han Yang (Tropical Animal Health and Production, 2025)

Conservation tillage regulates the influence of drought on multitrophic network complexity and improves soil multifunctionality - Ling Ma; Guixiang Zhou; Lin Chen; Zhongjun Jia; Hongtao Zou; Congzhi Zhang; Donghao Ma; Changdong Han; Jiabao Zhang (Applied Soil Ecology, 2025)

Energy consumption and emission analysis for electric container ships - Guiyang Ling; Chuanfeng Han; Zhensheng Yang; Junliang He (Ocean & Coastal Management, 2025)

The evolutionary advantage of artemisinin production by Artemisia annua - Qinggang Yin; Li Xiang; Xiaoyan Han; Yujun Zhang; Ruiqing Lyu; Ling Yuan; Shilin Chen (Trends in Plant Science, 2025)

Adaptive search based Grey Wolf optimization algorithm for multi-objective optimization of ethylene cracking furnace - Zhiqiang Geng; Weikang Kong; Xintian Wang; Ling Wang; Yongming Han (Swarm and Evolutionary Computation, 2025)

Enhanced removal of heavy metals by wetland plant-microbiome symbiont: Prospect of potential strategies and mechanisms for environmental heavy metal regulation - Ling LIU; Xiaoyi FAN; Yuan HAN; Hongjie WANG (Pedosphere, 2025)

Hypoxia-inducible factor-1α promotes ferroptosis by inducing ferritinophagy and promoting lactate production in yak longissimus thoracis et lumborum postmortem - Xijin Zhu; Chao Yang; Qunli Yu; Ling Han (Meat Science, 2025)

Nitrogen-doped porous carbon supported nickel catalysts for efficient hydrodeoxygenation of lignin-derived vanillin to 2-methoxy-4-methylphenol in ethanol - Jinye Wei; Dachao Ma; Mengxue Ling; Hongchang Hu; Qisong Zhong; Guozi Liu; Zheng Liu; Dongbo Wang; Biao Han; Qingge Feng (Journal of Environmental Chemical Engineering, 2025)

Solvent effects on the preparation of CuO-ZnO-ZrO2-Al2O3 catalyst by citrate complexing method for CO2 hydrogenation to methanol - Xuan Ling; Guo Wang; Jian Han; Lei Wang; Jun Yu; Dongsen Mao (Fuel, 2025)

Thermodynamic analysis of the effect of palm stearin on fully hydrogenated soybean oil coatings in granular micronutrient premixes - Y.K. Kiki Chan; Fletcher Han; Yu-Ling Cheng; Levente L. Diosady (Food Chemistry, 2025)

Insight into volatile metabolites and key odorants in black teas processed from Jianghua Kucha tea germplasm (Camellia sinensis var. assamica cv. Jianghua) - Ying-Lin Zhu; Wei-Xuan Li; Yu-Hui Zhang; Han Yan; Long-Yu Guo; Yue Zhang; Hai-Peng Lv; Ling-Hong Zhou; Zhi Lin; Wen-Liang Wu; Yin Zhu (Food Chemistry, 2025)

Achieving efficient multifunctional platform utilizing sugarcane for water-electricity cogeneration and dyes reduction - Haitao Li; Qifan Qian; Xuan Li; Hui Cheng; Bingquan Wu; Xing Yi Ling; Jie Han (Chemical Engineering Journal, 2025)

Enhancement of the yield of poly (ethylene terephthalate) hydrolase production using cell membrane protection strategy - Xiao-Qian Chen; De-Ming Rao; Xing-Yu Zhou; Yang Li; Xiao-min Zhao; De-min Kong; Han Xu; Chu-Qi Feng; Lei Wang; Ling-Qia Su; Zheng-Fei Yan; Jing Wu (Bioresource Technology, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Salinity affects C/N ratio through differential responses of carbon and nitrogen metabolism in mangrove Avicennia marina leaves revealed by combined analysis of transcriptome and metabolome - Jing Li; Ling-Yu Song; Ze-Jun Guo; Chao-Qun Xu; Lu-Dan Zhang; Ji-Cheng Wang; Han-Chen Tang; Ming-Jin Dai; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2025)

SaTDT enhanced plant tolerance to NaCl stress by modulating the levels of malic acid and citric acid in cells - Xiangyu Wei; Li Xu; Suisui Dong; Nina He; Qianqian Xi; Dan Yao; Qianqian Wang; Yue Zuo; Chen Ling; Meiting Qi; Wen Bai; Kai Han; et al. (Plant Molecular Biology, 2025)

Design, synthesis and herbicidal activity of novel cyclohexanedione derivations containing pyrazole and pyridine groups as potential HPPD inhibitors - Shuai-Tao Hou; Ling Han; Wen-Rui Li; Guang-Yu Dai; Yu Liu; Ai-Min Lu; Chun-Long Yang; Min Chen (Molecular Diversity, 2025)

Effects of fine particulate matter bound heavy metals on intentional self-harm deaths in Guangzhou, China, insight from core chemical constituents - Chunyan Gui; Han Zhang; Zhanlu Lv; Tao Liu; Shengbing Yu; Yanjun Xu; Hualiang Lin; Jianpeng Xiao; Wenjun Ma; Bin Luo; Ling-Chuan Guo (International Journal of Biometeorology, 2025)

Medium modification of Cynanchum wilfordii adventitious root culture for the production of C21 steroidal glycosides, polysaccharides, and polypeptides using orthogonal design methods - Han-Xi Li; Yu-Qing Guo; Wei-Qi Ye; Zhong-Yu Zhou; Ling-Hong Bai; Xuan-Chun Piao; Mei-Lan Lian (In Vitro Cellular & Developmental Biology - Plant, 2025)

Increased carbon sequestration of different straw return depths varies temporally - Jin Li; Xiaoyu Li; Ling Ma; Guangyan Liu; Yanyu Han; Jiaqi Li; Roland Bol; Hongtao Zou (Applied Soil Ecology, 2025)

UUVDNet: An efficient unmanned underwater vehicle target detection network for multibeam forward-looking sonar - Xuyang Zhang; Han Pan; Zhongliang Jing; Kaiyao Ling; Pai Peng; Buer Song (Ocean Engineering, 2025)

Entropy-TOPSIS-based quantitative evaluation of specific roles of the enhanced coagulation process in multi-objective sewage pre-concentration by microfiltration - Yukun Xing; Xiaoxiang Zhang; Simeng Han; Lanxin Ling; Xiyuan Feng; Xiaoyu Zhang; Zhaotong Liu; Zhengyu Jin (Journal of Water Process Engineering, 2025)

Nobiletin, an activator of the pyruvate kinase isozyme M1/M2 protein, upregulated the glycolytic signalling pathway and alleviated depressive-like behaviour caused by artificial light exposure at night in zebrafish - Meng-ling Zhang; Xiao-peng Li; Li-fang Gao; Jian Liu; Zi-jun Bi; Yu-han Miao; Yang Shan; Huan-ling Yu (Food Chemistry, 2025)

Tapioca starch/konjac gum-based composite film incorporated with nanoliposomes encapsulated grape seed oil: Structure, functionality, controlled release and its preservation role for chilled mutton - Zhaoyang Song; Zhixuan Zang; Yinjuan Cao; Yabin Ma; Bingzi Li; Ling Han; Qunli Yu (Food Chemistry, 2025)

Preparation of copper sulfate/natamycin/carboxymethylcellulose/agar film for synergistic antibacterial application in fruit via causing cuproptosis of Escherichia coli O157: H7 - Jinyue Sun; Han-Xiao Zhuang; Jia-Neng Pan; Qian-Jun Shen; Hui-Ling Shen; Wen-Wen Zhou (Food Bioscience, 2025)

Constructing chromium-tolerance La0.6Sr0.4Co0.2Fe0.8O3-δ cathode for solid oxide fuel cells using entropy-assisted surface engineering - Xu Han; Qi Shao; Kaixin Li; Yuan Gao; Bo Wei; Zimin Cai; Kun Zheng; Peizhong Feng; Zhe Lv; Yihan Ling (Chemical Engineering Journal, 2025)

Achieving efficient autotrophic nitrogen removal in anaerobic membrane bioreactor plus membrane aerated biofilm reactor by regulating nutrient ratios - Yu-Lin Han; Ling-Dong Shi; He-Ping Zhao (Bioresource Technology, 2025)

Mechanism Analysis of Selenium-Containing Compounds in Alleviating Spinal Cord Injury Based on Network Pharmacology and Molecular Docking Technology - Wen Han; Ling Xie; Chaochao Ding; Dandan Dai; Nan Wang; Jianmin Ren; Hailin Chen; Suyan Zhu; Jian Xiao; Hongbin Xu (Molecular Neurobiology, 2025)

Integrative analysis of transcriptome and proteome wide association studies prioritized functional genes for obesity - Qi-Gang Zhao; Xin-Ling Ma; Qian Xu; Zi-Tong Song; Fan Bu; Kuan Li; Bai-Xue Han; Shan-Shan Yan; Lei Zhang; Yuan Luo; Yu-Fang Pei (Human Genetics, 2025)

Axial Bearing Performance of Helix Stiffened Cement Mixing Piles in Sandy Soils - Jun-nan Zhao; Zhong-ling Zong; Yun-han Huang; Pai Jiang; Wei Jin; Hang Cen (Geotechnical and Geological Engineering, 2025)

Curzerenone inactivates the nuclear factor-kappa B signaling to suppress malignancy and immune evasion in cervical cancer by targeting CSNK2B - Yangyan Sun; Min Wang; Jing Ling; Qunying Wu; Guorong Han; Junxu Zhou (Human Cell, 2024)

Changes in the small-molecule fingerprints of rice planted near an industrial explosion site in Taiwan - Wen-Ling Chen; Husan-Yu Tai; Chang-Chuan Chan; Hung-Chien Lin; Ting-Hsuan Hung; Mong-Hsun Tsai; Chia-Cheng Wei; Yu-San Han; Chuan-Chou Shen (Environmental Science and Pollution Research, 2024)

Pilot scale application of 226Ra-contaminated soil leaching remediation - Juncheng Han; Guangming Xu; Kexin Shao; Haotian Yang; Aizhong Ding; Zhaorong Shang; Hongtu Sun; Ling Chen; Zhiyuan He; Qiao Li; Hongbo Fan; Junfeng Dou (Chemosphere, 2024)

An eco-friendly kapok fiber-supported liquid microextraction using natural deep eutectic solvent as extractant for convenient biological samples preparations: A proof-of-concept study - Wen-Chao Han; Xin-Ying Wang; Gao-Biao Wang; Han-Juan Zhang; Pei Yang; Jin-Chao Wei; Yu-Ling Yang; Dong-Dong Yuan; Di Chen (Sustainable Chemistry and Pharmacy, 2024)

Multi-omics analysis of the effects of low-temperature storage on chilling injury of bitter gourd - Hongwei Wang; Ling Li; Da-Wen Sun; Lili Ma; Lichun Han; Xuelian He; Qing Wang; Christopher B. Watkins; Jinhua Zuo; Yanyan Zheng (Postharvest Biology and Technology, 2024)

Early postnatal and concurrent exposure to metals and neurobehavioral outcomes at 5 years: Associations with individual environmental exposures and mixtures - Sui-Ling Liao; Shen-Hao Lai; Yuan-Ting Hsu; Li-Chen Chen; Ming-Han Tsai; Man-Chin Hua; Tsung-Chieh Yao; Kuan-Wen Su; Kuo-Wei Yeh; Chih-Yung Chiu; Shau-Ku Huang; Jing-Long Huang (NeuroToxicology, 2024)

AmTPS6 promotes trehalose biosynthesis to enhance the Cd tolerance in mangrove Avicennia marina - Ling-Yu Song; Jing Li; Lu-Dan Zhang; Zhao-Yu Guo; Chao-Qun Xu; Li-Wei Jiang; Jin-Yu Liu; Ji-Cheng Wang; Qing-Hua Li; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2024)

Disease risk of the foliar endophyte Colletotrichum from invasive Ageratina adenophora to native plants and crops - Ai-Ling Yang; Yi-Shan Chen; Liang Mei; Jing Guo; Han-Bo Zhang (Fungal Ecology, 2024)

Effects of fishing stress on fatty acid and amino acid composition and glycolipid metabolism in triploid rainbow trout - Banghua Xia; Dandan Zhao; Qirui Hao; Junfei Yu; Yue Han; Ling Ling; Rongwei Zhao; Junwei Zhao (Food Chemistry, 2024)

Establishment of a multiplex qPCR method for sensitive detection of proteolytic psychrotrophic bacteria in raw milk - Ling Ji; Xinling Du; Han Zhang; Fuchun Ji; Zishen Nie; Yu Xia (Food Bioscience, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Di(2-ethylhexyl) phthalate disrupts circadian rhythm associated with changes in metabolites and cytochrome P450 gene expression in Caenorhabditis elegans - Pei-Ling Yen; Ting-An Lin; Chun-Han Chang; Chan-Wei Yu; Yu-Hsuan Kuo; Tzu-Ting Chang; Vivian Hsiu-Chuan Liao (Environmental Pollution, 2024)

Molecular mechanism of immunotoxicity: Binding interaction between perfluorinated compounds and human immunoglobulin G - Qing Shi; Zekai Li; Wangzhiqian Zhao; Xiaojie Hu; Hefei Wang; Jian Wang; Miao Han; Lin Xu; Hao Sun; Chao Qin; Wanting Ling (Environmental Pollution, 2024)

Martian seismic anisotropy underneath Elysium Planitia revealed by direct S wave splitting - Jing Shi; Cunrui Han; Tao Wang; Chao Qi; Han Chen; Zhihan Yu; Jiaqi Geng; Minghan Yang; Xu Wang; Ling Chen; Hejiu Hui (Earth and Planetary Science Letters, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Structure-performance relationship and molecular structure optimization design of acid phosphate ester extractants - Bo Han; Can Chen; Shuai Li; Ling Ran; Jie Li; Zhong Zou; Yongming Chen; Hongliang Zhang (Chemical Engineering Journal, 2024)

Hinokiflavone from Platycladi cacumen as a potent broad-spectrum inhibitor of gut microbial Loop-1 β-glucuronidases: Inhibition kinetics and molecular simulation - Yue Han; Yu-Tong Liu; Lu Chen; Hao-Fan Sun; Guang-Hao Zhu; Dong-Ning Kang; Qi Zhou; Hui Tang; Yu-Ling Yin; Jie Hou (Chemico-Biological Interactions, 2024)

Straight road noise mapping prediction using probabilistic approach - Lee Hang Tan; Ming Han Lim; Yee Ling Lee; Hooi Ling Khoo (Stochastic Environmental Research and Risk Assessment, 2024)

Improving global weather and ocean wave forecast with large artificial intelligence models - Fenghua Ling; Lin Ouyang; Boufeniza Redouane Larbi; Jing-Jia Luo; Tao Han; Xiaohui Zhong; Lei Bai (Science China Earth Sciences, 2024)

Confirming the enzymatic activity and neurodevelopmental trajectory of PYCR1 mutation in one child with autosomal-recessive cutis laxa type 2 - Shaofang Shangguan; Xueyuan Zhang; Yangyang Ge; Ye Han; Ling Xiao; Yu Zhang; Hua Xie; Xiaoli Chen; Xiaoyan Wang (Molecular Genetics and Genomics, 2024)

A cross-spatial network based on efficient multi-scale attention for landslide recognition - Xu Zhang; Liangzhi Li; Ling Han (Landslides, 2024)

Efficacy and safety of 4-hydroxy-2-methyl-N-(5-methyl-2-thiazolyl)-2H-1, 2-benzothiazin-3-carboxamide 1,1-dioxide, a rapid-acting meloxicam formulation, for analgesia after orthopaedic surgery under general anaesthesia: a randomized controlled trial - Yingyong Zhou; Yan Jiang; Kaiming Duan; Qiongcan Li; Mengchang Yang; Qing Lei; Mingsheng Bao; Guijie Xie; Jie Sun; Liang Chen; Hongmei Zhou; Yanzhuo Zhang; et al. (Inflammopharmacology, 2024)

Identification and culture of functional salivary gland ductal epithelial cells - Han-Shu Zhang; You-Wei Zhao; Xin-Yi Tao; Xin Cong; Li-Ling Wu; Guang-Yan Yu; Yan Zhang (Histochemistry and Cell Biology, 2024)

Three-dimensional dynamic stability analysis of vegetation-rooted slopes - Chen Guang-Hui; Wang Ling; Ouyang Xu; Jiang Han (Bulletin of Engineering Geology and the Environment, 2024)

The food-borne carcinogenic 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) disrupts circadian rhythms and ameliorated by pterostilbene (PSB) in Caenorhabditis elegans - Chun-Han Chang; Pei-Ling Yen; Min-Hsiung Pan; Vivian Hsiu-Chuan Liao (Archives of Toxicology, 2024)

Azotosporobacter soli gen. nov., sp. nov., a novel nitrogen-fixing bacterium isolated from paddy soil - Cheng-Jie Xie; Ling Yao; Rong Tang; Shuang Han; Shang Yang; Hend Alwathnani; Christopher Rensing; Guo-Hong Liu; Shun-Gui Zhou (Antonie van Leeuwenhoek, 2024)

Using SAR imagery to extract flash flood sediment deposition area in the northern Loess Plateau - Xiaowu Ma; Juying Jiao; Bo Yang; Wenting Zhao; Qi Ling; Xinhan Zhang; Jianqiao Han; Pengfei Du; Yin Chen; Hao Chen (Journal of Hydrology, 2024)

Reseeding increased plant biomass production and soil fertility, but not plant species diversity in degraded grasslands in China - Hasbagan Ganjurjav; Mingjie Li; Ling Han; Yubao Sha; Zheng Li; Xuyang Han; Guoxu Ji; Rihan Wu; Yandan Ma; Guozheng Hu; Elise Gornish; Qingzhu Gao (Journal of Environmental Management, 2024)

Curcumin is an efficacious therapeutic agent against Chilodonella uncinata via interaction with tubulin alpha chain as protein target - Wenjia Han; Kechen Yang; Xiaoping Tan; Longkun Gao; Shenye Qu; Gengrong Zhang; Wenqi Fan; Mingzhu Liu; Erlong Wang; Pengfei Li; Fei Ling; Gaoxue Wang; et al. (Fish & Shellfish Immunology, 2024)

High-resolution carbon emission mapping and spatial-temporal analysis based on multi-source geographic data: A case study in Xi'an City, China - Ziyan Liu; Ling Han; Ming Liu (Environmental Pollution, 2024)

Highly effective fluorescence detection of UO22+ ions by an anionic Na/Eu heterometallic metal–organic framework with Lewis basic chelating sites - Feng Guo; Xue-Ling Han; Duo-Fu Li; Chun-Yang Li; Dong-Ping Li; Zhi-Kang Yao; Li-Ping Wang; Yong-Xiu Li (Chemical Engineering Journal, 2024)

Correction to: Effects of selenium application with different combinations of secondary elements on ‘Qingcui’ plum leaf nutrition and fruit quality - Xieping Sun; Shaobing Gao; Min Ling; Junyan Wang; Xinyue Zhao; Guoqiang Han (Plant and Soil, 2024)

Agricultural management reshaped the diversity patterns and community assembly of rhizosphere bacterial communities in a desert farming system - Wen-Hui Lian; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Zhi-Liang Lin; Chao-Jian Hu; Jia-Rui Han; Wen-Jun Li; Lei Dong (Applied Soil Ecology, 2024)

Isolation, identification, and technological characteristics analysis of yeast strains from Pyracantha fortuneana fruits fermentation liquid - Ling Zhu; Jiang-Yan Yu; Qing-Fang Xu; Xu Bai; Xiu Gao; Li-Fang Zhang; Wei-Liang Liu; Hao-Han Wang; Jian Cai (Archives of Microbiology, 2024)

Identifying modifiable factors and their joint effect on frailty: a large population-based prospective cohort study - Ling-Zhi Ma; Yi-Jun Ge; Yi Zhang; Xi-Han Cui; Jian-Feng Feng; Wei Cheng; Lan Tan; Jin-Tai Yu (GeroScience, 2024)

Abundance, characteristics and ecological risk assessment of microplastics in ship ballast water in ports around Liaodong Peninsula, China - Qing Su; Yuxia Li; Na Lu; Ling Qu; Xin Zhou; Yue Yu; Daping Lu; Junsong Han; Jianbo Han; Xiaotong Xu; Xiaomeng Wang (Marine Pollution Bulletin, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Oxidation and spontaneous combustion characteristics of particulate coal under stress–heat–gas interactions - Jiangkun Chao; Shuo Wei; Ling Shen; Xuefeng Han; Rongkun Pan; Jie Li; Shuang Liu; Daimin Hu (Science of The Total Environment, 2024)

Contamination characteristics and dietary intake risk of brominated flame retardants in fishes around a typical e-waste dismantling site in Southern China - Shanqi Zhou; Zhihua Qiao; Siyuan Ling; Mengru Fu; Yanna Han; Cheng Peng; Wei Zhang; Juying Lei (Science of The Total Environment, 2024)

Macroaggregate is crucial in soil carbon and nitrogen accumulation under different vegetation types in the Loess Plateau, China - Hongjian Hao; Yujie Liang; Duo Pian; Ying Zhang; Yaxian Chen; Hongtao Lai; Zhouchang Yu; Ahejiang Sailike; Rong Wang; Ling Cao; Xinhui Han; Wei Zhang (Forest Ecology and Management, 2024)

Anti-obesity effects of Lactiplantibacillus plantarum BHP03 on high-fat diet mice and its regulatory function on intestinal microbiota - Jun Meng; Pan-Pan Dong; Meng-Xi Zhu; Zheng Zhang; Jia-Hui Chen; Yue Meng; Chang-He Ding; Han Du; Dong-Ge Zheng; Ling-Guang Du (Food Bioscience, 2024)

Preparation of a novel ATP liposome and its regulation of postharvest senescence in Agaricus bisporus - Xin Jiang; Jiali Han; Lei Feng; Jia Wang; Cunkun Chen; Hiroaki Kitazawa; Xiangyou Wang; Yanyin Guo; Ling Li (Food Bioscience, 2024)

Phase inversion of bigels tuned by the concentration of soy protein isolate in the binary hydrogel matrix - Ling-Zhi Su; Ying-Xin Chen; Shi-Qi Zhang; Chun Hu; Jun-Bo He; Wei-Nong Zhang; Li-Juan Han (Food Hydrocolloids, 2024)

Magnesium hexacyanoferrate nanocatalysts alleviates fibromyalgia syndrome by reversing cellular ferroptosis - Ling Jiang; Zhongqiang Zhu; Kun Han; Dongxu Chen; Lu Huang; Na Hu; Jiayi Du; Bowen Zhang; Yi Su; Tao Li; Xiangyi Ren; Xiang He (Chemical Engineering Journal, 2024)

Nanofibrous dressing with drug/electroactivity synergistic effect for wound healing - Jinmiao Chen; Xihui Jia; Shuang Wang; Xueqin Wang; Ling Li; Guangting Han; Yuejie Dou; Jiwei Li (Chemical Engineering Journal, 2024)

Multifunctional pH-responsive hydrogel dressings based on carboxymethyl chitosan: Synthesis, characterization fostering the wound healing - Mingxin Xiong; Yu Chen; Han-Jian Hu; Hao Cheng; Wei-Xiong Li; Shipeng Tang; Xiaolong Hu; Ling-Min Lan; Hongyan Zhang; Gang-Biao Jiang (Carbohydrate Polymers, 2024)

Joint regulation of the soil organic carbon accumulation by mineral protection and microbial properties following conservation practices - Changdong Han; Lin Chen; Zhongjun Jia; Hongtao Zou; Ling Ma; Biao Feng; Jingwang Li; Guixiang Zhou; Congzhi Zhang; Donghao Ma; Jiabao Zhang (CATENA, 2024)

Chemical constituents from Ficus tikoua and chemotaxonomic significance - Han-Lei Wang; Jing Lu; Xue-Lin Chen; Ru Li; Kun Zhang; Yu-Ling Guo; Xia Zhao; Yu-Mei Zhang (Biochemical Systematics and Ecology, 2024)

LncRNA MIR210HG promotes phenotype switching of pulmonary arterial smooth muscle cells through autophagy-dependent ferroptosis pathway - Enze Wang; Binbin Zhang; Ling Huang; Pulin Li; Rui Han; Sijing Zhou; Daxiong Zeng; Ran Wang (Apoptosis, 2024)

Distribution characteristics and ecological risk analysis of microplastics in sediments and effluents related to offshore oil and gas activities in the Bohai Sea, China - Yuxia Li; Lingna Kong; Zhongxiu Li; Qing Su; Ling Qu; Xiaomeng Wang; Jianbo Han; Jiayi Cheng; Liang Wu; Naidong Zhang (Marine Pollution Bulletin, 2024)

The types of metal M and crystal surface in the PtM (M = Co, Ni, Zn) IMCs catalysts to regulate catalytic performance of ethane direct dehydrogenation - Yue Liu; Bing Han; Baojun Wang; Maohong Fan; Lixia Ling; Riguang Zhang (Fuel, 2024)

Subchronic oral toxic effects of 2,4-dinitroaniline in wistar rats: A comprehensive toxicity evaluation - Ling Hu; Xiaoxu Wu; Jinjin Peng; Biao Yan; Jinquan Li; Yongyong Guo; Jian Han (Food and Chemical Toxicology, 2024)

3D macroporous MXene/sodium alginate aerogels with “brick-concrete” structures for highly efficient solar-driven water purification - Yang Zhang; Shuai Wang; Di Han; Hongxuan Chen; Huiquan Liu; Jie Zhu; Wen Luo; Changrui Shi; Yongchen Song; Zheng Ling (Desalination, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

Carbon nanofibers introduce nitroguanidine propulsion to improve mechanical properties, and the study of thermal decomposition, combustion behavior and molecular dynamics - Ling Chen; Anning Sun; Jianwei Zhang; Derong Meng; Peichen Han; Feiyun Chen; Fengqiang Nan; Ping Du; Weidong He (Chemical Engineering Journal, 2024)

Synergistic effect of gellan gum and guar gum on improving the foaming properties of soy protein isolate-based complexes: Interaction mechanism and interfacial behavior - Yameng Han; Ling Zhu; Hui Zhang; Tongtong Liu; Gangcheng Wu (Carbohydrate Polymers, 2024)

The impacts of photochemical loss on the source apportionment of ambient volatile organic compounds: A case study in Northern China - Jingqiao Zhang; Zheng Liu; Yajun Wu; Yao Zhu; Ting Cao; Deyin Ling; Han Wang; Shulan Wang (Atmospheric Environment, 2024)

Early-onset and later-onset cancer: trends, risk factors, and prevention in Northern China - Tong Liu; Chen-An Liu; Qing-Song Zhang; Qi Zhang; Yi-Ming Wang; Meng-Meng Song; Shi-Qi Lin; Li Deng; Shou-Ling Wu; Han-Ping Shi (Science China Life Sciences, 2024)

The characteristics of nutrient distribution and influencing factors in the Chukchi Plateau and adjacent waters - Zhixin Ni; Han Zhang; Minxia Zhang; Tuanjie Li; Shengyong Li; Xin Chen; Ling Zhang; Yuan Gao; Changshu Chen; Zhongyuan Wang; Wei Deng; Hai zhou Zhang (Frontiers in Marine Science, 2024)
The Arctic is one of the regions under the most dramatic climate change. Global warming has led to elevated freshwater inflow into the western Arctic Ocean and significantly altered nutrient structure and biogeochemical cycling. In this work, inorganic dissolved nutrients in the Chukchi Plateau (CP) and adjacent regions were investigated to further understand their characteristics and influencing factors. Results showed that relatively high nutrient concentrations occurred in the water masses with salinity >32 psu, especially there was a nutrient-rich layer influenced by Winter Pacific Water in the water column (15.10±1.96, 2.23±0.26, and 23.46±6.64 µmol/L for DIN, PO 4 3– and Si(OH) 4 , respectively). Contrarily, lower nutrient concentrations occurred in the mixing water of the upper layer (1.76±1.04, 1.15±0.16 and 3.76±2.29 µmol/L for DIN, PO 4 3– and Si(OH) 4 , respectively) with a low DIN/P ratio (1.44±0.59), suggesting DIN has become the potentially biological limiting factor. Furthermore, the freshening and deepening of the upper layer driven by the Beaufort Gyre has hindered the nutrient transport from underlying layer into the upper layer. A maximum chla was observed at 36‒75 m water depth, and the phytoplankton biomass decreased from the western to the eastern CP, accompanied by a decreased contribution of micro-sized chla but an increased contribution of small-sized chla (74.0±0.1%). The phytoplankton resource use efficiency for DIN was estimated as (3.2±4.6)×10 -3 , which was primarily influenced by the physicochemical parameters of water and also largely regulated by the size structure of phytoplankton.

Study on seismic response of liquefiable soil-pile group considering pile cap and soil contact - Zhang Xiao-ling; Lan Hao; Xu Cheng-shun; Han Yan (Soil Dynamics and Earthquake Engineering, 2024)

The synergistic effect of high temperature and relative humidity on non-accidental deaths at different urbanization levels - Yaqin Bu; Zhaobin Sun; Yan Tao; Xiuge Zhao; Yuxin Zhao; Yinglin Liang; Xiaoyi Hang; Ling Han (Science of The Total Environment, 2024)

Prenatal and postnatal early life exposure to greenness and particulate matter of different size fractions in relation to childhood rhinitis - A multi-center study in China - Liu Yang; Han Chen; Huiyu Gao; Ying Wang; Tianyi Chen; Magnus Svartengren; Dan Norbäck; Jing Wei; Xiaohong Zheng; Ling Zhang; Chan Lu; Wei Yu; et al. (Science of The Total Environment, 2024)

Construction of ecological security pattern in combination with landslide sensitivity: A case study of Yan’an City, China - Bolin Li; Ling Han; Liangzhi Li (Journal of Environmental Management, 2024)

Experimental and modelling study on the laminar burning velocity correlation of CH4 flames diluted by different diluents - Xinlu Han; Zhongqian Ling; Guangxue Zhang; Dingkun Yuan; Jiangrong Xu (Fuel, 2024)

Mining for QTL controlling maize low-phosphorus response genes combined with deep resequencing of RIL parental genomes and in silico GWAS analysis - Bowen Luo; Peng Ma; Chong Zhang; Xiao Zhang; Jing Li; Junchi Ma; Zheng Han; Shuhao Zhang; Ting Yu; Guidi Zhang; Hongkai Zhang; Haiying Zhang; et al. (Theoretical and Applied Genetics, 2024)

Effects of selenium application with different combinations of secondary elements on ‘Qingcui’ plum leaf nutrition and fruit quality - Xieping Sun; Shaobing Gao; Min Ling; Junyan Wang; Xinyue Zhao; Guoqiang Han (Plant and Soil, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Preparation of (S)-epichlorohydrin using a novel halohydrin dehalogenase by selective conformation adjustment - Xiao-Jian Zhang; Meng-Yu Huang; Xin-Xin Peng; Min Cao; Han-Zhong Deng; Yi-Chuan Gong; Xiao-Ling Tang; Zhi-Qiang Liu; Yu-Guo Zheng (Biotechnology Letters, 2024)

A dried sweat spot paper (DSSP) method based on novel mass spectrometry probe labeling for detection and resolution of DL-lactate enantiomers as potential biomarkers for diabetes mellitus - Yueying Jin; Minghui Zhang; Xi-Ling Li; Chengqiang Han; Qing Shi; Jun Zhe Min (Analytica Chimica Acta, 2024)

Fermentation of Polygonati Rhizoma aqueous extract using Lactiplantibacillus plantarum under the condition of eutrophication - Zi-Ling Wang; Jia Lao; Zhen-Ni Xie; Wei He; Can Zhong; Shui-Han Zhang; Jian Jin (Archives of Microbiology, 2024)

Regulating microbial redox reactions towards enhanced removal of refractory organic nitrogen from wastewater - Ke Shi; Bin Liang; Hao-Yi Cheng; Hong-Cheng Wang; Wen-Zong Liu; Zhi-Ling Li; Jing-Long Han; Shu-Hong Gao; Ai-Jie Wang (Water Research, 2024)

Five coexisting brominated flame retardants in a water-sediment-Vallisneria system: Bioaccumulation and effects on oxidative stress and photosynthesis - Mengru Fu; Zhihua Qiao; Shanqi Zhou; Yanna Han; Siyuan Ling; Cheng Peng; Wei Zhang; Jinhong Wu (Science of The Total Environment, 2024)

Structurally diverse isoquinoline alkaloids from the barks of Alangium salviifolium (L. f.) Wangerin and their cytotoxicity - Yan-Mei Wei; Xuan Zhang; Fu-Ling Cen; Yi-Yi Du; Yuan-Ling Liu; Qiao-Yuan Han; Zhang-Xin Yu; Guang-Ying Chen (Phytochemistry, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

Elucidation of the beneficial role of co-fermented whole grain quinoa and black barley with Lactobacillus on rats fed a western-style diet via a multi-omics approach - Zi-Han Lin; Ling-Yue Zhong; Hui-Bin Jiang; Chuang Zhu; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Research International, 2024)

Sustained release of a novel bilayer packaging film loaded with binary microemulsion of melatonin/pummelo essential oil and its regulation of postharvest energy metabolism in Agaricus bisporus - Lei Feng; Na Zhang; Jia Wang; Xin Jiang; Jiali Han; Ling Li; Hiroaki Kitazawa; Xiangyou Wang; Cunkun Chen; Yanyin Guo (Food Control, 2024)

Diverse bacterial hosts and potential risk of antibiotic resistomes in ship ballast water revealed by metagenomic binning - Baoyi Lv; Changhai Jiang; Yangchun Han; Dong Wu; Ling Jin; Guorong Zhu; Tingxuan An; Jianhong Shi (Environmental Research, 2024)

Exploring the phosphorus–starch content balance mechanisms in maize grains using GWAS population and transcriptome data - Bowen Luo; Haiying Zhang; Zheng Han; Xiao Zhang; Jianyong Guo; Shuhao Zhang; Xianfu Luo; Jin Zhao; Wei Wang; Guohui Yang; Chong Zhang; Jing Li; et al. (Theoretical and Applied Genetics, 2024)

Adaptation of a prey population to increasing predation risks - Ling Pan; Han Zhu; Yan Wang; Bao-Chun Shi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen; Yi-Long Xi (Hydrobiologia, 2024)

Two new anti-inflammatory compounds from the roots and rhizomes of Clematis terniflora var . manshurica (Rupr.) Ohwi - Ping Shao; Sheng Dong; Lin-Tong Mu; Ling Han; Chong-Ning Lv; Jiu-Zhi Yuan; Jin-Cai Lu (Natural Product Research, 2024)

The effects of interaction with audiovisual elements on perceived restoration in urban parks in freezing weather - Ruining Zhang; Ling Zhu; Xinhao Yang; Rumei Han; Yuan Zhang; Jian Kang (Urban Forestry & Urban Greening, 2024)

In vivo study on osteogenic efficiency of nHA/ gel porous scaffold with nacre water-soluble matrix - SiRi-GuLeng Li; Zhu-Ling Guo; Si-Yu Tao; Tao Han; Jie Zhou; Wan-Yun Lin; Xiang Guo; Chu-Xing Li; Sunchuri Diwas; Xiao-Wen Hu (Tissue and Cell, 2024)

Exposure to volatile organic compounds and mortality in US adults: A population-based prospective cohort study - Xiaobing Feng; Feng Qiu; Ling Zheng; Yue Zhang; Yuji Wang; Min Wang; Han Xia; Bingrong Tang; Chunxiang Yan; Ruyi Liang (Science of The Total Environment, 2024)

Phthalate and DINCH exposure and ovarian reserve markers among women seeking infertility care - Yangqian Jiang; Yiqun Xu; Shuxin Xiao; Xianxian Zhu; Hong Lv; Lu Zang; Shuifang Lei; Xin Xu; Bo Xu; Xiumei Han; Jin Zhu; Jiangbo Du; et al. (Science of The Total Environment, 2024)

Two new steroids with cytotoxicities from fungus Acrocalymma cycadis - Li-Bin Lin; Deng-Gao Zhu; Ting Yang; Rui Han; Jia-Yao Hu; Wei Shi; Ze-Yi Li; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Two new lignans from the fresh roots of Zhongsheng No.1 Rehmannia glutinosa - Xiang-Da Li; Yan-Gang Cao; Yu-Han Zhang; Ying-Jie Ren; Meng-Nan Zeng; Yan-Ling Liu; Xu Chen; Xin-Yi Ma; Bing-Xian Zhao; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2024)

Thermodynamic and exergy assessment of a biomass oxy-fuel combustion with supercritical carbon dioxide cycle under various recycle flue gas conditions - Jester Lih Jie Ling; Han Saem Park; Ha Eun Lee; Bhanupratap S. Solanki; See Hoon Lee (Journal of Cleaner Production, 2024)

Distribution and influencing factors of Mycobacterium in rail transit based on metagenomic analysis - Yongping Liu; Ling Tong; Shaofeng Sui; Yewen Shi; Fengchan Han; Jianghua Zhang (Journal of Aerosol Science, 2024)

Elucidating the action mechanism of different kinds of oxygen species on methane dissociation to generate methyl radical on lanthanum oxide catalyst - Neng Shi; Ye Liu; Bingying Han; Yurong Liu; Riguang Zhang; Lixia Ling; Pengyu Niu; Litao Jia; Baojun Wang (Fuel, 2024)

Extending the freshness of tilapia surimi with pulsed electric field modified pea protein isolate-EGCG complex - Zhong Han; Ze-Ling Chen; Xin-Dong Xu; Songyi Lin; Yan Wang; Lang-Hong Wang; De-Bao Niu; Xin-An Zeng; Meng-Wai Woo; Ruo-Yong Wang (Food Hydrocolloids, 2024)

Fabrication of soy protein microgels via two top-down methods and characterization of the foaming behavior - Yameng Han; Ling Zhu; Hui Zhang; Tongtong Liu; Gangcheng Wu (Food Bioscience, 2024)

Greenness and its composition and configuration in association with allergic rhinitis in preschool children - Han Chen; Xia Meng; Yongfu Yu; Jin Sun; Zhiping Niu; Jing Wei; Ling Zhang; Chan Lu; Wei Yu; Tingting Wang; Xiaohong Zheng; Dan Norbäck; et al. (Environmental Research, 2024)

Modulations of ocean-atmosphere interactions on squid abundance over Southwest Atlantic - Chia-Ying Ko; Yu-Chi Lee; Yi-Chi Wang; Huang-Hsiung Hsu; Chun Hoe Chow; Ruei-Gu Chen; Tsung-Han Liu; Chih-Shin Chen; Tai-Sheng Chiu; Don-Hsieh Chiang; Ren-Fen Wu; Wan-Ling Tseng (Environmental Research, 2024)

Mechanism of stable autotrophic nitrogen removal and NOB inhibition in low-sludge PN-Anammox system under non-temperature control and low ammonia environment - Pei-ling Xu; Xiang Li; Yayi Wang; Yan Yuan; Han Wang; Yong Huang; Jun Ma; Miao Shi (Chemical Engineering Journal, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Cardiovascular adverse effects and mechanistic insights of arsenic exposure: a review - Yán Wāng; Ling Ma; Chunzhi Wang; Tiantian Gao; Yapeng Han; De-Xiang Xu (Environmental Chemistry Letters, 2024)

Air permeability variation of compacted loess: effects of soil basic properties and dry-wet cycles - Shi-Feng Lu; Xiao-Pei Guo; Xing-Rui Wang; Zi-Jing Han; Ling Xu; Xiao-Lin Huang; Lu Zuo (Bulletin of Engineering Geology and the Environment, 2024)

Numerical simulation investigation on the seismic performance of high-strength concrete columns reinforced with PVA fibers and HTRB630 steel bars - Mei-Ling Zhuang; Chuanzhi Sun; Jinbo Chen; Hanbo Zhu; Li Gao; Yan Qiao; Yuefeng Shao; Weihua Zhang; Yixiang Han; Guangdong Bao (Bulletin of Earthquake Engineering, 2024)

circ_0000337 Promotes the Progression of Cervical Cancer by miR-155-5p/RAB3B Axis - Jiqin Xu; Bai Xue; Min Gong; Ling Ling; Sipei Nie; Fujun Li; Meixia Wang; Miao Fang; Chen Chen; Qiaoling Liu; Yun Han (Biochemical Genetics, 2024)

Feasible use of ureolytic bacteria in lightweight foamed concrete to enhance its strength - Siong Kang Lim; Cher Siang Tan; Yee Ling Lee; Ming Han Lim; Ming Kun Yew (European Journal of Environmental and Civil Engineering, 2024)

Combined exposure to decabromodiphenyl ether and nano zero-valent iron aggravated oxidative stress and interfered with metabolism in earthworms - Ying Han; Siyuan Ling; Shuangqing Hu; Genxiang Shen; Hongchang Zhang; Wei Zhang (Science of The Total Environment, 2024)

Neural network establishes co-occurrence links between transformation products of the contaminant and the soil microbiome - Yuhui Xiang; Yansong Yu; Jiahui Wang; Weiwei Li; Yu Rong; Haibo Ling; Zhongbing Chen; Yiguang Qian; Xiaole Han; Jie Sun; Yuyi Yang; Liang Chen; et al. (Science of The Total Environment, 2024)

TemPanSharpening: A multi-temporal Pansharpening solution based on deep learning and edge extraction - Yifei Han; Hong Chi; Jinliang Huang; Xinyi Gao; Zhiyu Zhang; Feng Ling (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Revealing the variances in color formation and bioactivities of seven catechin monomers throughout the enzymatic reaction by colorimetric and mass spectrometry - Wei Hu; Mingchun Wen; Zisheng Han; Xue-Ling Gao; Jia-Ping Ke; Mengting Zhu; Xinlin Wei; Yong Cheng; Xiaochun Wan; Yundong Shao; Liang Zhang (Food Research International, 2024)

Fermented lily bulbs by “Jiangshui” probiotics improves lung health in mice - Aman Khan; Weidong Wang; Jing Ji; Zhenmin Ling; Pu Liu; Sa Xiao; Huawen Han; El-Sayed Salama; Samir Kumar Khanal; Xiangkai Li (Food Chemistry, 2024)

Decoding the aroma characteristics of icewine by partial least-squares regression, aroma reconstitution, and omission studies - Xu Qian; Mengqi Ling; Yanfeng Sun; Fuliang Han; Ying Shi; Changqing Duan; Yibin Lan (Food Chemistry, 2024)

Characteristic of the interaction mechanism between soy protein isolate and functional polysaccharide with different charge characteristics and exploration of the foaming properties - Yameng Han; Ling Zhu; Hui Zhang; Tongtong Liu; Gangcheng Wu (Food Hydrocolloids, 2024)

A novel integrated microbial fuel cell-membrane bioreactor (MFC-MBR) for controlling the spread of antibiotic and antibiotic resistance genes while simultaneously alleviating membrane fouling - Ling Zang; Xiao-Li Yang; Han Xu; Yang-Guang Xia; Hai-Liang Song (Chemical Engineering Journal, 2024)

An electro-ferroptotic nanoammunition enables image-guided, spatiotemporally controlled cancer ferroptosis induction via irreversible electroporation - Jun-Hyeok Han; Hee Seung Seo; Jiyoung Lee; Zheng Chen; Qiyue Wang; Yun Young Lee; Na Kyeong Lee; Jeon Min Kang; Song Hee Kim; Hwichan Hong; Jung-Hoon Park; Yuanzhe Piao; et al. (Chemical Engineering Journal, 2024)

Microbial mechanisms involved in negative effects of amoxicillin and copper on humification during composting of dairy cattle manure - Ya Su; Ling Zhou; Qianting Zhuo; Chen Fang; Jia You; Lujia Han; Guangqun Huang (Bioresource Technology, 2024)

Bud development, flower phenology and life history of holoparasitic Rafflesia cantleyi - Suk Ling Wee; Shwu Bing Tan; Sue Han Tan; Bernard Kok Bang Lee (Journal of Plant Research, 2024)
Despite being the world's largest single-flower, Rafflesia ’s biology and life history are still poorly understood due to its cryptic growth strategy on Tetrastigma vines. Previous studies have been mostly short-term, contrary to Rafflesia ’s long development period before blooming. Bud development and flower phenology of R. cantleyi was studied in a dipterocarp forest in Lata Jarum, Peninsular Malaysia. Seven populations, consisting of 247 buds, were monitored fortnightly for 65 months in two discrete studies between 2009 and 2018. The bud size distribution of R. cantleyi is dynamic, progressively changing from small flower buds to larger buds before flowering. Buds < 5.0 cm across had the slowest growth and highest mortality rates, while those > 15.0 cm across demonstrated accelerated growth. The bud growth profiles of the same site clustered distinctively regardless of sex with successful blooming rate that varied greatly between sites, prompting speculation about their relatedness to the sites’ physical attributes. We reported the first female-dominated population in Rafflesia ’s life history. Rafflesia cantleyi ’s blooming rate at Lata Jarum is moderate to high, with non-seasonal flowering phenology as evident by the lack of synchronisation and consistency between flowering and local rainfall patterns. Based on the field data of the present study and the published information of other Rafflesia species, R. cantleyi’s life cycle was estimated between 4.0 and 5.3 years. Our findings further explain Rafflesia ’s biology and life history and highlight the gap in knowledge of the natural habitats on the endoparasite’s growth and fate potentially for future conservation and study.

Spatial distribution characteristics of soil liquefaction potential in the Yellow River Subaquatic Delta, China - Xipeng Qin; Zhongnian Yang; Yuxue Cui; Xuesen Liu; Han Tian; Lei Guo; Xianzhang Ling (Marine Georesources & Geotechnology, 2024)

Evolutionary multimodal multiobjective optimization guided by growing neural gas - Yiping Liu; Ling Zhang; Xiangxiang Zeng; Yuyan Han (Swarm and Evolutionary Computation, 2024)

Transcriptomic analysis and knockout experiments reveal the role of suhB in the biocontrol effects of Pantoea jilinensis D25 on Botrytis cinerea - Lining Zheng; Zhe Han; Shengyi Wang; Ao Gao; Ling Liu; Hongyu Pan; Hao Zhang (Science of The Total Environment, 2024)

Isolation and characterization of seven neovibsane-type diterpenoids from Viburnum odoratissimum and their neuroblastoma cell protective effects - Jin-Ling Han; Tian-Ming Lv; Jia-Qi Niu; Jin-Le Hao; Guo-Dong Yao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Study on the remediation of uranium-contaminated soils by compound leaching: Screening of leaching agents and a pilot-scale application - Juncheng Han; Jing Zou; Xindai Li; Aizhong Ding; Zhaorong Shang; Hongtu Sun; Ling Chen; Zhiyuan He; Qiao Li; Hongbo Fan; Junfeng Dou (Journal of Cleaner Production, 2024)

Identification of dynamic changes in volatile compounds and metabolites during the smoking process of Zhenba bacon by GC-IMS combined metabolomics - Shuai Han; Meiling Ke; Ling Wang; Haidong Ma; Guofei Wu; Lianxu Zhu; Tao Zhang; Hongzhao Lu (Food Research International, 2024)

The polyphenols profile of co-fermented quinoa and black barley with Lactobacillus kisonensis and its in vitro bioactivities - Hui-Bin Jiang; Pan Nie; Zi-Han Lin; Chuang Zhu; Ling-Yue Zhong; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Bioscience, 2024)

Dual effect of organic/inorganic artificial protective layer to construct high-performance zinc metal anode - Yingxiao Du; Ruotong Li; Tingting Wang; Ziyi Feng; Han Dong; Fangfang Fan; Dezhao Deng; Jing Zhu; Yongguang Liu; Lei Dai; Ling Wang; Zhangxing He (Chemical Engineering Journal, 2024)

Quaternary integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Yong Wang; Mianping Zheng; Yuan Ling; Shuyuan Xiang; Zhaogang Shao; Kexin Zhang; Xue Ke; Xiao Lin; Fang Han; Jian’en Han (Science China Earth Sciences, 2024)

Characterization of the MIKCC-type MADS-box gene family in blueberry and its possible mechanism for regulating flowering in response to the chilling requirement - Sui-Lin Zhang; Yan Wu; Xiao-Han Zhang; Xin Feng; Hui-Ling Wu; Bing-Jie Zhou; Ya-Qian Zhang; Man Cao; Zhi-Xia Hou (Planta, 2024)

Nrf2-mediated ferroptosis of spermatogenic cells involved in male reproductive toxicity induced by polystyrene nanoplastics in mice - Xufeng Fu; Hang Han; Hong Yang; Bo Xu; Wenjie Dai; Ling Liu; Tiantian He; Xing Du; Xiuying Pei (Journal of Zhejiang University-SCIENCE B, 2024)

GRMPose: GCN-based real-time dairy goat pose estimation - Ling Chen; Lianyue Zhang; Jinglei Tang; Chao Tang; Rui An; Ruizi Han; Yiyang Zhang (Computers and Electronics in Agriculture, 2024)

Wheat straw biochar as an additive in swine manure Composting: An in-depth analysis of mixed material particle characteristics and interface interactions - Xueqin He; Zhihao Peng; Yuxiong Zhu; Yufeng Chen; Yuanping Huang; Jingpeng Xiong; Chen Fang; Shurong Du; Long Wang; Ling Zhou; Guangqun Huang; Lujia Han (Waste Management, 2024)

Hydrogeochemical and isotopic evidences of the underlying produced water intrusion into shallow groundwater in an oil production area, Northwest China - Hongyu Zhang; Xu Han; Guangcai Wang; Ling Zhou; Dandan Huang; Xianglong Chen; Fan Zhang (Science of The Total Environment, 2024)

Long-term conservation tillage enhances microbial carbon use efficiency by altering multitrophic interactions in soil - Ling Ma; Guixiang Zhou; Jiabao Zhang; Zhongjun Jia; Hongtao Zou; Lin Chen; Congzhi Zhang; Donghao Ma; Changdong Han; Yan Duan (Science of The Total Environment, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

A comprehensive evaluation of milk protein molecular weight distribution based on exclusion chromatography dataset - Yu Liu; Xiao-Yan Li; Ling Li; Yu-Qi Yin; Han-Lin Zhang; Kun-Long Wang; Jie Zhou; Yun Chen; Ying-Hua Zhang (Food Chemistry, 2024)

High pressure-assisted enzymatic hydrolysis promotes the release of a bi-functional peptide from cowhide gelatin with dipeptidyl peptidase IV (DPP-IV) inhibitory and antioxidant activities - Long He; Ling Han; Qunli Yu; Xinyue Wang; Ying Li; Guangxing Han (Food Chemistry, 2024)

Fine mapping of a major QTL, qKl-1BL controlling kernel length in common wheat - Ran Qin; Mingsu Cao; Jizi Dong; Linqu Chen; Haoru Guo; Qingjie Guo; Yibiao Cai; Lei Han; Zhenjie Huang; Ninghao Xu; Aoyu Yang; Huiyuan Xu; et al. (Theoretical and Applied Genetics, 2024)

Hessian Regularized $$L_{2,1}$$-Nonnegative Matrix Factorization and Deep Learning for miRNA–Disease Associations Prediction - Guo-Sheng Han; Qi Gao; Ling-Zhi Peng; Jing Tang (Interdisciplinary Sciences: Computational Life Sciences, 2024)

A novel 193-plex MPS panel integrating STRs and SNPs highlights the application value of forensic genetics in individual identification and paternity testing - Xueyuan Liu; Chengliang Yang; Xiaohui Chen; Xiaolong Han; Hong Liu; Xingkun Zhang; Quyi Xu; Xingyi Yang; Changhui Liu; Ling Chen; Chao Liu (Human Genetics, 2024)

Microfluidic platform for omics analysis on single cells with diverse morphology and size: A review - Shujin Lin; Dan Feng; Xiao Han; Ling Li; Yao Lin; Haibing Gao (Analytica Chimica Acta, 2024)

Identification and Characterization of Entamoeba histolytica Choline Kinase - Chiat Han Chang; Wei Cun See Too; Boon Huat Lim; Ling Ling Few (Acta Parasitologica, 2024)

Advancements and hurdles of deeper‐offshore aquaculture in China - Shuang‐Lin Dong; Yun‐Wei Dong; Liu‐Yi Huang; Yan‐Gen Zhou; Ling Cao; Xiang‐Li Tian; Li‐Min Han; Da‐Hai Li (Reviews in Aquaculture, 2024)
Open offshore areas boast strong physical self‐purification capacity and abundant non‐fossil energy resources, such as wind, waves, and solar energy. Consequently, the global community anticipates nearshore aquaculture to transition towards offshore to help increase production, alleviate eutrophication, and reduce greenhouse gas emissions. To date, China has constructed over 40 sets of deeper‐offshore aquaculture (DOA) infrastructures, encompassing various types of pens, cages and closed containment systems. Although DOA holds vast potential to address food security and aquaculture sustainability in China, its current development trajectory struggles to meet those goals and primarily achieves profitability by focusing on high‐value species or products. For DOA to realize its potential, innovative production systems must tackle three key contradictions: enterprise profitability versus product affordability, clean energy‐based products versus carbon‐intensive products, and automated operation versus re‐employment of coastal fish farmers. Resolving these contradictions requires the development of a large‐scale, anti‐typhoon offshore enclosure that integrates mariculture with other industries, such as wind farming, food processing, and tourism. This approach will foster a sustainable balance between profitability, environmental impact, and employment opportunities in the sector.

TPN10475 Constrains Effector T Lymphocytes Activation and Attenuates Experimental Autoimmune Encephalomyelitis Pathogenesis by Facilitating TGF-β Signal Transduction - Chun Wang; Xiangrui Jiang; Jie Lv; Wei Zhuang; Ling Xie; Guangyu Liu; Kaidireya Saimaier; Sanxing Han; Changjie Shi; Qiuhong Hua; Ru Zhang; Changsheng Du (Journal of Neuroimmune Pharmacology, 2024)

Analysis of environmental biological effects and OBT accumulation potential of microalgae in freshwater systems exposed to tritium pollution - Jin-long Lai; Zhan-guo Li; Meng-wei Han; Yan Huang; Hai-ling Xi; Xue-gang Luo (Water Research, 2024)

GAS5 promotes cytarabine induced myelosuppression via inhibition of hematopoietic stem cell differentiation - Yin-Xiao Du; Jing Yang; Han Yan; Yan-Ling Liu; Xiao-Ping Chen (Toxicology and Applied Pharmacology, 2024)

Heterogeneity analysis of main driving factors affecting potential evapotranspiration changes across different climate regions - Wenhui Liu; Baozhong Zhang; Zheng Wei; Yaqi Wang; Ling Tong; Jingyang Guo; Xin Han; Congying Han (Science of The Total Environment, 2024)

AaABCG20 transporter involved in cutin and wax secretion affects the initiation and development of glandular trichomes in Artemisia annua - Xueqing Fu; Han Zheng; Yuting Wang; Hang Liu; Pin Liu; Ling Li; Jingya Zhao; Xiaofen Sun; Kexuan Tang (Plant Science, 2024)

Synergistic catalysis induced by a multicomponent system constructed with combined DBD plasma, g-C3N4/FOD and persulfate for trichloroethylene removal - Wei Gao; Xiaoying Xu; Xueqi Han; Ling Zhang; Haitao Ding; Chengxun Deng (Journal of Water Process Engineering, 2024)

Preparation of homogeneous LiF-BeF2-ZrF4 molten salt with low oxygen content - Yulong Song; Miao Shen; Jing Yang; Ling Han; Rui Tang; Sufang Zhao; Yuan Qian (Journal of Fluorine Chemistry, 2024)

A high-efficient protoplast transient system for screening gene editing elements in Salvia miltiorrhiza - Jin Shao; Bowen Peng; Yaojie Zhang; Xin Yan; Xinghao Yao; Xinyi Hu; Ling Li; Xueqing Fu; Han Zheng; Kexuan Tang (Plant Cell Reports, 2024)

Lithium-rich claystone in Pingguo area, Guangxi, southwest China: precursor kaolinite controls lithium enrichment - Kunyue Ling; Hanjie Wen; Tao Han; Zhitong Lu; Yi Cui; Chongguang Luo; Wenbin Yu (Mineralium Deposita, 2024)

Blockade of ZFX Alleviates Hypoxia-Induced Pulmonary Vascular Remodeling by Regulating the YAP Signaling - Ling Tang; Xiao Zhou; Aili Guo; Lizhang Han; Silin Pan (Cardiovascular Toxicology, 2024)

Long-term fertilization affects microbial necromass accumulation by regulating nutrient and enzymatic stoichiometry in a calcareous Fluvisol - Changdong Han; Lin Chen; Xiuli Xin; Guixiang Zhou; Congzhi Zhang; Donghao Ma; Yue Li; Ling Ma; Jiabao Zhang (Applied Soil Ecology, 2024)

Laccase-evoked removal of antibiotics: Reaction kinetics, conversion mechanisms, and ecotoxicity assessment - Kai Sun; Mei-Hua Chen; Xue-Min Qi; Dan Hong; Ling-Zhi Dai; Shun-Yao Li; Yi-Chen Lu; Han-Qing Yu (Critical Reviews in Environmental Science and Technology, 2024)

Re-evaluating the impact and mechanism of digital economy on regional pollution intensity from the perspective of spatial spillover - Pei-Ling Yang; Zi-Han Lin; Zhen-Ning Zhu; Feng-Wei Ying (Environmental Science and Pollution Research, 2024)

Overall integrated navigation based on satellite and lidar in the standardized tall spindle apple orchards - Weihong Liu; Wenwei Li; Han Feng; Jiawei Xu; Shenghui Yang; Yongjun Zheng; Xingxing Liu; Zimeng Wang; Xiaokang Yi; Yichuan He; Ling Zhou (Computers and Electronics in Agriculture, 2024)

Dietary supplementation of patchouli oil improves resistance to Streptococcus agalactiae infection in genetically improved cultured Tilapia (GIFT, Oreochromis niloticus.) as revealed by RNA-Seq - Yin Yi Yao; Zong Xian Zhu; Chun Hui Ai; Xue Ying Liang; Gan Yang; Tong De Liu; Hong Yi Zhang; Han Jing Yan; Jun Hong Xia; Meng Ling He (Aquaculture, 2024)

Quercetin as a major component of Punica granatum L. effectively controls WSSV infection and transmission in the larval shrimp culture stage - Xu Zhang; Ling Hu; Yang Hu; Han-Wei Liu; Lei Liu; Jiong Chen (Aquaculture, 2024)

Combined effects of crowding stress and low salinity on GH/IGF axis, antioxidant response, and HPI axis in largemouth bass (Micropterus salmoides) larvae - Jia-Lang Zheng; Hai-Ting Zhang; Lu Gao; Xiao Chen; Qing-Ling Zhu; Tao Han (Aquaculture, 2024)

LED light spectra differently affected growth, antioxidant capacity, stress response, GH/IGF and HPI axis in largemouth bass (Micropterus salmoides) larvae - Jia-Lang Zheng; Lu Gao; Hai-Ting Zhang; Xiao Chen; Qing-Ling Zhu; Tao Han (Aquaculture, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Mixing uniformity effect on leaching behaviour of cement-based solidified contaminated clay - Tingting Deng; Marsheal Fisonga; Han Ke; Ling Li; Jianwei Wang; Yongfeng Deng (Science of The Total Environment, 2024)

Mxenes for membrane separation: from fabrication strategies to advanced applications - Zhengyi Huang; Die Ling Zhao; Liguo Shen; Hongjun Lin; Cheng Chen; Yanchao Xu; Bisheng Li; Jiaheng Teng; Lei Han; Tai-Shung Chung (Science Bulletin, 2024)

Self-assembled Fe3O4-NH2 @g-C3N4 composite for magnetic solid-phase extraction of benzophenones in sea water and lake water coupled with LC-MS/MS determination - Man-Man Wang; Zi-Ling Li; Han Wu; Ke-Yan Chen; Fan Guo; Gui-Fu Zuo; Yu He; Xue-Bo Yin (Journal of Hazardous Materials, 2024)

Heat exposure assessment based on high-resolution spatio-temporal data of population dynamics and temperature variations - Zhaobin Sun; Xiaoling Zhang; Ziming Li; Yinglin Liang; Xingqin An; Yuxin Zhao; Shiguang Miao; Ling Han; Demin Li (Journal of Environmental Management, 2024)

Waste separation behavior with a new plastic category for the plastic resource circulation: Survey in Kansai, Japan - Jiarong Hu; Ling Miao; Ji Han; Weisheng Zhou; Xuepeng Qian (Journal of Environmental Management, 2024)

RETRACTED: Ancient forest plants possess cytotoxic properties causing liver cancer HepG2 cell apoptosis - Xiaochen Yue; Nyuk Ling Ma; Jiateng Zhong; Han Yang; Huiling Chen; Yafeng Yang; Su Shiung Lam; Lijun Yan; Bjarne Styrishave; Tomasz Maciej Ciesielski; Wan-Xi Peng; Christian Sonne (Environmental Research, 2024)

Red blood cell membrane biomimetic nanoprobes for ratiometric imaging of reactive oxygen species level in atherosclerosis - Bo Liu; Gui-Mei Han; Dong-Xia Wang; Ding-Bin Liu; An-An Liu; Jing Wang; Yu-Ling Xiao; Lin Yuan; De-Ming Kong (Chemical Engineering Journal, 2024)

Unique bi-continuous phase structure can facilitate the development of fire-resistant surface - Han Zhang; Ling Zhang; Zhen Zhang; Tingting Chen; Jun Zhang; Shaida S. Rumi; Noureddine Abidi (Chemical Engineering Journal, 2024)

Applying the projection pursuit and DPSIR model for evaluation of ecological carrying capacity in Inner Mongolia Autonomous Region, China - Bai Zongfan; Han Ling; Liu Huiqun; Li Liangzhi; Jiang Xuhai (Environmental Science and Pollution Research, 2023)

Progress in phytoremediation of chromium from the environment - Lingzhuo Han; Haiping Gu; Wenjie Lu; Hanyin Li; Wan-xi Peng; Nyuk Ling Ma; Su Shiung Lam; Christian Sonne (Chemosphere, 2023)

A many-objective optimization evolutionary algorithm based on hyper-dominance degree - Zhe Liu; Fei Han; Qinghua Ling; Henry Han; Jing Jiang (Swarm and Evolutionary Computation, 2023)

Study on seismic response difference of horizontal and inclined liquefied site-pile-structure - Xiao-ling Zhang; Li-jing Fang; Yan Han (Soil Dynamics and Earthquake Engineering, 2023)

Gut microbes consume host energy and reciprocally provide beneficial factors to sustain a symbiotic relationship with the host - Ying Wu; Liang Peng; Pengya Feng; Rong Han; Aman Khan; Sourabh Kulshreshtha; Zhenmin Ling; Pu Liu; Xiangkai Li (Science of The Total Environment, 2023)

Modeling of secondary organic aerosols (SOA) based on two commonly used air quality models in China: Consistent S/IVOCs contribution but large differences in SOA aging - Ling Huang; Hanqing Liu; Greg Yarwood; Gary Wilson; Jun Tao; Zhiwei Han; Dongsheng Ji; Yangjun Wang; Li Li (Science of The Total Environment, 2023)

Past and projected future patterns of fractional vegetation coverage in China - Zijie Kong; Hongbo Ling; Mingjiang Deng; Feifei Han; Junjie Yan; Xiaoya Deng; Zikang Wang; Yuanzhi Ma; Wenqi Wang (Science of The Total Environment, 2023)

Recycled waste masks as oil absorbent based on stable SiO2 coating for efficient separation of oil-water mixtures and oil-in-water emulsions - Lianchao Ning; Yi Liu; Shuang Man; Yaxin Han; Longfei Zhang; Honglei Ling; Ming Zhang (Journal of Water Process Engineering, 2023)

Properties of an active film based on glutenin/tamarind gum and loaded with binary microemulsion of melatonin/pummelo essential oil and its preservation for Agaricus bisporus - Lei Feng; Xin Jiang; Jiali Han; Ling Li; Hiroaki Kitazawa; Xiangyou Wang; Yanyin Guo; Xinru Dong; Haipeng Liu (Food Chemistry, 2023)

An integrated mycotoxin-mitigating agent can effectively mitigate the combined toxicity of AFB1, DON and OTA on the production performance, liver and oviduct health in broiler breeder hens - Meng-Ling Ruan; Jie Wang; Zhi-Yuan Xia; Xue-Wu Li; Bo Zhang; Guan-Lin Wang; Yuan-Yuan Wu; Yanming Han; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Corrigendum to “Effects of pollen concentration on allergic rhinitis in children: A retrospective study from Beijing, a Chinese megacity” [Environ. Res. 229(2023) 115903/ER-22-11024] - Yuxin Zhao; Zhaobin Sun; Li Xiang; Xingqin An; Xiaoling Hou; Jing Shang; Ling Han; Caihua Ye (Environmental Research, 2023)

An ontology-based framework for semantic geographic information systems development and understanding - Chiao-Ling Kuo; Han-Chuan Chou (Computers & Geosciences, 2023)

Economic values of reproductive and growth traits in Chinese Yiling sheep - Jihua Li; Guiqiong Liu; Xunping Jiang; Yumeng Shen; Ling Sun; Yan Chen; Xu Wang; Shiping Yang; Han Yang (Tropical Animal Health and Production, 2023)

Subchronic exposure to di-(2-ethylhexyl) phthalate (DEHP) elicits blood–brain barrier dysfunction and neuroinflammation in male C57BL/6J mice - Wen-qiang Ren; Nuo Liu; Yan Shen; Xian-yan Wang; Qiong Zhou; Chen Rui; Xiao-han Yang; Sheng-long Cao; Ling-yu Li; Yán Wāng; Qu-nan Wang (Toxicology, 2023)

Estimating water surface evaporation losses under floating coverage: Modeling and Application - Ke-Wu Han; Ke-Bin Shi; Xin-Jun Yan; Fei Ling; Guo-Chen Hao; Qian-Ran Qin (Journal of Hydrology, 2023)

Weakened economic impacts with future intensifying drought in Chinese mainland - Feifei Han; Hongbo Ling; Xiaoya Deng; Junjie Yan; Yanming Gong; Guangpeng Zhang; Yuanzhi Ma (Journal of Cleaner Production, 2023)

Logistics density, E-commerce and high-quality economic development: An empirical analysis based on provincial panel data in China - Shaolong Zeng; Qinyi Fu; Fazli Haleem; Yiyang Han; Ling Zhou (Journal of Cleaner Production, 2023)

Effects of muscle-specific oxidative stress on protein phosphorylation and its relationship with mitochondrial dysfunction, muscle oxidation, and apoptosis - Guoyuan Ma; Jiaying Zhang; Zhuo Wang; Qunli Yu; Ling Han (Food Chemistry, 2023)

Aroma enhancement of blueberry wine by postharvest partial dehydration of blueberries - Yu Wang; Qi Zhang; Meng-Yao Cui; Yu Fu; Xiao-Han Wang; Qin Yang; Yue Zhu; Xiao-Hui Yang; Hai-Jun Bi; Xue-Ling Gao (Food Chemistry, 2023)

Physicochemical and biological changes on naturally aged microplastic surfaces in real environments over 10 months - Xue Yu; Bing Wang; Chenglong Han; Ling Liu; Xiaoxin Han; Boyang Zheng; Bo Zhang; Jiawei Sun; Zhiyin Zhang; Weiqi Ma; Lifang Zhai; Xueqiang Lu (Environmental Pollution, 2023)

Self-tuned interfacial charges induced by protonated transition metal heterostructure for efficiently acidic hydrogen evolution reaction - Chuitao Zeng; Jianhua Zhang; Lingzhi Xia; Kai-Ling Zhou; Yuhong Jin; Yongzheng Zhang; Changbao Han; Woon-Ming Lau; Hao Wang (Chemical Engineering Journal, 2023)

Stable anode interface regulation of solid sodium battery through oxygen potential regulation - Weidong Meng; Weibo Han; Lei Dai; Ling Wang; Xianjian Tang; Shan Liu (Chemical Engineering Journal, 2023)

The Critical Role of Equilibrative Nucleoside Transporter-2 in Modulating Cerebral Damage and Vascular Dysfunction in Mice with Brain Ischemia-Reperfusion - Hui-Ling Chiang; Kuo-Chen Wu; You-Yin Chen; Chin-Jui Ho; Han-Lin Wang; Yu-Hua Fu; Wen-Yu Chen; Chun-Jung Lin (Pharmaceutical Research, 2023)

Rapid adaptation of a rotifer prey population to non-consumptive predation pressures - Ling Pan; Han Zhu; Yi-Long Xi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen (Hydrobiologia, 2023)

Cinnamaldehyde, a major component of Cinnamomum cassia Presl ethanol extract, has the potential to unlock the outbreak of WSSV - Xu Zhang; Ling Hu; Han-Wei Liu; Da-Wei Song; Yu-Feng Shen; Lei Liu; Yang Hu; Jiong Chen (Aquaculture, 2023)

Research on dynamic p-y curves in liquefied sand under cyclic loading conditions - Xiao-ling Zhang; Bing-jie Zhang; Wen-Xi Zhang; Yan Han (Ocean Engineering, 2023)

Chitosan coating with grape peel extract: A promising coating to enhance the freeze–thaw stability of beef - Yinjuan Cao; Zhaoyang Song; Chunjuan Dong; Qunli Yu; Ling Han (Meat Science, 2023)

The potential mediation of hypoxia-inducible factor-1α in heat shock protein 27 translocations, caspase-3 and calpain activities and yak meat tenderness during postmortem aging - Xijin Zhu; Renqing Dingkao; Nan Sun; Ling Han; Qunli Yu (Meat Science, 2023)

Distribution and formation of soil balls under heavy rainstorm conditions in the northern Loess Plateau - Bo Yang; Juying Jiao; Xiaowu Ma; Wenting Zhao; Qi Ling; Xinhan Zhang; Jianqiao Han; Pengfei Du; Yin Chen; Hao Chen (Journal of Hydrology, 2023)

From air to airway: Dynamics and risk of inhalable bacteria in municipal solid waste treatment systems - Ru Fang; Tian Chen; Zhibang Han; Wenhui Ji; Yudan Bai; Zhipeng Zheng; Yinglong Su; Ling Jin; Bing Xie; Dong Wu (Journal of Hazardous Materials, 2023)

Performance evaluation on CO2 fixation with chlorine gas production based on direct electrolysis of seawater - Ling Han; Shuai Deng; Ruikai Zhao; Xun Wang; Zhihao Guo; Yixuan Li; Peng Sun (Journal of Environmental Chemical Engineering, 2023)

The immunomodulatory effects of DNA-conjugated collagen scaffolds on bone healing - Jing-han Song; Jun-ting Gu; Gao-peng Dang; Zhi-ting Li; Chen Lei; Ling Li; Zhao Mu; Franklin R. Tay; Kai Jiao; Li-na Niu (Chemical Engineering Journal, 2023)

Titanium oxide nanotubes intercalated two-dimensional MXene composite membrane with exceptional antifouling and self-cleaning properties for oil/water separation - Qianqian Zeng; Die Ling Zhao; Liguo Shen; Hongjun Lin; Ning Kong; Lei Han; Cheng Chen; Jiaheng Teng; Chuyang Tang; Tai-Shung Chung (Chemical Engineering Journal, 2023)

Transdermal delivery of Fluoropolymer-Modified microneedle vaccines against rabies elicits potent humoral immunity - Jiamin Deng; Zongmei Wang; Zhipeng Zhou; Wentao Yu; Xun Li; Zhiyong Song; Heyou Han; Ling Zhao (Chemical Engineering Journal, 2023)

Air pollution exposure and plasma fatty acid profile in pregnant women: a cohort study - Chenhui Yang; Ye Shen; Yiqiong Zhang; Han Xiao; Xiaojie Sun; Jiaqiang Liao; Xinmei Chen; Wenxin Zhang; Ling Yu; Wei Xia; Shunqing Xu; Yuanyuan Li (Environmental Science and Pollution Research, 2023)

Mitochondrial RNA m3C methyltransferase METTL8 relies on an isoform-specific N-terminal extension and modifies multiple heterogenous tRNAs - Meng-Han Huang; Jin-Tao Wang; Jian-Hui Zhang; Xue-Ling Mao; Gui-Xin Peng; Xiuying Lin; Daizhu Lv; Chen Yuan; Huan Lin; En-Duo Wang; Xiao-Long Zhou (Science Bulletin, 2023)

C21 steroids from the roots of Marsdenia tenacissima - Jin-Ling Liu; Hong-Tao Xu; Dan-Dan Mu; Xiao Han; Ting-Ting Du; Yong-li Wang; Xiao-Hui Wei; Gui-Xin Chou (Phytochemistry, 2023)

Analysis of the effect of Tenebrio Molitor rennet on the flavor formation of Cheddar cheese during ripening based on gas chromatography-ion mobility spectrometry (GC-IMS) - Zhaoyang Song; Yinjuan Cao; Haijun Qiao; Pengcheng Wen; Guozheng Sun; Weibing Zhang; Ling Han (Food Research International, 2023)

Ru-catalyzed chemoselective methoxycarbonylation of methyl pentenoate: An assistant role of chloride anions - Shu Zhang; Rui Sun; Pengxin Guan; Yaofeng Wang; Ling Wang; Yanli Zhu; Lijun Han; Jiayu Xin (Chemical Engineering Journal, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Role of Mutations of Mitochondrial Aminoacyl-tRNA Synthetases Genes on Epileptogenesis - Ling-yue Kong; Yi-ze Wu; Run-qi Cheng; Pei-han Wang; Bi-wen Peng (Molecular Neurobiology, 2023)

Hydrodynamic and anthropogenic disturbances co-shape microbiota rhythmicity and community assembly within intertidal groundwater-surface water continuum - Ze Zhao; Lu Zhang; Guoqing Zhang; Han Gao; Xiaogang Chen; Ling Li; Feng Ju (Water Research, 2023)

MaizeNetome: A multi-omics network database for functional genomics in maize - Jia-Wu Feng; Linqian Han; Hao Liu; Wen-Zhao Xie; Hanmingzi Liu; Lin Li; Ling-Ling Chen (Molecular Plant, 2023)

Construction of S-scheme Zn0.2Cd0.8S/biochar aerogel architectures for boosting photocatalytic hydrogen production under sunlight irradiation - Chonghai Deng; Lulu Peng; Xiaohui Ling; Tao Wang; Rui Xu; Yibin Zhu; Chenchen Wang; Xuehui Qian; Lili Wang; Yiping Wu; Hanmei Hu; Yongsheng Han (Journal of Cleaner Production, 2023)

Soft measurement and prediction of refrigerant leakage based on SVR-LSTM - Yuting Yang; Ling Xu; Hua Han; Zhengxiong Ren; Kongrui Wu; Feitian Liu (International Journal of Refrigeration, 2023)

Using UHPLC-HRMS-based comprehensive strategy to efficiently and accurately screen and identify illegal additives in health-care foods - Meng-Han Ma; Jia-Ni Zhang; Xing-Ling Ma; Xing-Cai Wang; Feng-Lian Ma; Jia-Nan Liu; Yi Lv; Yong-Jie Yu; Yuanbin She (Food Research International, 2023)

A gluten degrading probiotic Bacillus subtilis LZU-GM relieve adverse effect of gluten additive food and balances gut microbiota in mice - Aman Khan; Shiqing Li; Huawen Han; Wei-Lin Jin; Zhenmin Ling; Jing Ji; Shazia Iram; Pu Liu; Sa Xiao; El-Sayed Salama; Xiangkai Li (Food Research International, 2023)

Development and characterization of tapioca starch/pectin composite films incorporated with broccoli leaf polyphenols and the improvement of quality during the chilled mutton storage - Zhaoyang Song; Jinwen Wei; Yinjuan Cao; Qunli Yu; Ling Han (Food Chemistry, 2023)

Improvement of hydrolysis efficiency and interfacial properties of zein using nanoemulsions prepared by a low energy emulsification method - Jia-Ling He; Bo-Hao Liu; Han-Lin Zhang; Di Xu; Bao-Ming Shi; Ying-Hua Zhang (Food Bioscience, 2023)

Changes in physicochemical characteristics and metabolites in the fermentation of goji juice by Lactiplantibacillus plantarum - Han Xie; Pengyan Gao; Zhen-Ming Lu; Fang-Zhou Wang; Li-Juan Chai; Jin-Song Shi; Hui-Ling Zhang; Yan Geng; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2023)

Mitigating the adverse effects of Aflatoxin B1 in LMH, IPEC-J2 and 3D4/21 cells by a novel integrated agent - Yi-Xin Mo; Meng-Ling Ruan; Jie Wang; Ying Liu; Yuan-Yuan Wu; Guan-Lin Wang; Yan-Ming Han; Hai-Feng Wan; Dessalegn Lamesgen; Kamil Kuča; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Resilience and probiotic interventions to prevent and recover from shrimp gut dysbiosis - Ramya Kumar; Mei-Ying Huang; Chih-Ling Chen; Han-Ching Wang; Hsiao-Pei Lu (Fish & Shellfish Immunology, 2023)

Spatiotemporal effects of meteorological conditions on global influenza peaks - Yinglin Liang; Zhaobin Sun; Wei Hua; Demin Li; Ling Han; Jian Liu; Liming Huo; Hongchun Zhang; Shuwen Zhang; Yuxin Zhao; Xiaonan He (Environmental Research, 2023)

Tween 80 assisted washing ciprofloxacin-contaminated soil, and recycled it using active chlorines - Yi Ren; Fengchun Li; Luwei Zhai; Dianxiao Dong; Ruifu Han; Xiaoyi Qi; Xin Zhang; Ling Li; Wenqiang Jiang; Xia Chen (Environmental Pollution, 2023)

Sphk1 deficiency induces apoptosis and developmental defects and premature death in zebrafish - Ling Huang; Fang Han; Ying Huang; Jieping Liu; Xinjun Liao; Zigang Cao; Wanbo Li (Fish Physiology and Biochemistry, 2023)

Contributions of abundant and rare bacteria to soil multifunctionality depend on aridity and elevation - Peng He; Ning Ling; Xiao-Tao Lü; Hai-Yang Zhang; Chao Wang; Ru-Zhen Wang; Cun-Zheng Wei; Jing Yao; Xiao-Bo Wang; Xing-Guo Han; Zhibiao Nan (Applied Soil Ecology, 2023)

Fluorescence enhancement of surface plasmon coupled emission by Au nanobipyramids and its modulation effect on multi-wavelength radiation - Kai-Xin Xie; Rui-Ping Huo; Xiu-Li Song; Qiao-Ling Liu; Yue Jiang; Yu-Han Li; Lu-Lu Dong; Jia-Xin Cheng (Analytica Chimica Acta, 2023)

Crop – Livestock integration via maize straw recycling increased carbon sequestration and crop production in China - Ling Liu; Hui-fang Zheng; Zhen Liu; Yu-Zhao Ma; Hui-fang Han; Tang-yuan Ning (Agricultural Systems, 2023)

FDX1 enhances endometriosis cell cuproptosis via G6PD-mediated redox homeostasis - Jiayi Lu; Xi Ling; Yonghong Sun; Lu Liu; Lan Liu; Xiaoyun Wang; Chao Lu; Chune Ren; Xue Han; Zhenhai Yu (Apoptosis, 2023)

Spatiotemporal characteristics of carbon emissions in Shaanxi, China, during 2012–2019: a machine learning method with multiple variables - Ziyan Liu; Ling Han; Ming Liu (Environmental Science and Pollution Research, 2023)

Fluoride occurrence in geothermal water of fault zone area, Southeast China - Xuelian Huang; Yongjie Han; Zhicai Xiao; Shuai Wang; Sijia Wang; Min Zhang; Turong Zeng; Ling Tang; Hailong Li; Shihua Qi (Chemosphere, 2023)

Ocean acidification increases inorganic carbon over organic carbon in shrimp's exoskeleton - Veran Weerathunga; Chin-Chang Hung; Sam Dupont; Hsueh-Han Hsieh; Nathangi Piyawardhana; Fei-Ling Yuan; Kai-Jung Kao; Kuei-Chen Huang; Wei-Jen Huang (Marine Pollution Bulletin, 2023)

Transcriptional regulatory network of high-value active ingredients in medicinal plants - Han Zheng; Xueqing Fu; Jin Shao; Yueli Tang; Muyao Yu; Ling Li; Luqi Huang; Kexuan Tang (Trends in Plant Science, 2023)

Statistical modeling of multivariate loess properties in Taiyuan using regular vine copula with optimized tree structure - Dongdong Yan; Tengyuan Zhao; Ling Xu; Lu Zuo; Han Wen; Jie Ren (Transportation Geotechnics, 2023)

Effects of different test methods on the seismic dynamic response in inclined liquefiable soil - Xiao-ling Zhang; Xian-hui Zhao; Cheng-shun Xu; Ke-min Jia; Yan Han (Soil Dynamics and Earthquake Engineering, 2023)

Corrigendum to “Carbon capture by macroalgae Sarcodia suae using aquaculture wastewater and solar energy for cooling in subtropical regions” [Sci. Total Environ. 855 (2023) 158850] - W. Sanjaya Weerakkody; Ka Hin Ling; Hsueh-Han Hsieh; Vicente G. Abedneko; Jeng-Feng Shyu; Tse-Min Lee; Yung-Yen Shih; R.R.M.K.P. Ranatunga; Peter H. Santschi; Chin-Chang Hung (Science of The Total Environment, 2023)

Emission characteristics of condensable particulate matter (CPM) from FCC flue gas - Jiawei Bian; Hai Zhao; Bohan Wang; Bingqiang Han; Hao Ling; Feng Ju (Science of The Total Environment, 2023)

Nitrogen removal enhanced by its migration and transformation in a three-chamber microbial electrolysis cell - Xiao-Li Yang; Ling Zang; Jia-Jin Chen; Han Xu; Yi-Jing Yang; Hai-Liang Song (Journal of Water Process Engineering, 2023)

Electrolyte circulation: Metal recovery from waste printed circuit boards of mobile phones by alkaline slurry electrolysis - Qian Liang; Jiqin Wang; Shuyuan Chen; Shaoqin Chen; Ling Hu; Jinchuan Qin; Yunhui Han; Xiangfei Zeng; Xiaogang Li; Qingbin Guo; Mengjun Chen; Jiancheng Shu (Journal of Cleaner Production, 2023)

Effects of pollen concentration on allergic rhinitis in children: A retrospective study from Beijing, a Chinese megacity - Yuxin Zhao; Zhaobin Sun; Li Xiang; Xingqin An; Xiaoling Hou; Jing Shang; Ling Han; Caihua Ye (Environmental Research, 2023)

Association of long-term exposure to air pollutant mixture and incident cardiovascular disease in a highly polluted region of China - Fuyuan Wen; Bingxiao Li; Han Cao; Pandi Li; Yunyi Xie; Fengxu Zhang; Yuan Sun; Ling Zhang (Environmental Pollution, 2023)

Stable β-form zinc phthalocyanine cathodes for flexible Zn-ion hybrid supercapacitors with ultra-long cycling life - Daotong Han; Wenyun Wang; Shangjing Yu; Wentao Qi; Rui Ling; Chao Yang; Guangqiang Liu (Chemical Engineering Journal, 2023)

Evaluation of key factors influencing urban ozone pollution in the Pearl River Delta and its atmospheric implications - Xiao-Yu Lin; Shi-Yong Xia; Yao Luo; Heng-Xiao Han; Ling-Yan He (Atmospheric Environment, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Life stage affects prey use with fitness consequences in a zoophytophagous mirid bug - Ruo-han Ma; Jia-min Gu; Coline C. Jaworski; Zheng-xuan Xue; Xue-ling Li; Pei-ling Wang; Peng Han; Nicolas Desneux (Phytoparasitica, 2023)

Stable isotope labeling differential glycans discovery in the serum of acute myocardial infarction by ultrahigh-performance liquid chromatography-quadrupole-Orbitrap high resolution mass spectrometry - Xi-Ling Li; Yuxuan Li; Shuyun Xiao; Qingsong Li; Chengqiang Han; Danyang Liu; Tengfei Cui; Xiyang Rao; Kenichiro Todoroki; Guang Yang; Jun Zhe Min (Analytica Chimica Acta, 2023)

Influence analysis of overlying soil layer to seismic behavior of inclined liquefiable soil and pile interaction system - Xiao-ling Zhang; Li-jing Fang; Cheng-shun Xu; Ke-min Jia; Yan Han (Soil Dynamics and Earthquake Engineering, 2023)

Spatial distribution and driving factors of groundwater chemistry and pollution in an oil production region in the Northwest China - Hongyu Zhang; Xu Han; Guangcai Wang; Hairu Mao; Xianglong Chen; Ling Zhou; Dandan Huang; Fan Zhang; Xin Yan (Science of The Total Environment, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

A study of flavor variations during the flaxseed roasting procedure by developed real-time SPME GC–MS coupled with chemometrics - Xing-Ling Ma; Xing-Cai Wang; Jia-Ni Zhang; Jia-Nan Liu; Meng-Han Ma; Feng-Lian Ma; Yi Lv; Yong-Jie Yu; Yuanbin She (Food Chemistry, 2023)

Screening, structural characterization and anti-adipogenesis effect of a water-soluble polysaccharide from Lycium barbarum L. by an activity-oriented approach - Han Wang; Yunchun Li; Yunyun Dai; Ling Ma; Duolong Di; Jianfei Liu (Food Bioscience, 2023)

Anion assisted completely reconfigured manganese oxides with optimal proton adsorption for boosting acidic hydrogen evolution reaction - Wen Kang Zhao; Bei Chen Sun; Chang Bao Han; Kai Ling Zhou; Chao Wang; Jia Yu Zheng; Yuangang Lu; Decai Fang; Hui Yan (Chemical Engineering Journal, 2023)

Roles of vetiver roots in desiccation cracking and tensile strengths of near-surface lateritic soil - Qian-Feng Gao; Han Yu; Ling Zeng; Rui Zhang; Yuan-Hang Zhang (CATENA, 2023)

Molecular characterization and validation of adult-plant stripe rust resistance gene Yr86 in Chinese wheat cultivar Zhongmai 895 - Zhanwang Zhu; Qiang Cao; Dejun Han; Jianhui Wu; Ling Wu; Jingyang Tong; Xiaowan Xu; Jun Yan; Yong Zhang; Kaijie Xu; Fengju Wang; Yachao Dong; et al. (Theoretical and Applied Genetics, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

NLRP7 participates in the human subcortical maternal complex and its variants cause female infertility characterized by early embryo arrest - Jian Han; Nana Zhang; Qiqi Cao; Xiaodan Shi; Congjing Wang; Ximan Rui; Jie Ding; Chun Zhao; Junqiang Zhang; Xiufeng Ling; Hong Li; Yichun Guan; et al. (Journal of Molecular Medicine, 2023)

How do epiphytic and surrounding seawater bacterial communities shift with the development of the Saccharina japonica farmed in the Northern China? - Ling Cai; Xin Gao; Mahasweta Saha; Yixiao Han; Lirong Chang; Luyang Xiao; Gaoge Wang (Frontiers in Marine Science, 2023)
Epibacteria of seaweeds play an important role for the development of hosts and are influenced by the planktonic surrounding seawater bacteria. However, to date, the knowledges related to both epiphytic and surrounding seawater bacterial communities associated with northern farmed Saccharina japonica are very limited. In this study, using 16S rRNA gene amplicon sequencing, the shifts of epiphytic and surrounding seawater bacterial communities of the northern farmed S. japonica from mature sporophytes, sporelings (3 time points) to juvenile sporophytes (2 time points) were investigated. The dominant genera of epibacterial communities were Alcanivorax (mature sporophytes and 4-week-old sporelings), Bacillus (7-week-old sporelings and 9-week-old sporelings), Halomonas (4-week-old juvenile sporophytes) and Cobetia (9-week-old juvenile sporophytes). Meanwhile, the Chao1 indexes and beta diversity of epibacterial communities were significantly different with the development of S. japonica ( p < 0.05). Furthermore, Alcanivorax , Bacillus and Halomonas were both dominant and core genera, indicating that these taxa may be beneficial to the development of S. japonica . The alpha diversity indexes of both epiphytic and surrounding seawater bacterial communities were significantly different for 9-week-old juvenile sporophytes. Therefore, the epibacterial communities were influenced by both development of S. japonica and the surrounding seawater bacterial communities. This study not only extends the understanding of the bacterial communities associated with the northern farmed S. japonica , but also help to make production management by monitoring the variations in both epiphytic and surrounding seawater bacterial communities.

An optimization method for surface urban heat island footprint extraction based on anisotropy assumption - Ke Yang; Fei Tao; Chu-Ling Wang; Zi-Long Wang; Qi-Le Han; Tong Zhou (Urban Climate, 2023)

Rapid screening of diarylpentanoids from Daphne bholua - Shu-Hui Dong; Mei-Ya Lian; Jin-Ling Han; Yun-Fei Ai; Xiao-Fang Zhou; Ming Bai; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Zinc efficiently extracted from zinc calcine by reduced wet grinding: ZnFe2O4 to ZnO and Fe3O4 - Shaoqin Chen; Xiangfei Zeng; Qian Liang; Ling Hu; Shuyuan Chen; Dejun He; Yunhui Han; Zhisheng Zhao; Rong Huang; Yin Huang; Songshan Zhou; Jiqin Wang; et al. (Journal of Cleaner Production, 2023)

Effects of Torulaspora delbrueckii co-fermented with Saccharomyces cerevisiae on physicochemical and aromatic profiles of blueberry fermented beverage - Yu Wang; Xiao-Yan Qi; Yu Fu; Qi Zhang; Xiao-Han Wang; Meng-Yao Cui; Ying-Ying Ma; Xue-Ling Gao (Food Chemistry, 2023)

Disease resistance conferred by components of essential chrysanthemum oil and the epigenetic regulation of OsTPS1 - Chuansong Zhan; Long Lei; Hao Guo; Shen Zhou; Congping Xu; Zixin Liu; Zichen Wu; Yuan Deng; Yuanyuan Miao; Yu Han; Meng Zhang; Hua Li; et al. (Science China Life Sciences, 2023)

Deficiency of RAB39B Activates ER Stress-Induced Pro-apoptotic Pathway and Causes Mitochondrial Dysfunction and Oxidative Stress in Dopaminergic Neurons by Impairing Autophagy and Upregulating α-Synuclein - Ching-Chi Chiu; Yi-Hsin Weng; Tu-Hsueh Yeh; Juu-Chin Lu; Wan-Shia Chen; Allen Han-Ren Li; Ying-Ling Chen; Kuo-Chen Wei; Hung-Li Wang (Molecular Neurobiology, 2023)

A comparison of feature extraction capabilities of advanced UHPLC-HRMS data analysis tools in plant metabolomics - Xing-Cai Wang; Xing-Ling Ma; Jia-Nan Liu; Yang Zhang; Jia-Ni Zhang; Meng-Han Ma; Feng-Lian Ma; Yong-Jie Yu; Yuanbin She (Analytica Chimica Acta, 2023)

Study on the resourceful reuse in SBS-modified asphalt of waste bagasse fibers based on green modification with tannic acid and FeOOH - Ling Yang; Fuhu Han; Yaseen Muhammad; Yu Liu; Zhenxia Zhao; Hao Kong; Jing Li; Honggang Zhang (Environmental Science and Pollution Research, 2023)

Toxicological characteristics of drinking water in two large-scale municipal water supply systems of a metropolitan city in Central China - Huai-Ji Wang; Chen-Wei Peng; Xue Han; Yan Wang; Jie Zhang; Jun-Ling Liu; Meng-Xuan Zhou; Fei Tang; Ai-Lin Liu (Environmental Science and Pollution Research, 2023)

Transcriptional regulatory network of high-value active ingredients in medicinal plants - Han Zheng; Xueqing Fu; Jin Shao; Yueli Tang; Muyao Yu; Ling Li; Luqi Huang; Kexuan Tang (Trends in Plant Science, 2023)

A corrected p-y curve model for large-diameter pile foundation of offshore wind turbine - Xiao-ling Zhang; Rui Zhou; Guo-liang Zhang; Yan Han (Ocean Engineering, 2023)

Simulation and risk assessment of arsenic by Hydrus-3D and CalTOX in a typical brownfield site - Tianhao He; Ye Li; Ye Huang; Erkai He; Yan Li; Liangyu Qu; Fangfang Ding; Ruihe Jin; Mingzhe Han; Lina Yuan; Weizhen Xue; Ruijuan Qu; et al. (Journal of Hazardous Materials, 2023)

Proteomic analysis reveals differential responsive mechanisms in Solanum nigrum exposed to low and high dose of cadmium - Ling-Yu Song; Xiang Liu; Lu-Dan Zhang; Wen-Jun Hu; Chao-Qun Xu; Jing Li; Shi-Wei Song; Ze-Jun Guo; Chen-Yang Sun; Han-Chen Tang; Ji-Cheng Wang; Xue-Yi Zhu; et al. (Journal of Hazardous Materials, 2023)

Treatment of Cd(Ⅱ) and As(Ⅴ) co-contamination in aqueous environment by steel slag-biochar composites and its mechanism - Menglu Wang; Xuemei Wang; Meng Zhang; Wei Han; Zhuang Yuan; Xinlian Zhong; Ling Yu; Hongbing Ji (Journal of Hazardous Materials, 2023)

Redox evolution of differentiating hydrous basaltic magmas recorded by zircon and apatites in mafic cumulates: The case of the Malayer Plutonic Complex, Western Iran - Reza Deevsalar; Yuanming Pan; Ryuichi Shinjo; Luke Milan; Ke-han Song; Qunfeng Xiao; Mohsen Shakouri; Alisa Rae-Ling Paterson; Yongfeng Hu (Geochemistry, 2023)

Mixing of tree species with the same water use strategy might lead to deep soil water deficit - Lei Han; Lili Liu; Ling Peng; Nana Wang; Peng Zhou (Forest Ecology and Management, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

β-carboline alkaloids in Picrasma quassioides and their chemotaxonomic significance - Jin-Ling Han; Tian-Ming Lv; Shao-Jiang Song; Xiao-Xiao Huang (Biochemical Systematics and Ecology, 2023)

Co-contaminants of ethinylestradiol and sulfamethoxazole in groundwater exacerbate ecotoxicity and ecological risk and compromise the energy budget of C. elegans - Yu-Hsuan Kuo; Chun Ming How; Chi-Wei Huang; Pei-Ling Yen; Chan-Wei Yu; Chun-Han Chang; Vivian Hsiu-Chuan Liao (Aquatic Toxicology, 2023)

Two Novel Species of Mesophoma gen. nov. from China - Ai-Ling Yang; Lin Chen; Lu Cheng; Jin-Peng Li; Zhao-Ying Zeng; Han-Bo Zhang (Current Microbiology, 2023)

Significance of temperature control in nitrogen transformations in surface sediments of Taihu Lake, China - Ling Wu; Wenhui Zhong; Hongyi Qin; Cheng Han (Paddy and Water Environment, 2023)

One-pot RPA-Cas12a assay for instant and visual detection of Burkholderia pseudomallei - Ling Deng; Xiaoyi He; Ke Liu; Yuanli Li; Han Xia; Hang Qian; Xiaoxue Lu; Xuhu Mao; Yang Xiang (Analytica Chimica Acta, 2023)

Self-assembled DNA nanoparticles enable cascade circuits for mRNA detection and imaging in living cells - Zhe Dong; Debo Gao; Yuancheng Li; Kang An; Jing Ni; Ling Meng; Han Wu (Analytica Chimica Acta, 2023)

Molecular cloning, characterization, and expression patterns of the hatching enzyme genes during embryonic development of pikeperch (Sander lucioperca) - Chenglong Pan; Lingling Li; Hao Zhu; Wenjia Mao; Tao Han; Xuqian Zhao; Caijuan Li; Qufei Ling (Aquaculture International, 2023)

Pickering foams stabilized by protein-based particles: A review of characterization, stabilization, and application - Yameng Han; Ling Zhu; Emad Karrar; Xiguang Qi; Hui Zhang; Gangcheng Wu (Trends in Food Science & Technology, 2023)

Optical properties of sedimentary dissolved organic matter in intertidal zones along the coast of China: Influence of anthropogenic activities - Zhe Wang; Min Lv; Chu-Long Huang; Dong-Dong Zhang; Ruixia Han; Gang Li; Ling-Xin Chen (Science of The Total Environment, 2023)

Using HRMS fingerprinting to explore micropollutant contamination in soil and vegetables caused by swine wastewater irrigation - Wen-Ling Chen; Sih-Yi Yu; Shu-Yen Liu; Sheng-Chi Lin; Tsung-Han Lee (Science of The Total Environment, 2023)

Managing straw and nitrogen fertilizer based on nitrate threshold for balancing nitrogen requirement of maize and nitrate residue - Ru Guo; Rui Qian; Fei Han; Abdul Khaliq; Sadam Hussain; Ling Yang; Peng Zhang; Xiaoli Chen; Xiaolong Ren (Journal of Environmental Management, 2023)

Production and identification of dipeptidyl peptidase IV (DPP-IV) inhibitory peptides from discarded cowhide collagen - Long He; Xinyue Wang; Yanru Wang; Jin Luo; Yining Zhao; Guangxing Han; Ling Han; Qunli Yu (Food Chemistry, 2023)

Autochthonous Bacillus subtilis and Enterococcus faecalis improved liver health, immune response, mucosal microbiota and red-head disease resistance of yellow drum (Nibea albiflora) - Xi-Yue Ding; Cheng-Ye Wei; Zi-Yan Liu; Hong-Ling Yang; Fang Han; Yun-Zhang Sun (Fish & Shellfish Immunology, 2023)

Corrigendum to “Discovery and characterization of the flavonoids in Cortex Mori Radicis as naturally occurring inhibitors against intestinal nitroreductases” [Chem. Biol. Interact. 368 (2022) 110222] - Xi Chen; Yue Han; Lu Chen; Qian-Lin Tian; Yu-Ling Yin; Qi Zhou; Shi-Zhu Zang; Jie Hou (Chemico-Biological Interactions, 2023)

P2X7 receptor involved in antitumor activity of atractylenolide I in human cervical cancer cells - Yue Han; Can Bai; Xi-Meng He; Qing-Ling Ren (Purinergic Signalling, 2023)
Atractylenolide I (Atr-I) was found to sensitize a variety of human cancer cells in previous studies. Purinergic P2X7R plays important role in different cancers. However, whether Atr-I could generate antitumor activity in human cervical cancer cells and P2X7R get involved in this effect remain unclear. In this study, Hela (HPV 18 +) and SiHa (HPV 16 +) cells were treated with different doses of Atr-I. The results indicated that agonist and antagonist of P2X7 receptors, BzATP and JNJ-47965567 (JNJ), could suppress the proliferation of Hela and SiHa cells. Atr-I demonstrated a considerable antitumor effect in both human cervical cancer cells in vitro. Atr-I combined with P2X7R agonist, BzATP, restored Atr-I-induced growth inhibition in Hela cells but not in SiHa cells. However, the combinatorial treatment of P2X7R antagonist JNJ and Atr-I has an additive effect on cell growth inhibition in SiHa cells rather than in Hela cells. It implied that P2X7R would get involved in the anti-human cervical cancer cells effect of Atr-I.

Multi-omics analysis identifies potential mechanisms by which high glucose accelerates macrophage foaming - Jie Qi; Ying Lv; Ni-Er Zhong; Wen-Qi Han; Qi-Ling Gou; Chao-Feng Sun (Molecular and Cellular Biochemistry, 2023)

Landslide displacement prediction based on optimized empirical mode decomposition and deep bidirectional long short-term memory network - Ming-yue Zhang; Yang Han; Ping Yang; Cong-ling Wang (Journal of Mountain Science, 2023)

Spatiotemporal change and driving factors of ecological status in Inner Mongolia based on the modified remote sensing ecological index - Bai Zongfan; Han Ling; Liu Huiqun; Jiang Xuhai; Li Liangzhi (Environmental Science and Pollution Research, 2023)

Genotoxicity of organic contaminants in the soil: A review based on bibliometric analysis and methodological progress - Miao Han; Zaifeng Zhang; Si Liu; Youying Sheng; Michael Gatheru Waigi; Xiaojie Hu; Chao Qin; Wanting Ling (Chemosphere, 2023)

The conserved L1089 in the S2 subunit of avian infectious bronchitis virus determines viral kidney tropism by disrupting virus-cell fusion - Shu-Yun Li; Yu-Xi Shen; Xue-Lian Xiang; Yong-Xin Li; Nian-Ling Li; An-Dong Wang; Min Cui; Xin-Feng Han; Yong Huang; Jing Xia (Veterinary Microbiology, 2023)

The shared NDM-positive strains in the hospital and connecting aquatic environments - Huiyun Zou; Jingyi Han; Ling Zhao; Di Wang; Yanyu Guan; Tianle Wu; Xinjiao Hou; Hui Han; Xuewen Li (Science of The Total Environment, 2023)

Divergent responses in the gut microbiome and liver metabolome to ammonia stress in three freshwater turtles - Qin-Yuan Meng; Dong-Mei Mo; Han Li; Wan-Ling Wang; Hong-Liang Lu (Science of The Total Environment, 2023)

Associations between serum polychlorinated biphenyls, halogen flame retardants, and renal function indexes in residents of an e-waste recycling area - Ling-Chuan Guo; Zhanlu Lv; Tingting Zhu; Guanhao He; Jianxiong Hu; Jianpeng Xiao; Tao Liu; Shengbing Yu; Jinliang Zhang; Han Zhang; Wenjun Ma (Science of The Total Environment, 2023)

Two new monoterpenoids from the stems of Ephedra sinica - Chen He; Yan-gang Cao; Meng-nan Zeng; Yu-han Zhang; Ying-jie Ren; Yan-ling Liu; Xu Chen; Xi-ling Fan; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry Letters, 2023)

Calcium isotope systematics of altered oceanic crust at IODP site 1256: Insights into the hydrothermal alteration - Ling-Zhi Hu; Jin-Ting Kang; Yu-Han Qi; Yong-Jun Gao; Xiao-Yun Nan; Jian Huang; Fang Huang (Lithos, 2023)

Spatial and temporal dynamics of microbial community composition and factors influencing the surface water and sediments of urban rivers - Hongjie Wang; Xingchun Liu; Yali Wang; Shengqi Zhang; Guangming Zhang; Yangyang Han; Mengxiang Li; Ling Liu (Journal of Environmental Sciences, 2023)

Are olefin aromatization reactions structure sensitive over Al pairs and single Al in H-ZSM-5 Zeolite? - Mengjiao Xing; Yunlei Chen; Jian Cao; Yuanlong Han; Zhichao Tao; Fei Wang; Kun Hao; Ling Zhang; Wentao Zheng; Hongwei Xiang; Yong Yang; Yongwang Li; et al. (Fuel, 2023)

A study on the release characteristics and formation mechanism of SO2 during co-combustion of sewage sludge and coal slime - Xin Wang; Jun Xu; Peng Ling; Xiaoxue An; Hengda Han; Yifeng Chen; Long Jiang; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Fuel, 2023)

SWCNTs/Ag2Se film with superior bending resistance and enhanced thermoelectric performance via in situ compositing - Qin-Xue Hu; Wei-Di Liu; Li Zhang; Wei Sun; Han Gao; Xiao-Lei Shi; Yan-Ling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2023)

Collateral-Core Ratio as a Novel Predictor of Clinical Outcomes in Acute Ischemic Stroke - Jinhao Lyu; Sa Xiao; Zhihua Meng; Xiaoyan Wu; Wen Chen; Guohua Wang; Qingliang Niu; Xin Li; Yitong Bian; Dan Han; Weiting Guo; Shuai Yang; et al. (Translational Stroke Research, 2023)

Novel (Z)/(E)-1,2,4-triazole derivatives containing oxime ether moiety as potential ergosterol biosynthesis inhibitors: design, preparation, antifungal evaluation, and molecular docking - Shengxin Sun; Jinghua Yan; Lang Tai; Jianqi Chai; Haoran Hu; Ling Han; Aimin Lu; Chunlong Yang; Min Chen (Molecular Diversity, 2023)

The effects of environmental, climatic and spatial factors on diatom diversity in Sphagnum peatlands in central and northeastern China - Jun-Lu Li; Zhao-Jun Bu; Xian-Yu Huang; Ling-han Zeng; Xu Chen (Hydrobiologia, 2023)

Municipal solid waste, an overlooked route of transmission for the severe acute respiratory syndrome coronavirus 2: a review - Jie Han; Shanshan He; Wenyuan Shao; Chaoqi Wang; Longkai Qiao; Jiaqi Zhang; Ling Yang (Environmental Chemistry Letters, 2023)

Substituting fish meal with a bacteria protein (Methylococcus capsulatus, Bath) grown on natural gas: Effects on growth non-specific immunity and gut health of spotted seabass (Lateolabrax maculatus) - Man-han Yu; Xue-shan Li; Jia Wang; Matt Longshaw; Kai Song; Ling Wang; Chun-xiao Zhang; Kang-le Lu (Animal Feed Science and Technology, 2023)

Carbon capture by macroalgae Sarcodia suae using aquaculture wastewater and solar energy for cooling in subtropical regions - W. Sanjaya Weerakkody; Ka Hin Ling; Hsueh-Han Hsieh; Vicente G. Abedneko; Jeng-Feng Shyu; Tse-Min Lee; Yung-Yen Shih; R.R.M.K.P. Ranatunga; Peter H. Santschi; Chin-Chang Hung (Science of The Total Environment, 2023)

Exploring business models for carbon emission reduction via post-consumer recycling infrastructures in Beijing: An agent-based modelling approach - Xin Tong; Haofan Yu; Ling Han; Tao Liu; Liang Dong; Filippos Zisopoulos; Benjamin Steuer; Martin de Jong (Resources, Conservation and Recycling, 2023)

Application of a count data model to evaluate the anti-metastatic efficacy of QAP14 in 4T1 breast cancer allografts - Yuchen Guo; Ling Yong; Qingyu Yao; Mengyi Han; Junsheng Xue; Weizhe Jian; Tianyan Zhou (Journal of Theoretical Biology, 2023)

Efficient biodegradation of acetoacetanilide in hypersaline wastewater with a synthetic halotolerant bacterial consortium - Yanqing Zhang; Ke Shi; Hanlin Cui; Jinglong Han; Hao Wang; Xiaodan Ma; Zhiling Li; Ling Zhang; Shichen Nie; Changshui Ma; Aijie Wang; Bin Liang (Journal of Hazardous Materials, 2023)

How magnitude of PM2.5 exposure disparities have evolved across Chinese urban-rural population during 2010–2019 - Ming Liu; Yang Wang; Ruochen Liu; Chao Ding; Gaoxiang Zhou; Ling Han (Journal of Cleaner Production, 2023)

A novel UHPLC-MS/MS method for the determination of four α-dicarbonyl compounds in wine and dynamic monitoring in human urine after drinking - Chao Qi; Yueying Jin; Shengyu Cheng; Lei Di; Xin Wang; Minghui Zhang; Lingli Zhang; Xi-Ling Li; Yu Han; Qingkun Ma; Jun Zhe Min (Food Research International, 2023)

Numerical study of steel plate shear walls with diverse construction configurations - Chen Wang; Li-yan Xu; Ling-han Song; Jian-sheng Fan (Engineering Structures, 2023)

Correction to: Modeling landslide susceptibility using data mining techniques of kernel logistic regression, fuzzy unordered rule induction algorithm, SysFor and random forest - Tingyu Zhang; Quan Fu; Chao Li; Fangfang Liu; Huanyuan Wang; Ling Han; Renata Pacheco Quevedo; Tianqing Chen; Na Lei (Natural Hazards, 2023)

Humulus lupulus L. extract and its active constituent xanthohumol attenuate oxidative stress and nerve injury induced by iron overload via activating AKT/GSK3β and Nrf2/NQO1 pathways - Sun Xiao-Lei; Xia Tian-Shuang; Jiang Yi-Ping; Wang Na-Ni; Xu Ling-Chuan; Han Ting; Xin Hai-Liang (Journal of Natural Medicines, 2023)

QTL analyses of soybean root system architecture revealed genetic relationships with shoot-related traits - Zhili Wang; Cheng Huang; Yongchao Niu; Wai-Shing Yung; Zhixia Xiao; Fuk-Ling Wong; Mingkun Huang; Xin Wang; Chun-Kuen Man; Ching-Ching Sze; Ailin Liu; Qianwen Wang; et al. (Theoretical and Applied Genetics, 2022)

Manganese addition accelerates litter decomposition and alters litter mixing effects in the late stage in subtropical plantations of southern China - Pan-Pan Wu; Ling-Xin Jiang; Yan Zhang; Qi-Han Tu; Rong Mao (Plant and Soil, 2022)

Modeling landslide susceptibility using data mining techniques of kernel logistic regression, fuzzy unordered rule induction algorithm, SysFor and random forest - Tingyu Zhang; Quan Fu; Chao Li; Fangfang Liu; Huanyuan Wang; Ling Han; Renata Pacheco Quevedo; Tianqing Chen; Na Lei (Natural Hazards, 2022)

Interactive Effects of Maize Straw-Derived Biochar and N Fertilization on Soil Bulk Density and Porosity, Maize Productivity and Nitrogen Use Efficiency in Arid Areas - Ru Guo; Rui Qian; Ling Yang; Abdul Khaliq; Fei Han; Sadam Hussain; Peng Zhang; Tie Cai; Zhikuan Jia; Xiaoli Chen; Xiaolong Ren (Journal of Soil Science and Plant Nutrition, 2022)

Two new phenylpropenoid glycosides from the roots of Illicium dunnianum - Yi-lin Wang; Han Li; Ling Song; Yun-hang Gao; Teng-fei Chen (Natural Product Research, 2022)

Enhanced Fluoride Stabilization by Modified Layered Double Hydroxides for the Remediation of Soil Pollution: Performance and Mechanism - Dong-ling Wang; Yu-han Fu; Jin-yan Yang (Water, Air, & Soil Pollution, 2022)

Rootstock rescues watermelon from Fusarium wilt disease by shaping protective root-associated microbiomes and metabolites in continuous cropping soils - An-Hui Ge; Zhi-Huai Liang; Li-Li Han; Ji-Ling Xiao; Yi Zhang; Qing Zeng; Ji-Fang Xiang; Chao Xiong; Li-Mei Zhang (Plant and Soil, 2022)

Harmonizing surface reflectance between Landsat-7 ETM + , Landsat-8 OLI, and Sentinel-2 MSI over China - Hongye Cao; Ling Han; Liangzhi Li (Environmental Science and Pollution Research, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Impacts of climate and reservoirs on the downstream design flood hydrograph: a case study of Yichang Station - Rongrong Li; Lihua Xiong; Xini Zha; Bin Xiong; Han Liu; Jie Chen; Ling Zeng; Wenbin Li (Natural Hazards, 2022)

Associations of long-term ambient air pollution and traffic-related pollution with blood pressure and hypertension defined by the different guidelines worldwide: the CHCN-BTH study - Bingxiao Li; Han Cao; Kuo Liu; Juan Xia; Yanyan Sun; Wenjuan Peng; Yunyi Xie; Chunyue Guo; Xiaohui Liu; Fuyuan Wen; Fengxu Zhang; Guangliang Shan; et al. (Environmental Science and Pollution Research, 2022)

Applicability of standard forward column/row recurrence equations for ALFs - Han-Wei Zhang; Hua Zhang; Xiao-Ling Li; Yong-Qin Yang (Applied Geophysics, 2022)

Reliability analysis of prestressed anchors in rock slopes of open-pit mines - Min Bao; Zhong-hui Chen; Ling-fei Zhang; Zi-han Zhou; Geng-qian Nian; Shu-yao Shi (Journal of Mountain Science, 2022)

Functional microglia derived from human pluripotent stem cells empower retinal organs - Mei-Ling Gao; Xiao Zhang; Fang Han; Jia Xu; Si-Jian Yu; Kangxin Jin; Zi-Bing Jin (Science China Life Sciences, 2022)

Evaluation of PET List Data-Driven Gated Motion Correction Technique Applied in Lung Tumors - Yi-Lun Chen; Bang-Hung Yang; I.-Ling Shih; Ko-Han Lin (Journal of Medical and Biological Engineering, 2022)

Relationships of multiple metals exposure, global DNA methylation, and urothelial carcinoma in central Taiwan - Hui-Tsung Hsu; Hui-Ling Lee; Hsu-Hui Cheng; Chao-Hsiang Chang; Chiu-Shong Liu; Po-Jen Hsiao; Han Chang; Chi-Shun Lien; Mu-Chi Chung; Chi-Jung Chung (Archives of Toxicology, 2022)

Responses of photosynthesis, antioxidant enzymes, and related gene expression to nicosulfuron stress in sweet maize (Zea mays L.) - Zhen-Xing Wu; Ning-Wei Xu; Min Yang; Xiang-Ling Li; Jin-Ling Han; Xiao-Hu Lin; Qing Yang; Gui-Hua Lv; Jian Wang (Environmental Science and Pollution Research, 2022)

Chemical constituents of Viscum coloratum (Kom.) Nakai and their cytotoxic activities - Ying-Ying Chen; Jiang-Ping Hou; Ling Huang; Afsar Khan; Fei-Fei Xing; Xiao-Han Zhang; De-Feng Han; Shi-Li Yan; Gui-Dong Cao; Qi-Yang Jiao; Dejie Liu; Xuwei Zhu; et al. (Natural Product Research, 2022)

Synthesis, antifungal activity, and molecular dynamics study of novel geranyl aromatic sulfonamide compounds as potential complex III inhibitors - Xinning Song; Zhiyang Jiang; Jianing Li; Xingxing Lu; Qing Han; Kai Zhu; Huilin Li; Yun Ling; Hongxia Duan (Medicinal Chemistry Research, 2022)

A novel anticancer property of Lycium barbarum polysaccharide in triggering ferroptosis of breast cancer cells - Xing Du; Jingjing Zhang; Ling Liu; Bo Xu; Hang Han; Wenjie Dai; Xiuying Pei; Xufeng Fu; Shaozhang Hou (Journal of Zhejiang University-SCIENCE B, 2022)

Novel blood-based hypomethylation of SH3BP5 is associated with very early-stage lung adenocarcinoma - Rong Qiao; Runbo Zhong; Chunlan Liu; Feifei Di; Zheng Zhang; Ling Wang; Tian Xu; Yue Wang; Liping Dai; Wanjian Gu; Baohui Han; Rongxi Yang (Genes & Genomics, 2022)

Screening and identification of HLA-A2-restricted neoepitopes for immunotherapy of non-microsatellite instability-high colorectal cancer - Ranran Shi; Yubing Li; Ling Ran; Yu Dong; Xiuman Zhou; Jingwen Tang; Lu Han; Mingshuang Wang; Liwei Pang; Yuanming Qi; Yahong Wu; Yanfeng Gao (Science China Life Sciences, 2022)

The short-term impact of the COVID-19 epidemic on socioeconomic activities in China based on the OMI-NO2 data - Hongye Cao; Ling Han (Environmental Science and Pollution Research, 2022)

The lining responses for shallow mountain tunnels subjected to frost heaving - Xian-zhang Ling; Yuan Yu; Liang Tang; Lin Geng; Xiao Han (Journal of Mountain Science, 2022)

Comparative phylogeography of Acanthocalyx (Caprifoliaceae) reveals distinct genetic structures in the Himalaya–Hengduan Mountains - Qi-Yong Mu; Chih-Chieh Yu; Yan Wang; Ting-Shen Han; Hui Wang; Wen-Na Ding; Qiu-Yue Zhang; Shook Ling Low; Quan-Jing Zheng; Chuan Peng; Zheng-Yan Hu; Yao-Wu Xing (Alpine Botany, 2022)

Bagging-based machine learning algorithms for landslide susceptibility modeling - Tingyu Zhang; Quan Fu; Hao Wang; Fangfang Liu; Huanyuan Wang; Ling Han (Natural Hazards, 2022)

The GSK-3β/β-Catenin Signaling–Mediated Brain–Derived Neurotrophic Factor Pathway Is Involved in Aluminum-Induced Impairment of Hippocampal LTP In Vivo - Huifang Zhang; Yingchao Han; Ling Zhang; Xiaofang Jia; Qiao Niu (Biological Trace Element Research, 2021)

A novel Trichoderma asperellum isolate promoting the growth, detoxification, and antifungal abilities of Arabidopsis thaliana seedlings under Fusarium oxysporum toxin stress - Yibo An; Xinyu Wang; Shida Ji; Jing Han; Yucheng Wang; Ling Ma; Zhihua Liu (Journal of Plant Pathology, 2021)

Maritimibacter alexandrii sp. nov., a New Member of Rhodobacteraceae Isolated from Marine Phycosphere - Xing Wang; Yun Ye; Fei-Fei Xu; Yu-Han Duan; Peng-Fei Xie; Qiao Yang; Xiao-Ling Zhang (Current Microbiology, 2021)

Tumor Microenvironment Modulating Functional Nanoparticles for Effective Cancer Treatments - Seungyong Shin; Jiyoung Lee; Jieun Han; Fangyuan Li; Daishun Ling; Wooram Park (Tissue Engineering and Regenerative Medicine, 2021)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Dynamic Regulation of Ions and Amino Acids in Adult Asian Hard Clams Meretrix lusoria Upon Hyperosmotic Salinity - Chia-Hao Lin; Po-Ling Yeh; Yu-Chun Wang; Tsung-Han Lee (Frontiers in Marine Science, 2021)
The dynamic regulation of ions and amino acids in the gills and mantle of the Asian hard clam, Meretrix lusoria , following the exposure to a hyperosmotic environment was hitherto unclear. The present study revealed that the osmolality as well as the Na + and Cl – concentrations in the hemolymph were significantly increased 3 h after transferring the clams from an environment with the salinity of their natural habitat (brackish water; BW; 20‰) to one with hyperosmotic salinity (seawater; 35‰). In addition, we found that the specific activities of Na + /K + -ATPase, a key enzyme that plays a significant role in cell osmoregulation, in the gills and mantle of clams were significantly increased at 72 and 12 h post-transfer, respectively, during acclimation to hyperosmotic salinity. Similarly, the contents of free amino acids (FAAs) such as taurine, alanine, and glycine were significantly elevated during hyperosmotic salinity acclimation. Previous research indicates that taurine is the most abundant FAA in the gills and mantles of Asian hard clams and that the taurine transporter (TAUT) plays an important role in taurine accumulation. The present study showed that TAUT mRNA and protein expression were significantly and transiently increased in the mantle of Asian hard clams following exposure to seawater; although the expression of TAUT mRNA in the gills of Asian hard clams was also transiently stimulated by exposure to hyperosmotic salinity, the relative TAUT protein abundance decreased only at later stages. Accordingly, the findings of this study improve our understanding of the dynamic processes of ion and amino acid regulation in the peripheral tissues of bivalves under hyperosmotic stress.

Impacts of pH on the Fitness and Immune System of Pacific White Shrimp - Veran Weerathunga; Wei-Jen Huang; Sam Dupont; Hsueh-Han Hsieh; Nathangi Piyawardhana; Fei-Ling Yuan; Jhe-Syuan Liao; Chia-Yu Lai; Wei-Ming Chen; Chin-Chang Hung (Frontiers in Marine Science, 2021)
The atmospheric partial pressure of CO 2 ( p CO 2 ) has been increasing dramatically since the beginning of the industrial revolution and about 30% of the CO 2 produced by anthropogenic activities was absorbed by the ocean. This led to a perturbation of the seawater carbonate chemistry resulting in a decrease of the average surface ocean pH by 0.1 and termed ocean acidification (OA). Projections suggest that p CO 2 may reach 900 μatm by the end of the twenty-first century lowering the average pH of the surface ocean by 0.4 units. The negative impacts of OA on many species of marine invertebrates such as mollusks, echinoderms, and crustaceans are well documented. However, less attention has been paid to the impacts of low pH on fitness and immune system in crustaceans. Here, we exposed Pacific white shrimps to 3 different pHs (nominal pH 8.0, 7.9, and 7.6) over a 100-days experiment. We found that, even though there were no significant effects on fitness parameters (survival, growth and allometries between length and weight), some immune markers were modified under low pH. A significant decrease in total hemocyte count and phenoloxidase activity was observed in shrimps exposed to pH 7.6 as compared to pH 8.0; and phagocytosis rate significantly decreased with decreasing pH. A significant increase in superoxide production was also observed at pH 7.6 as compared to pH 8.0. All these results suggest that a 100-days exposure to pH 7.6 did not have a direct effect on fitness but lead to a modulation of the immune response.

Soil heavy metal pollution source analysis based on the land use type in Fengdong District of Xi’an, China - Huijuan Hu; Ling Han; Liangzhi Li; Haiyang Wang; Tangqi Xu (Environmental Monitoring and Assessment, 2021)

Circular RNA circ_Cabin1 promotes DNA damage in multiple mouse organs via inhibition of non-homologous end-joining repair upon PM2.5 exposure - Huixian Zeng; Meizhen Li; Qiuhan Hua; Yufei Liu; Yueting Shao; Qinqin Diao; Yihui Ling; Han Zhang; Miaoyun Qiu; Jialu Zhu; Xun Li; Rong Zhang; et al. (Archives of Toxicology, 2021)

Efficiently immobilizing uranium (VI) by oxidized carbon foam - Hongliang Bao; Chunyu Xie; Ling Han; Zenghui Yue; Yuan Qian; Linjuan Zhang; Zi-Jian Li; Huangjie Lu; Jian Lin; Jian-Qiang Wang (Environmental Science and Pollution Research, 2021)

Hourly remote sensing monitoring of harmful algal blooms (HABs) in Taihu Lake based on GOCI images - Hongye Cao; Ling Han (Environmental Science and Pollution Research, 2021)

Resolvin D1 Attenuates Innate Immune Reactions in Experimental Subarachnoid Hemorrhage Rat Model - Guang-Jie Liu; Tao Tao; Xiang-Sheng Zhang; Yue Lu; Ling-Yun Wu; Yong-Yue Gao; Han Wang; Hai-Bin Dai; Yan Zhou; Zong Zhuang; Chun-Hua Hang; Wei Li (Molecular Neurobiology, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Regulating CH4, N2O, and NO emissions from an alkaline paddy field under rice–wheat rotation with controlled release N fertilizer - Ting Lan; Heng Zhang; Yong Han; Ouping Deng; Xiaoyan Tang; Ling Luo; Jian Zeng; Guangdeng Chen; Changquan Wang; Xuesong Gao (Environmental Science and Pollution Research, 2021)

Early diagnosis of rabies virus infection by RPA-CRISPR techniques in a rat model - Meishen Ren; Hong Mei; Jiaojiao Zhou; Ming Zhou; Heyou Han; Ling Zhao (Archives of Virology, 2021)

Spatial Analysis of the Fishing Behaviour of Tuna Purse Seiners in the Western and Central Pacific Based on Vessel Trajectory Data - Han Zhang; Sheng-Long Yang; Wei Fan; Hui-Min Shi; San-Ling Yuan (Journal of Marine Science and Engineering, 2021)
The Western and Central Pacific Oceans are the primary operational areas of tuna purse seiners worldwide. Describing and analysing the fishing behaviour of vessels is highly significant for the protection of sustainable tuna resources. This study uses Automatic Identification System (AIS) data of 130 tuna purse seiners from July 2017 to May 2018 and uses data mining methods to identify the operating status of tuna purse seiners; describes the spatial characteristics of fishing intensity and the distribution of hot spots; and analyses vessel spatial characteristics to describe their fishing behaviour. The results show that the tuna purse seiner speed has a marked bimodal distribution, which corresponds to high-speed transiting and low-speed seine operation. Additionally, from July to September 2017, the amount of fishing effort invested by tuna purse seiners was lower than that in other months. The tuna purse seiner activity range includes 120° E–60° W, 30° S–30° N, and the activities for fish and seine operations are primarily concentrated at 140° E–150° W, 15° S–15° N. There are differences between the space for fishing search operations and space where fishing events took place in each month. Spatial analysis shows that the high-speed transiting fishing effort map covers a large area, while seine fishing covers a small area. The global spatial autocorrelation analysis shows that the fishing effort devoted to searching for fish stocks has a spatial distribution pattern of aggregation and close aggregation. The results of a hot-spot analysis show that the hot spots on a heat map for finding fish, which are closely spatially clustered, correspond to vessels searching for fish concentration areas and seine operation areas. Correlation testing shows that under a 5° × 5° grid, there is a high positive correlation between the fishing effort invested in finding fish stocks and the yield data, nets (r > 0.8), and a moderate correlation with catch per unit of effort(CPUE) (r > 0.3). Based on vessel behaviour, the location of the fish school can be directly determined, and the distribution of fish clusters and fishing grounds can be predicted. This study can aid in managing tuna purse seiners in the Western and Central Pacific Oceans and analysing changes in fishery resources.

2,3,5,6-Tetramethylpyrazine protects retinal photoreceptors against endoplasmic reticulum stress by modulating ATF4-mediated inhibition of PRP aggregation - Hao Huang; Xiaobo Zhu; Hao Cheng; Xielan Kuang; Chongde Long; Xizhi Deng; Yuxiu Zou; Han Zhang; Yue Xing; Xiangtian Ling; Renchun Wang; Han Tang; et al. (Journal of Molecular Medicine, 2021)

New 23, 27-dihydroxy-oleanane-type triterpenoid saponins from Anemone Raddeana Regel - Chongning Lv; Ying Zhao; Bin Zhao; Ling Han; Jincai Lu (Natural Product Research, 2021)

The reduction of lipid-sourced energy production caused by ATGL inhibition cannot be compensated by activation of HSL, autophagy, and utilization of other nutrients in fish - Si-Lan Han; Yan Liu; Samwel M. Limbu; Li-Qiao Chen; Mei-Ling Zhang; Zhen-Yu Du (Fish Physiology and Biochemistry, 2021)

miR-375-3p contributes to hypoxia-induced apoptosis by targeting forkhead box P1 (FOXP1) and Bcl2 like protein 2 (Bcl2l2) in rat cardiomyocyte h9c2 cells - Yuefan Li; Xiaofei Li; Ling Wang; Na Han; Gang Yin (Biotechnology Letters, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Method for fast staining and obtaining high-magnification and high-resolution cell images of Nicotiana benthamiana - Yuanyuan Jiang; Jiangrong Peng; Yunpeng Cao; Zhiqiang Han; Ling Zhang; Wenbing Su; Shunquan Lin; Yuan Yuan; Bin Wang; Xianghui Yang; Zhike Zhang (Physiology and Molecular Biology of Plants, 2021)

Updating and identifying three novel variants of the CARD14 gene in Chinese Han patients with psoriasis - Yike Huang; Chenhui Zhang; Lu Tao; Jiaqing Zhou; Jie Zhu; Kexiang Yan; Ling Han; Qiong Huang; Jinxiu Shi; Zhenghua Zhang (Journal of Genetics, 2020)

Cloning and Characterization of a Ginsenoside-Hydrolyzing α-L-Arabinofuranosidase, CaAraf51, From Cellulosimicrobium aquatile Lyp51 - Sha-Sha Zuo; Yu-Chen Wang; Ling Zhu; Jiang-Yuan Zhao; Ming-Gang Li; Xiu-Lin Han; Meng-Liang Wen (Current Microbiology, 2020)

Transcriptome Analysis of the Acid Stress Response of Desulfovibrio vulgaris ATCC 7757 - Hang Yu; Zhiqiang Jiang; Yueer Lu; Xurong Yao; Chongyin Han; Ying Ouyang; Han Wang; Chuling Guo; Fei Ling; Zhi Dang (Current Microbiology, 2020)

Standardized object-based dual CNNs for very high-resolution remote sensing image classification and standardization combination effect analysis - Liangzhi Li; Ling Han; Huijuan Hu; Zhiheng Liu; Hongye Cao (International Journal of Remote Sensing, 2020)

The Joubert Syndrome Gene arl13b is Critical for Early Cerebellar Development in Zebrafish - Jian Zhu; Han-Tsing Wang; Yu-Rong Chen; Ling-Ya Yan; Ying-Ying Han; Ling-Yan Liu; Ying Cao; Zhi-Zhi Liu; Hong A. Xu (Neuroscience Bulletin, 2020)
Joubert syndrome is characterized by unique malformation of the cerebellar vermis. More than thirty Joubert syndrome genes have been identified, including ARL13B . However, its role in cerebellar development remains unexplored. We found that knockdown or knockout of arl13b impaired balance and locomotion in zebrafish larvae. Granule cells were selectively reduced in the corpus cerebelli, a structure homologous to the mammalian vermis. Purkinje cell progenitors were also selectively disturbed dorsomedially. The expression of atoh1 and ptf1 , proneural genes of granule and Purkinje cells, respectively, were selectively down-regulated along the dorsal midline of the cerebellum. Moreover, wnt1 , which is transiently expressed early in cerebellar development, was selectively reduced. Intriguingly, activating Wnt signaling partially rescued the granule cell defects in arl13b mutants. These findings suggested that Arl13b is necessary for the early development of cerebellar granule and Purkinje cells. The arl13b -deficient zebrafish can serve as a model organism for studying Joubert syndrome.

Extracellular ATP affects cell viability, respiratory O2 uptake, and intracellular ATP production of tobacco cell suspension culture in response to hydrogen peroxide-induced oxidative stress - Qin-zheng Hou; Yu-pei Wang; Bao-qiang Fan; Kun Sun; Jun-yu Liang; Han-qing Feng; Ling-yun Jia (Biologia, 2020)

Responses of Primary Afferent Fibers to Acupuncture-Like Peripheral Stimulation at Different Frequencies: Characterization by Single-Unit Recording in Rats - Ran Huo; Song-Ping Han; Feng-Yu Liu; Xiao-Jing Shou; Ling-Yu Liu; Tian-Jia Song; Fu-Jun Zhai; Rong Zhang; Guo-Gang Xing; Ji-Sheng Han (Neuroscience Bulletin, 2020)

Classification of Alzheimer’s Disease from 18F-FDG and 11C-PiB PET Imaging Biomarkers Using Support Vector Machine - Bang-Hung Yang; Jyh-Cheng Chen; Wen-Hsiang Chou; Wen-Sheng Huang; Jong-Ling Fuh; Ren‑Shyan Liu; Cheng-Han Wu (Journal of Medical and Biological Engineering, 2020)

Impaired peroxisomal fat oxidation induces hepatic lipid accumulation and oxidative damage in Nile tilapia - Yan Liu; Si-Lan Han; Yuan Luo; Ling-Yu Li; Li-Qiao Chen; Mei-Ling Zhang; Zhen-Yu Du (Fish Physiology and Biochemistry, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Potential of stem cell therapy in intracerebral hemorrhage - Abel Po-Hao Huang; Yi-Hua Hsu; Meng-Shiue Wu; Hsin-Han Tsai; Chia-Yi Su; Thai-Yen Ling; Shan-hui Hsu; Dar-Ming Lai (Molecular Biology Reports, 2020)

Impacts of genomic research on soybean improvement in East Asia - Man-Wah Li; Zhili Wang; Bingjun Jiang; Akito Kaga; Fuk-Ling Wong; Guohong Zhang; Tianfu Han; Gyuhwa Chung; Henry Nguyen; Hon-Ming Lam (Theoretical and Applied Genetics, 2020)
It has been commonly accepted that soybean domestication originated in East Asia. Although East Asia has the historical merit in soybean production, the USA has become the top soybean producer in the world since 1950s. Following that, Brazil and Argentina have been the major soybean producers since 1970s and 1990s, respectively. China has once been the exporter of soybean to Japan before 1990s, yet she became a net soybean importer as Japan and the Republic of Korea do. Furthermore, the soybean yield per unit area in East Asia has stagnated during the past decade. To improve soybean production and enhance food security in these East Asian countries, much investment has been made, especially in the breeding of better performing soybean germplasms. As a result, China, Japan, and the Republic of Korea have become three important centers for soybean genomic research. With new technologies, the rate and precision of the identification of important genomic loci associated with desired traits from germplasm collections or mutants have increased significantly. Genome editing on soybean is also becoming more established. The year 2019 marked a new era for crop genome editing in the commercialization of the first genome-edited plant product, which is a high-oleic-acid soybean oil. In this review, we have summarized the latest developments in soybean breeding technologies and the remarkable progress in soybean breeding-related research in China, Japan, and the Republic of Korea.

Assessing dietary exposure risk to neonicotinoid residues among preschool children in regions of Taiwan - Min-Pei Ling; Huai-An Hsiao; Szu-Chieh Chen; Wei-Yu Chen; Wei-Chun Chou; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Hsing-Chieh Lin; Chi-Yun Chen; Tien-Hsuan Lu; Chung-Min Liao (Environmental Science and Pollution Research, 2020)

Association between tooth loss and gray matter volume in cognitive impairment - Chia-Shu Lin; Hsiao-Han Lin; Shin-Woei Fann; Wei-Ju Lee; Ming-Lun Hsu; Shuu-Jiun Wang; Jong-Ling Fuh (Brain Imaging and Behavior, 2020)

Synthesis and structure anti-inflammatory activity relationships studies of andrographolide derivatives - Ling Liu; Yan Yan; Lihua Zheng; Haiyan Jia; Guang Han (Natural Product Research, 2020)

Mechanism of phosphorus mobility in sediments with larval (Propsilocerus akamusi) bioturbation - Wenming Yan; Musong Chen; Ling Liu; Tingfeng Wu; Yi Zhang; Han Wang; Xigang Xing; Kongming Fan (Environmental Science and Pollution Research, 2020)

Neogenkwanine I from the flower buds of Daphne genkwa with its stereostructure confirmation using quantum calculation profiles and antitumor evaluation - Xue-Wen Hou; Shuang Han; Ying-Ying Zhang; Hai-Bi Su; Pin-Yi Gao; Ling-Zhi Li; Shao-Jiang Song (Natural Product Research, 2020)

Inhibition of intestinal lipases alleviates the adverse effects caused by high-fat diet in Nile tilapia - Yu-Xue Zhang; Zhe-Yue Jiang; Si-Lan Han; Ling-Yu Li; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Fish Physiology and Biochemistry, 2020)

Effect of dissolved organic matters and inorganic ions on TiO2 photocatalysis of diclofenac: mechanistic study and degradation pathways - Ling Gao; Beihai Zhou; Fei Wang; Rongfang Yuan; Huilun Chen; Xiaomin Han (Environmental Science and Pollution Research, 2020)

Geochemical behaviors of antimony in mining-affected water environment (Southwest China) - Ling Li; Han Tu; Shui Zhang; Linna Wu; Min Wu; Yang Tang; Pan Wu (Environmental Geochemistry and Health, 2019)

Epigenetic modification enhances ergot alkaloid production of Claviceps purpurea - Jing-Jing Chen; Meng-Yao Han; Ting Gong; Yun-Ming Qiao; Jin-Ling Yang; Ping Zhu (Biotechnology Letters, 2019)

Multi‐model analysis of climate impacts on plant photosynthesis in China during 2000–2015 - Hao Yan; Shao‐Qiang Wang; Jun‐Bang Wang; Yun Cao; Ling‐Ling Xu; Men‐Xin Wu; Lu Cheng; Liu‐Xi Mao; Feng‐Hua Zhao; Xian‐Zhou Zhang; Yun‐Fen Liu; Yan‐Fen Wang; et al. (International Journal of Climatology, 2019)
Differences, arising from differences in gross primary production (GPP) model structures and driving forces, have fuelled arguments concerning interannual changes of GPP in China since 2000. To better investigate the interannual variability of GPP and its covariance with climate factors in China, this study adopted a multi‐model analysis based on three GPP models (i.e., Terrestrial Ecosystem Carbon flux model [TEC], Breathing Earth System Simulator model [BESS], and MOD17 GPP model). The results show that annual GPP in China increased by 0.021–0.057 Pg C year −1 from 2000 to 2015 attributable to atmospheric‐CO 2 fertilization effects and favourable climate change, that is, increasing precipitation ( P r ) and temperature ( T a ). However, northern China and southern China had a large difference in the amplitude of these GPP changes; annual GPP increased by 0.017–0.039 Pg C year −1 in northern China but only 0.001–0.018 Pg C year −1 in southern China. Northern China and southern China occupy contrasting climate zones and this contrast produced different interannual variability of GPP through different mechanisms. Northern China has a dry climate with GPP changes sensitive to P r . As a result, more P r along with higher T a in northern China produced the strong uptrend of GPP from 2000 to 2015. In contrast, southern China has a wet climate with its GPP sensitive to solar radiation and T a . For the interval of 2000–2015, decreasing radiation plus drought exerted a negative influence on GPP in southern China. This study highlights the diverse mechanisms in which climate change affects GPP in dry and wet climate zones. A robust multi‐model analysis is preferred to reduce uncertainties arising from a single GPP model and its driving data.

Rapid adaptation of Brachionus angularis (Rotifera) to invasion by Brachionus calyciflorus - Yi-Long Xi; Ke-Qiang Huang; Ling Pan; Han Zhu; Ya-Li Ge; Xin-Li Wen; Xian-Ling Xiang (Hydrobiologia, 2019)

Overexpression of AtAGT1 promoted root growth and development during seedling establishment - Rui Wang; Lin Yang; Xiaofang Han; Yuhong Zhao; Ling Zhao; Beibei Xiang; Yerong Zhu; Yanling Bai; Yong Wang (Plant Cell Reports, 2019)

Exosomes from patients with Parkinson’s disease are pathological in mice - Chao Han; Nian Xiong; Xingfang Guo; Jinsha Huang; Kai Ma; Ling Liu; Yun Xia; Yan Shen; Jie Li; Haiyang Jiang; Luxi Wang; Shiyi Guo; et al. (Journal of Molecular Medicine, 2019)

Development of a loop-mediated isothermal amplification for rapid diagnosis of Aphelenchoides ritzemabosi - Dong-Wei Wang; Chun-Ling Xu; Zong-Shi Bai; Jun-Yi Li; Yu-Chun Han; Li-Rong Zhao; Hui Xie (European Journal of Plant Pathology, 2019)

DNA methylation and mRNA expression of COL6A3 in antler mesenchyme of female and male reindeer - Jian-Cheng Zhai; Ruo-Bing Han; Sheng-Nan Wang; Qiang-Hui Wang; Yan-Ling Xia; Wei-Shi Liu; Ya-Jie Yin; He-Ping Li (Genes & Genomics, 2019)

A metabolic investigation of anticancer effect of G. glabra root extract on nasopharyngeal carcinoma cell line, C666-1 - Chaopan Zheng; Ling Han; Shihai Wu (Molecular Biology Reports, 2019)

Measurement of urinary arsenic profiles and DNA hypomethylation in a case–control study of urothelial carcinoma - Chi-Jung Chung; Hui-Ling Lee; Chao-Hsiang Chang; Han Chang; Chiu-Shong Liu; Wei-Ting Jung; Huei-Ju Liu; Saou-Hsing Liou; Mu-Chi Chung; Yu-Mei Hsueh (Archives of Toxicology, 2019)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

QTL mapping for maize starch content and candidate gene prediction combined with co-expression network analysis - Feng Lin; Ling Zhou; Bing He; Xiaolin Zhang; Huixue Dai; Yiliang Qian; Long Ruan; Han Zhao (Theoretical and Applied Genetics, 2019)

A structural and data-driven approach to engineering a plant cytochrome P450 enzyme - Dawei Li; Yongshuo Ma; Yuan Zhou; Junbo Gou; Yang Zhong; Lingling Zhao; Lida Han; Sergey Ovchinnikov; Ling Ma; Sanwen Huang; Per Greisen; Yi Shang (Science China Life Sciences, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

GIS-based landslide susceptibility mapping using hybrid integration approaches of fractal dimension with index of entropy and support vector machine - Ting-yu Zhang; Ling Han; Heng Zhang; Yong-hua Zhao; Xi-an Li; Lei Zhao (Journal of Mountain Science, 2019)

Pseudofrancisella aestuarii gen. nov., sp. nov., a novel member of the family Francisellaceae isolated from estuarine seawater - Min-Ling Zheng; Jian-Yu Jiao; Lei Dong; Ming-Xian Han; Liang-Hui Li; Min Xiao; Cha Chen; Ping-Hua Qu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Role of SIRT1 in hematologic malignancies - Fei-teng Huang; Jie Sun; Lei Zhang; Xin He; Ying-hui Zhu; Hao-jie Dong; Han-ying Wang; Lei Zhu; Jing-ying Zou; Jin-wen Huang; Ling Li (Journal of Zhejiang University-SCIENCE B, 2019)

Epidemiological trends and virological traits of hepatitis B virus infection in pregnant women and neonates - Ting-Ting Peng; Qiu-E Cai; Min Yang; Shao-Ping Chen; Feng Chen; Miao Wang; Ling Peng; Gary Wong; Chen-Guang Shen; Wen-Bing Cheng; Sai-Yun Liu; Ya-Bai Peng; et al. (Archives of Virology, 2019)

Skinfold thickness for rivastigmine patch application in Alzheimer’s disease - Ping-Song Chou; Kai-Ming Jhang; Ling-Chun Huang; Wen-Fu Wang; Yuan-Han Yang (Psychopharmacology, 2019)

Expression Profiling of Notch Signalling Pathway and Gamma-Secretase Activity in the Brain of Ts1Cje Mouse Model of Down Syndrome - Hadri Hadi Yusof; Han-Chung Lee; Eryse Amira Seth; Xiangzhong Wu; Chelsee A. Hewitt; Hamish S Scott; Pike-See Cheah; Yue-Ming Li; De-Ming Chau; King-Hwa Ling (Journal of Molecular Neuroscience, 2019)

Extracellular ATP released by copper stress could act as diffusible signal in alleviating the copper stress-induced cell death - Ling-Yun Jia; Jing-Yue Bai; Kun Sun; Rong-fang Wang; Han-Qing Feng (Protoplasma, 2019)

A Literature Review of Blood-Disseminated P. marneffei Infection and a Case Study of this Infection in an HIV-Negative Child with Comorbid Eosinophilia - Xiu-jing Han; Dan-hong Su; Jian-yun Yi; Ya-wei Zou; Yu-ling Shi (Mycopathologia, 2019)

Effects of biogas residues containing antibiotics on soil enzyme activity and lettuce growth - Jiancong Han; Congguang Zhang; Jia Cheng; Fei Wang; Ling Qiu (Environmental Science and Pollution Research, 2019)

Macrophage-derived CCL18 promotes osteosarcoma proliferation and migration by upregulating the expression of UCA1 - Yang Su; Yan Zhou; Yuan-jue Sun; Ya-Ling Wang; Jun-yi Yin; Yu-jing Huang; Jian-jun Zhang; Ai-na He; Kun Han; Hui-zhen Zhang; Yang Yao; Xiao-Bin Lv; et al. (Journal of Molecular Medicine, 2019)

Identification of QTL regions for seedling root traits and their effect on nitrogen use efficiency in wheat (Triticum aestivum L.) - Xiaoli Fan; Wei Zhang; Na Zhang; Mei Chen; Shusong Zheng; Chunhua Zhao; Jie Han; Jiajia Liu; Xilan Zhang; Liqiang Song; Jun Ji; Xigang Liu; et al. (Theoretical and Applied Genetics, 2018)

Cortical Inflammation is Increased in a DSS-Induced Colitis Mouse Model - Ying Han; Tong Zhao; Xiang Cheng; Ming Zhao; Sheng-Hui Gong; Yong-Qi Zhao; Hai-Tao Wu; Ming Fan; Ling-Ling Zhu (Neuroscience Bulletin, 2018)

Low root/shoot (R/S) biomass ratio can be an indicator of low cadmium accumulation in the shoot of Chinese flowering cabbage (Brassica campestris L. ssp. chinensis var. utilis Tsen et Lee) cultivars - Zhi-Min Xu; Xiu-Qin Mei; Ling Tan; Qu-Sheng Li; Li-Li Wang; Bao-Yan He; Shi-Hong Guo; Chu Zhou; Han-Jie Ye (Environmental Science and Pollution Research, 2018)

Selective adsorption and separation of illegal cationic dyes from foodstuffs with anionic polyelectrolyte functionalised metal-organic frameworks - Xue Wang; Hui-Ling Duan; Shi-Yao Ma; Jun Wang; Han-Ying Zhan; Zhi-Qi Zhang (Food Additives & Contaminants: Part A, 2018)

Microsatellite records for volume 10, issue 3 - Ling Ding; Dandan Gao; Jie Han; Zhihong Liu; Tao Pan; Luye Shi; Xiujun Sun; Zhong-lou Sun; Hui Wang; Biao Wu; Gui-you Wu; Yao Xu; et al. (Conservation Genetics Resources, 2018)

Prognostic significance of combining high mobility group Box-1 and OV-6 expression in hepatocellular carcinoma - Jihui Zhu; Han Yu; Shuzhen Chen; Pinghua Yang; Zihui Dong; Yan Ling; Hao Tang; Shilei Bai; Wen Yang; Liang Tang; Feng Shen; Hongyang Wang; et al. (Science China Life Sciences, 2018)

Negative regulation of MAVS-mediated innate immune response by ASC - Yue Han; Xiang He; Congwen Wei; Ting Song; Ling Zou; Zihui Li; Jiazhou Ye; Lunan Qi; Lequn Li; Hui Zhong; Feixiang Wu (Molecular and Cellular Biochemistry, 2018)

Tacrine(10)-hupyridone, a dual-binding acetylcholinesterase inhibitor, potently attenuates scopolamine-induced impairments of cognition in mice - Huixin Chen; Siying Xiang; Ling Huang; Jiajia Lin; Shengquan Hu; Shing-Hung Mak; Chuang Wang; Qinwen Wang; Wei Cui; Yifan Han (Metabolic Brain Disease, 2018)

Historical Records and Source Apportionment of Polycyclic Aromatic Hydrocarbons Over the Past 100 Years in Dianchi Lake, a Plateau Lake in Southwest China - Xiaohua Ma; Xiuxiu Han; Quanliang Jiang; Changchun Huang; Tao Huang; Hao Yang; Ling Yao (Archives of Environmental Contamination and Toxicology, 2018)

Novel antidepressant effects of Paeonol alleviate neuronal injury with concomitant alterations in BDNF, Rac1 and RhoA levels in chronic unpredictable mild stress rats - Xiu-Ling Zhu; Jing-Jing Chen; Fei Han; Chuan Pan; Ting-Ting Zhuang; Ya-Fei Cai; Ya-Ping Lu (Psychopharmacology, 2018)

Classifying clinical notes with pain assessment using machine learning - Samah Jamal Fodeh; Dezon Finch; Lina Bouayad; Stephen L. Luther; Han Ling; Robert D. Kerns; Cynthia Brandt (Medical & Biological Engineering & Computing, 2018)

Cortical thickness reductions associate with abnormal resting-state functional connectivity in non-neuropsychiatric systemic lupus erythematosus - Chen Niu; Xiangliang Tan; Xiaojin Liu; Kai Han; Meiqi Niu; Jun Xu; Ling Zhao; Yuankui Wu; Feng Deng; Qin Huang; Xiaoyan Wu; Huiyuan Huang; et al. (Brain Imaging and Behavior, 2018)

Ideal cardiovascular health and incidence of atherosclerotic cardiovascular disease among Chinese adults: the China-PAR project - Chao Han; Fangchao Liu; Xueli Yang; Jichun Chen; Jianxin Li; Jie Cao; Ying Li; Chong Shen; Ling Yu; Zhendong Liu; Xianping Wu; Liancheng Zhao; et al. (Science China Life Sciences, 2018)

Repetitive transcranial magnetic stimulation inhibits Sirt1/MAO-A signaling in the prefrontal cortex in a rat model of depression and cortex-derived astrocytes - Zheng-wu Peng; Fen Xue; Cui-hong Zhou; Rui-guo Zhang; Ying Wang; Ling Liu; Han-fei Sang; Hua-ning Wang; Qing-rong Tan (Molecular and Cellular Biochemistry, 2018)

Early diagnosis of acute kidney injury in aged patients undergoing percutaneous coronary intervention - Hong-hua Ye; Gen Shen; Qun Luo; Fang-fang Zhou; Xiao-ling Xie; Chun-yan Wang; Li-na Han (Journal of Zhejiang University-SCIENCE B, 2018)

Structural Characteristics and Functional Properties of Corncob Modified by Hyperbranched Polyamide for the Adsorption of Cr (VI) - Hai Lin; Shaoke Han; Yingbo Dong; Wencui Ling; Yinhai He (Water, Air, & Soil Pollution, 2018)

Unraveling the Mechanisms of Memory Extinction - Shao-Ling Han; Tian-Le Xu (Neuroscience Bulletin, 2018)

Comprehensive transcriptome analyses correlated with untargeted metabolome reveal differentially expressed pathways in response to cell wall alterations - Nathan T. Reem; Han-Yi Chen; Manhoi Hur; Xuefeng Zhao; Eve Syrkin Wurtele; Xu Li; Ling Li; Olga Zabotina (Plant Molecular Biology, 2018)

Alternative oxidase functions in the excess excitation energy-induced resistance to pathogen infection - Qin-zheng Hou; Kun Sun; Ling-yun Jia; Jun-yu Liang; Jia-jia Xie; Li-na Lu; Han-qing Feng; Jing Wen (Biologia, 2018)

Spa therapy (balneotherapy) relieves mental stress, sleep disorder, and general health problems in sub-healthy people - Bei Yang; Qi-zhong Qin; Ling-li Han; Jing Lin; Yu Chen (International Journal of Biometeorology, 2018)

Brain white matter structural networks in patients with non-neuropsychiatric systemic lupus erythematosus - Ling Zhao; Xiangliang Tan; Junjing Wang; Kai Han; Meiqi Niu; Jun Xu; Xiaojin Liu; Xixi Zhao; Miao Zhong; Qin Huang; Yikai Xu; Ruiwang Huang (Brain Imaging and Behavior, 2018)

Metaproteomics of marine viral concentrates reveals key viral populations and abundant periplasmic proteins in the oligotrophic deep chlorophyll maximum of the South China Sea - Zhang‐Xian Xie; Feng Chen; Shu‐Feng Zhang; Ming‐Hua Wang; Hao Zhang; Ling‐Fen Kong; Min‐Han Dai; Hua‐Sheng Hong; Lin Lin; Da‐Zhi Wang (Environmental Microbiology, 2018)
Summary Viral concentrates (VCs), containing bioinformative DNA and proteins, have been used to study viral diversity, viral metagenomics and virus–host interactions in natural ecosystems. Besides viruses, VCs also contain many noncellular biological components including diverse functional proteins. Here, we used a shotgun proteomic approach to characterize the proteins of VCs collected from the oligotrophic deep chlorophyll maximum (DCM) of the South China Sea. Proteins of viruses infecting picophytoplankton, that is, cyanobacteria and prasinophytes, and heterotrophic bacterioplankton, such as SAR11 and SAR116, dominated the viral proteome. Almost no proteins from RNA viruses or known gene transfer agents were detected, suggesting that they were not abundant at the sampling site. Remarkably, nonviral proteins made up about two thirds of VC proteins, including overwhelmingly abundant periplasmic transporters for nutrient acquisition and proteins for diverse cellular processes, that is, translation, energy metabolism and one carbon metabolism. Interestingly, three 56 kDa selenium‐binding proteins putatively involved in peroxide reduction from gammaproteobacteria were abundant in the VCs, suggesting active removal of peroxide compounds at DCM. Our study demonstrated that metaproteomics provides a valuable avenue to explore the diversity and structure of the viral community and also the pivotal biological functions affiliated with microbes in the natural environment.

Ore- and Bio- Geochemical Survey Based on the Landsat Remotely Sensed Data In and Around the Dexing Porphyry Copper-Polymetal Ore-Field, Southeastern China - Bo Zhao; Ling Han; Jianjian Wu; Lei Liu; Tingting Wu; Jürgen Pilz; Fan Yang (Journal of the Indian Society of Remote Sensing, 2018)

First identification of porcine parvovirus 7 in China - Xiulin Xing; Han Zhou; Ling Tong; Yao Chen; Yankuo Sun; Heng Wang; Guihong Zhang (Archives of Virology, 2018)

Changes by cadmium stress in lipid peroxidation and activities of lipoxygenase and antioxidant enzymes in Arabidopsis are associated with extracellular ATP - Qin-zheng Hou; Guang-ji Ye; Rong-fang Wang; Ling-yun Jia; Jun-yu Liang; Han-qing Feng; Jing Wen; Dai-long Shi; Qing-wen Wang (Biologia, 2017)

The N-terminal and central domain of colicin A enables phage lysin to lyse Escherichia coli extracellularly - Guangmou Yan; Jianfang Liu; Qiang Ma; Rining Zhu; Zhimin Guo; Chencheng Gao; Shuang Wang; Ling Yu; Jingmin Gu; Dongliang Hu; Wenyu Han; Rui Du; et al. (Antonie van Leeuwenhoek, 2017)

AnkG hemizygous mice present cognitive impairment and elevated anxiety/depressive-like traits associated with decreased expression of GABA receptors and postsynaptic density protein - Cui Liu; Ling Zhang; Jie Wu; Xiaolong Sui; Yanfeng Xu; Lan Huang; Yunlin Han; Hua Zhu; Yanhong Li; Xiuping Sun; Chuan Qin (Experimental Brain Research, 2017)

Protective effects of paeonol on inflammatory response in IL-1β-induced human fibroblast-like synoviocytes and rheumatoid arthritis progression via modulating NF-κB pathway - Ke-feng Zhai; Hong Duan; Lin Luo; Wen-gen Cao; Fang-kai Han; Ling-ling Shan; Xue-mei Fang (Inflammopharmacology, 2017)

Comparison of SO2 column retrievals from BRD and DOAS algorithms - HuanHuan Yan; XiaoJing Li; WeiHe Wang; XingYing Zhang; LiangFu Chen; Dong Han; Chao Yu; Ling Gao (Science China Earth Sciences, 2017)

Sequential combination of docetaxel with a SHP-1 agonist enhanced suppression of p-STAT3 signaling and apoptosis in triple negative breast cancer cells - Chun-Yu Liu; Kuen-Feng Chen; Tzu-I Chao; Pei-Yi Chu; Chun-Teng Huang; Tzu-Ting Huang; Hsiu-Ping Yang; Wan-Lun Wang; Chia-Han Lee; Ka-Yi Lau; Wen-Chun Tsai; Jung-Chen Su; et al. (Journal of Molecular Medicine, 2017)

miR-30a-5p enhances paclitaxel sensitivity in non-small cell lung cancer through targeting BCL-2 expression - Xiaojie Xu; Shuai Jin; Yongfu Ma; Zhongyi Fan; Zhifeng Yan; Wenchao Li; Qi Song; Wenye You; Zhaohui Lyu; Yeqiong Song; Pingan Shi; Ying Liu; et al. (Journal of Molecular Medicine, 2017)

Plipastatin and surfactin coproduction by Bacillus subtilis pB2-L and their effects on microorganisms - Ling Gao; Jinzhi Han; Hongxia Liu; Xiaoxu Qu; Zhaoxin Lu; Xiaomei Bie (Antonie van Leeuwenhoek, 2017)

Association of folate metabolism gene polymorphisms and haplotype combination with pulmonary embolism risk in Chinese Han population - Xin Li; Ling Weng; Baihe Han; Yingnan Dai; Li Cha; Shujun Yan; Enze Jin (Mammalian Genome, 2017)

Mixture risk assessment due to ingestion of arsenic, copper, and zinc from milkfish farmed in contaminated coastal areas - Yi-Jun Lin; Min-Pei Ling; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Hsien Cheng; Shu-Han You; Wei-Chun Chou; Ming-Chao Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2017)

Study on the apoptosis mediated by cytochrome c and factors that affect the activation of bovine longissimus muscle during postmortem aging - Jiaying Zhang; Qunli Yu; Ling Han; Cheng Chen; Hang Li; Guangxing Han (Apoptosis, 2017)

RBD and Neurodegenerative Diseases - Haiyang Jiang; Jinsha Huang; Yan Shen; Shiyi Guo; Luxi Wang; Chao Han; Ling Liu; Kai Ma; Yun Xia; Jie Li; Xiaoyun Xu; Nian Xiong; et al. (Molecular Neurobiology, 2017)

A study on one-dimensional consolidation of layered structured aquitard soils in a leakage system - An-Feng Hu; Chang-Qing Xia; Hao Wu; Kang-He Xie; Ling-Han Yan (Marine Georesources & Geotechnology, 2017)

Effects of rapid ascent on the heart rate variability of individuals with and without acute mountain sickness - Ming Ling Yih; Fang-Chi Lin; Heng-Sheng Chao; Han-Chen Tsai; Shi-Chuan Chang (European Journal of Applied Physiology, 2017)

Cryopreservation of Jerusalem artichoke cultivars using an improved droplet-vitrification method - Jin-Mei Zhang; Li Han; Xin-Xiong Lu; Gayle M. Volk; Xia Xin; Guang-Kun Yin; Juan-Juan He; Ling Wang; Xiao-Ling Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Salidroside accelerates fracture healing through cell-autonomous and non-autonomous effects on osteoblasts - Xiao Qin Guo; Lin Qi; Jing Yang; Yue Wang; Chuan Wang; Zong Min Li; Ling Li; Ye Qu; Dan Wang; Ze Min Han (Cell and Tissue Research, 2017)

Differences in the high-temperature tolerance of Aphis craccivora (Hemiptera: Aphididae) on cotton and soybean: implications for ecological niche switching among hosts - Lu Zhaozhi; Feng Likai; Gao Guizhen; Gao Ling-Ling; Peng Han; Shashi Sharma; Myron P. Zalucki (Applied Entomology and Zoology, 2017)

Induced Pluripotent Stem Cells in Huntington’s Disease: Disease Modeling and the Potential for Cell-Based Therapy - Ling Liu; Jin-Sha Huang; Chao Han; Guo-Xin Zhang; Xiao-Yun Xu; Yan Shen; Jie Li; Hai-Yang Jiang; Zhi-Cheng Lin; Nian Xiong; Tao Wang (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 4 - Alejandra Paola Ojeda; Alexandre Wagner Silva Hilsdorf; Ana Caroline Leite; Ao-ao Yang; Ayako Izuno; Chongbo He; Chun-ya Zhou; Daisuke Kyogoku; Danilo Caneppele; Dongmei Zhu; Fernando Stopato da Fonseca; Hao Yin; et al. (Conservation Genetics Resources, 2016)

Cytotoxicity and Genotoxicity in Human Embryonic Kidney Cells Exposed to Surface Modify Chitosan Nanoparticles Loaded with Curcumin - Yu Zheng; Yan Chen; Ling-Wei Jin; Han-Yang Ye; Gang Liu (AAPS PharmSciTech, 2016)

Geochemical fingerprints and pebbles zircon geochronology: Implications for the provenance and tectonic setting of Lower Cretaceous sediments in the Zhucheng Basin (Jiaodong peninsula, North China) - JIN-LONG NI; JUN-LAI LIU; XIAO-LING TANG; XIAO-XIAO SHI; HONG ZHANG; SHUAI HAN (Journal of Earth System Science, 2016)

Impacts of rapeseed dregs on Cd availability in contaminated acid soil and Cd translocation and accumulation in rice plants - Wen-Tao Yang; Jiao-Feng Gu; Jia-Ling Zou; Hang Zhou; Qing-Ru Zeng; Bo-Han Liao (Environmental Science and Pollution Research, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Chicken gga-miR-130a targets HOXA3 and MDFIC and inhibits Marek’s disease lymphoma cell proliferation and migration - Bo Han; Ling Lian; Xin Li; Chunfang Zhao; Lujiang Qu; Changjun Liu; Jiuzhou Song; Ning Yang (Molecular Biology Reports, 2016)

Application and comparison of coaxial correlation diagram and hydrological model for reconstructing flood series under human disturbance - Peng-nian Huang; Zhi-jia Li; Qiao-ling Li; Ke Zhang; Han-chen Zhang (Journal of Mountain Science, 2016)

Molecular identification of ‘Candidatus phytoplasma asteris’ related strain (16SrΙ-B) associated with Broussonetia papyrifera in Nanjing, China - Cong-Jin Mei; Qing-Can Wang; Ju-Can Gui; Yan-Ling Ji; Han-Shou Yu (European Journal of Plant Pathology, 2016)

Effects of 4-methylbenzylidene camphor (4-MBC) on neuronal and muscular development in zebrafish (Danio rerio) embryos - Vincent Wai Tsun Li; Mei Po Mirabelle Tsui; Xueping Chen; Michelle Nga Yu Hui; Ling Jin; Raymond H. W. Lam; Richard Man Kit Yu; Margaret B. Murphy; Jinping Cheng; Paul Kwan Sing Lam; Shuk Han Cheng (Environmental Science and Pollution Research, 2016)

Neuroprotection of Sevoflurane Against Ischemia/Reperfusion-Induced Brain Injury Through Inhibiting JNK3/Caspase-3 by Enhancing Akt Signaling Pathway - Xiang-Ru Wen; Yan-Yan Fu; Hong-Zhi Liu; Jian Wu; Xiao-Ping Shao; Xun-Bao Zhang; Man Tang; Yue Shi; Kai Ma; Fang Zhang; Yi-Wen Wang; Hui Tang; et al. (Molecular Neurobiology, 2016)

LDL acts as an opsonin enhancing the phagocytosis of group A Streptococcus by monocyte and whole human blood - Lulei Zhou; Ling Liu; Jinli Yang; Yuxin Li; Wencheng Bai; Na Liu; Wenlong Li; Yumin Gao; Liping Xu; Zhi Liu; Runlin Han (Medical Microbiology and Immunology, 2016)

Valproic Acid Influences MTNR1A Intracellular Trafficking and Signaling in a β-Arrestin 2-Dependent Manner - Ling-juan Hong; Quan Jiang; Sen Long; Huan Wang; Ling-di Zhang; Yun Tian; Cheng-kun Wang; Jing-jing Cao; Rong-rong Tao; Ji-yun Huang; Mei-hua Liao; Ying-mei Lu; et al. (Molecular Neurobiology, 2016)

Arsenic speciation in rice and risk assessment of inorganic arsenic in Taiwan population - Hsiu-Ling Chen; Ching-Chang Lee; Winn-Jung Huang; Han-Ting Huang; Yi-Chen Wu; Ya-Chen Hsu; Yi-Ting Kao (Environmental Science and Pollution Research, 2016)

Cochliomycin A inhibits the larval settlement of Amphibalanus amphitrite by activating the NO/cGMP pathway - Kai-Ling Wang; Gen Zhang; Jin Sun; Ying Xu; Zhuang Han; Ling-Li Liu; Chang-Lun Shao; Qing-Ai Liu; Chang-Yun Wang; Pei-Yuan Qian (Biofouling, 2016)

Cannabinoid CB1 receptor signaling dichotomously modulates inhibitory and excitatory synaptic transmission in rat inner retina - Xiao-Han Wang; Yi Wu; Xiao-Fang Yang; Yanying Miao; Chuan-Qiang Zhang; Ling-Dan Dong; Xiong-Li Yang; Zhongfeng Wang (Brain Structure and Function, 2016)

Myeloid-Specific Blockade of Notch Signaling by RBP-J Knockout Attenuates Spinal Cord Injury Accompanied by Compromised Inflammation Response in Mice - Bei-Yu Chen; Min-Hua Zheng; Yan Chen; Yan-Ling Du; Xiao-Long Sun; Xing Zhang; Li Duan; Fang Gao; Liang Liang; Hong-Yan Qin; Zhuo-Jing Luo; Hua Han (Molecular Neurobiology, 2015)

CTRP3 attenuates post-infarct cardiac fibrosis by targeting Smad3 activation and inhibiting myofibroblast differentiation - Dan Wu; Hong Lei; Jin-Yu Wang; Cheng-Lin Zhang; Han Feng; Feng-Ying Fu; Li Li; Li-Ling Wu (Journal of Molecular Medicine, 2015)

Morphology-dependent antimicrobial activity of Cu/CuxO nanoparticles - Lu Xiong; Zhong-Hua Tong; Jie-Jie Chen; Ling-Li Li; Han-Qing Yu (Ecotoxicology, 2015)

Detection and identification of ‘Candidatus Phytoplasma ziziphi’ associated with violet orychophragmus yellow dwarf disease in China - Qing-Can Wang; Cong-Jin Mei; Ju-Can Gui; Yan-Ling Ji; Han-Shou Yu (Journal of General Plant Pathology, 2015)

Low-Toxicity Diindol-3-ylmethanes as Potent Antifouling Compounds - Kai-Ling Wang; Ying Xu; Liang Lu; Yongxin Li; Zhuang Han; Jun Zhang; Chang-Lun Shao; Chang-Yun Wang; Pei-Yuan Qian (Marine Biotechnology, 2015)

Characteristics of hopanoid hydrocarbons in ambient PM10 and motor vehicle emissions and coal ash in Taiyuan, China - Feng Han; Junji Cao; Lin Peng; Huiling Bai; Dongmei Hu; Ling Mu; Xiaofeng Liu (Environmental Geochemistry and Health, 2015)

miR-26a enhances autophagy to protect against ethanol-induced acute liver injury - Weidong Han; Xianghui Fu; Jiansheng Xie; Zhipeng Meng; Ying Gu; Xichun Wang; Ling Li; Hongming Pan; Wendong Huang (Journal of Molecular Medicine, 2015)

Direct cloning, expression of a thermostable xylanase gene from the metagenomic DNA of cow dung compost and enzymatic production of xylooligosaccharides from corncob - Ming-zhe Sun; Hong-chen Zheng; Ling-cai Meng; Jun-she Sun; Hui Song; Yun-juan Bao; Hai-sheng Pei; Zheng Yan; Xiu-qing Zhang; Jing-sheng Zhang; Yi-han Liu; Fu-ping Lu (Biotechnology Letters, 2015)

Comparisons of two types of teleostean pseudobranchs, silver moony (Monodactylus argenteus) and tilapia (Oreochromis mossambicus), with salinity-dependent morphology and ion transporter expression - Sheng-Hui Yang; Chao-Kai Kang; Yau-Chung Hu; Ling-Chia Yen; Shu-Chuan Tsai; Yueh-Ling Hsieh; Tsung-Han Lee (Journal of Comparative Physiology B, 2015)

Research on Chinese public finance in response to domestic natural disasters - Yong-ling Zhang; Yan-nan Ma; An Chen; Yu-han Lin (Natural Hazards, 2015)

Effect of Propofol on the Expression of MMP-9 and Its Relevant Inflammatory Factors in Brain of Rat with Intracerebral Hemorrhage - Dongji Han; Shiyong Li; Qiuju Xiong; Ling Zhou; Ailin Luo (Cell Biochemistry and Biophysics, 2015)

Rifampicin Loaded Mannosylated Cationic Nanostructured Lipid Carriers for Alveolar Macrophage-specific Delivery - Xu Song; Qing Lin; Ling Guo; Yao Fu; Jianfeng Han; Huan Ke; Xun Sun; Tao Gong; Zhirong Zhang (Pharmaceutical Research, 2015)

The 3D-QSAR and pharmacophore studies of pyrimidine derivatives as HCV replication (replicase) inhibitor - Yan Li; Dechao Wang; Yinfeng Yang; Jingxiao Zhang; Chunxiao Han; Jinghui Wang; Weimin Gao; Guomei Zhang; Xiaoqian Sun; Bingchen Wang; Shuwei Zhang; Ling Yang (Medicinal Chemistry Research, 2015)

Smooth muscle 22α facilitates angiotensin II-induced signaling and vascular contraction - Xiao-Li Xie; Xi Nie; Jun Wu; Fan Zhang; Li-Li Zhao; Yan-Ling Lin; Ya-Juan Yin; Hui Liu; Ya-Nan Shu; Sui-Bing Miao; Huan Li; Peng Chen; et al. (Journal of Molecular Medicine, 2015)

Glycogen synthase kinase 3β inhibition promotes human iTreg differentiation and suppressive function - Yongxiang Xia; Han Zhuo; Yunjie Lu; Lei Deng; Runqiu Jiang; Long Zhang; Qin Zhu; Liyong Pu; Xuehao Wang; Ling Lu (Immunologic Research, 2015)

Anti-inflammatory Mechanism of Bone Marrow Mesenchymal Stem Cell Transplantation in Rat Model of Spinal Cord Injury - Dongji Han; Chenglong Wu; Qiuju Xiong; Ling Zhou; Yuke Tian (Cell Biochemistry and Biophysics, 2015)

Increased Expression of p-Akt correlates with Chronic Allograft Nephropathy in a Rat Kidney Model - Li-Na Zhou; Ning Wang; Yang Dong; Yiqin Zhang; Hequn Zou; Qingqin Li; Yangling Shi; Ling Chen; Wenying Zhou; Conghui Han; Yuxin Wang (Cell Biochemistry and Biophysics, 2015)

Pedogenetic evolution of clay minerals and agricultural implications in three paddy soil chronosequences of south China derived from different parent materials - Guang-Zhong Han; Gan-Lin Zhang; De-Cheng Li; Jin-Ling Yang (Journal of Soils and Sediments, 2015)

Speciation and phytoavailability of cadmium in soil treated with cadmium-contaminated rice straw - Shuai Wang; Dao-You Huang; Qi-Hong Zhu; Han-Hua Zhu; Shou-Long Liu; Zun-Chang Luo; Xiao-Ling Cao; Ji-Yu Wang; Zhong-Xiu Rao; Xin Shen (Environmental Science and Pollution Research, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Isocitrate lyase is required for urediniospore germination of Puccinia striiformis f. sp. tritici - Jie Liu; Qiu-Ling Wang; Qing Chang; Li-Na Han; Guo-Liang Pei; Yue-Qing Xue; Lu-Meng Jia; Kun Zhang; Yuan-Yuan Duan; Zhen-Sheng Kang (Molecular Biology Reports, 2014)

Genetic relationships among buckwheat (Fagopyrum) species from southwest China based on chloroplast and nuclear SSR markers - ZIZHONG TANG; LING HUANG; JUNBO GOU; HUI CHEN; XUEYI HAN (Journal of Genetics, 2014)

Parallel simulation of groundwater flow in the North China Plain - Tangpei Cheng; Jingli Shao; Yali Cui; Zeyao Mo; Zhong Han; Ling Li (Journal of Earth Science, 2014)

Viscoelastic characteristics of low-frequency seismic wave attenuation in porous media - Yun Ling; Li-Guo Han; Yi-Ming Zhang (Applied Geophysics, 2014)

Effects of Adaptive Support Ventilation and Synchronized Intermittent Mandatory Ventilation on Peripheral Circulation and Blood Gas Markers of COPD Patients with Respiratory Failure - Ling Han; Yingxiao Wang; Yonghua Gan; Lijun Xu (Cell Biochemistry and Biophysics, 2014)

Morphology and molecular phylogeny for two new species of Fomitopsis (Basidiomycota) from South China - Mei-Ling Han; Jie Song; Bao-Kai Cui (Mycological Progress, 2014)

Enhanced cold stress tolerance of transgenic Dendrocalamus latiflorus Munro (Ma bamboo) plants expressing a bacterial CodA gene - Guirong Qiao; Huiqing Yang; Ling Zhang; Xiaojiao Han; Mingying Liu; Jing Jiang; Yancheng Jiang; Renying Zhuo (In Vitro Cellular & Developmental Biology - Plant, 2014)

Characterization and expression profiles of MaACS and MaACO genes from mulberry (Morus alba L.) - Chang-ying Liu; Rui-hua Lü; Jun Li; Ai-chun Zhao; Xi-ling Wang; Umuhoza Diane; Xiao-hong Wang; Chuan-hong Wang; Ya-sheng Yu; Shu-mei Han; Cheng Lu; Mao-de Yu (Journal of Zhejiang University-SCIENCE B, 2014)

Comparison of complete genome sequences of dog rabies viruses isolated from China and Mexico reveals key amino acid changes that may be associated with virus replication and virulence - Fulai Yu; Guoqing Zhang; Xiangfu Zhong; Na Han; Yunfeng Song; Ling Zhao; Min Cui; Simon Rayner; Zhen F. Fu (Archives of Virology, 2014)

Molecular and Catalytic Properties of Glutathione Peroxidase Family Proteins from Pinus tabulaeformis - Li Zhao; Xue-Min Han; Wei Wang; Hai-Ling Yang (Plant Molecular Biology Reporter, 2014)

Pathological and microbiological findings from mortality of the Chinese giant salamander (Andrias davidianus) - Yan Meng; Jie Ma; Nan Jiang; Ling-Bing Zeng; Han-Bing Xiao (Archives of Virology, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

Synthesis of isoflavones by room-temperature nickel-catalyzed cross-couplings of 3-iodo(bromo)chromones with arylzincs - Zunting Zhang; Jinfeng Qiao; Ding Wang; Ling Han; Ru Ding (Molecular Diversity, 2014)

LIM homeobox transcription factor 1B is associated with pro-fibrotic components and apoptosis in hypoxia/reoxygenation renal tubular epithelial cells - Tian-Biao Zhou; Hui-Ling Xu; Yuan-Han Qin; Feng-Ying Lei; Wei-Fang Huang; Gregor P. C. Drummen (Apoptosis, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Embodied exergy-based assessment of energy and resource consumption of buildings - Jing Meng; Zhi Li; Jiashuo Li; Ling Shao; Mengyao Han; Shan Guo (Frontiers of Earth Science, 2014)

Cloning and molecular characterization of a myosin light chain gene from Puccinia striiformis f. sp. tritici - Jie Liu; Li-Na Han; Qiong Zhang; Qiu-Ling Wang; Qing Chang; Hua Zhuang; Jia Liu; Man Li; Dan Yu; Zhen-Sheng Kang (World Journal of Microbiology and Biotechnology, 2014)

Lack of association between the polymorphisms of hypoxia-inducible factor 1A (HIF1A) gene and SLE susceptibility in a Chinese population - Chen-Chen Feng; Qian-Ling Ye; Yan Zhu; Rui-Xue Leng; Gui-Mei Chen; Jie Yang; Han Cen; Xiao-Ke Yang; Rui Li; Wang-Dong Xu; Hai-Feng Pan; Dong-Qing Ye (Immunogenetics, 2014)

Natural antisense transcripts of UL123 packaged in human cytomegalovirus virions - Cui-Qing Yang; Ling-Feng Miao; Xing Pan; Cong-Cong Wu; Simon Rayner; Edward S. Mocarski; Han-Qing Ye; Min-Hua Luo (Archives of Virology, 2014)

A knockdown mutation of YELLOW-GREEN LEAF2 blocks chlorophyll biosynthesis in rice - Hong Chen; Zhijun Cheng; Xiaoding Ma; Han Wu; Yanling Liu; Kunneng Zhou; Yilin Chen; Weiwei Ma; Jingcui Bi; Xin Zhang; Xiuping Guo; Jiulin Wang; et al. (Plant Cell Reports, 2013)

Two new Fomitopsis species from southern China based on morphological and molecular characters - Hai-Jiao Li; Mei-Ling Han; Bao-Kai Cui (Mycological Progress, 2013)

Abnormal Activation of Microglia Accompanied with Disrupted CX3CR1/CX3CL1 Pathway in the Brains of the Hamsters Infected with Scrapie Agent 263K - Wu-Ling Xie; Qi Shi; Jin Zhang; Bao-Yun Zhang; Han-Shi Gong; Yan Guo; Shao-Bin Wang; Yin Xu; Ke Wang; Cao Chen; Yong Liu; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2013)

Impact of matrix metalloproteinase-8 gene variations on the risk of thoracic aortic dissection in a Chinese Han population - Xiao-Zeng Wang; Xiao-Mo Du; Quan-Min Jing; Xing-Xing Li; Ruo-Xi Gu; Jiao Wang; Ya-Ling Han (Molecular Biology Reports, 2013)

Optimization of extraction of phenolics from leaves of Ficus virens - Xiao-xin Chen; Xiao-bing Wu; Wei-ming Chai; Hui-ling Feng; Yan Shi; Han-tao Zhou; Qing-xi Chen (Journal of Zhejiang University-SCIENCE B, 2013)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

Zircon U–Pb–Hf isotopes and bulk-rock geochemistry of gneissic granites in the northern Jiamusi Massif, Central Asian Orogenic Belt: implications for Middle Permian collisional orogeny and Mesoproterozoic crustal evolution - Pei-Long Cui; Jing-Gui Sun; Shi-Jiong Han; Peng Zhang; Yong Zhang; Ling-An Bai; A-Lei Gu (International Geology Review, 2013)

Re-Examination of the Genotoxic Activity of Water Taken From the Songhua River in P. R. China - Jia Yu; Hong-Wei Dong; Li-Tian Shi; Hui-Ling Jiang; Jian-Wen Yu; Qian-Wen Zhao; Shi-Chun Cai; Dan Han; Xuan-Yue Tang; Jia-Ren Liu (Archives of Environmental Contamination and Toxicology, 2013)

Molecular cloning of the duck MEF2C gene cDNA coding domain sequence and its expression during fetal muscle tissue development - Ling-Li Sun; He-he Liu; Hao-han Wang; Jian-Ming Si; Hai-bo Jin; Xin-xin Li; Chao Yang; Liang Li; Ji-wen Wang (Genes & Genomics, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Anti-neutral endopeptidase, natriuretic peptides disarrangement, and proteinuria onset in membranous nephropathy - Peng Hu; Qiang Xuan; Bo Hu; Ling Lu; Yuan Han Qin (Molecular Biology Reports, 2013)

Development of a new polyclonal antibody for the determination of polychlorinated biphenyls in indoor air by ic-ELISA - Han-Yu Chen; Hui-Sheng Zhuang; Guang-Xin Yang; Xiu-Ling Ji (Environmental Science and Pollution Research, 2013)

Geology and ages of porphyry and medium- to high-sulphidation epithermal gold deposits of the continental margin of Northeast China - Shi-Jiong Han; Jing-Gui Sun; Ling-An Bai; Shu-Wen Xing; Peng Chai; Yong Zhang; Fan Yang; Lan-Jing Men; Yi-Xin Li (International Geology Review, 2013)

SOD1 gene transfer into paraventricular nucleus attenuates hypertension and sympathetic activity in spontaneously hypertensive rats - Ning Yuan; Feng Zhang; Ling-Li Zhang; Juan Gao; Ye-Bo Zhou; Ying Han; Guo-Qing Zhu (Pflügers Archiv - European Journal of Physiology, 2013)

Overexpressed C-type natriuretic peptide serves as an early compensatory response to counteract extracellular matrix remodeling in unilateral ureteral obstruction rats - Peng Hu; Jing Wang; Xue Qi Zhao; Bo Hu; Ling Lu; Yuan Han Qin (Molecular Biology Reports, 2013)

Steroids and phenolic constituents from the fruiting bodies of the basidiomycete Sarcodon joedes - Han-Wei Liu; Ling Hu; An-Ling Zhang; Jin-Ming Gao (Natural Product Research, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

The Diagnostic Value of Treadmill Exercise Test Parameters for Coronary Artery Disease - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2013)

Hepatitis E virus genotype 4 isolated from a patient with liver failure: full-length sequence analysis showing potential determinants of virus pathogenesis - Qiuning Bu; Xiaojuan Wang; Ling Wang; Peng Liu; Jiabao Geng; Maorong Wang; Jian Han; Yonghong Zhu; Hui Zhuang (Archives of Virology, 2013)

Effects of Ibutilide on Canine Cardiac Pacing Threshold and on Induction Rates of Atrial Fibrillation - Jian-ling Sun; Rong Han; Ji-hong Guo; Xiao-ying Li; Xian-lin Ma; Chong-yu Wang (Cell Biochemistry and Biophysics, 2012)

Establishment of reference mandibular plane for anterior alveolar morphology evaluation using cone beam computed tomography - Rong-yang Wang; Min Han; Hong Liu; Chun-ling Wang; Hong-hong Xian; Lei Zhang; Shi-jie Zhang; Dong-xu Liu (Journal of Zhejiang University-SCIENCE B, 2012)

Polymorphisms of the interleukin-15 gene and their associations with fatness and muscle fiber traits in chickens - Shi-Jie Lv; Ling Su; Hong Li; Rui-Li Han; Gui-Rong Sun; Xiang-Tao Kang (Journal of Applied Genetics, 2012)

Effect of Ibutilide on the Canine Cardiac Conduction System - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2012)

Diagnosis and Treatment of Xanthogranulomatous Cholecystitis: A Report of 39 Cases - Sheng-Hua Han; Yan-Ling Chen (Cell Biochemistry and Biophysics, 2012)

Association of apoE gene expression and its gene polymorphism with nephrotic syndrome susceptibility: a meta-analysis of experimental and human studies - Tian-Biao Zhou; Yuan-Han Qin; Hui-Ling Xu (Molecular Biology Reports, 2012)

Characterization of grapevine microR164 and its target genes - Xin Sun; Nicholas Kibet Korir; Jian Han; Ling-Fei Shangguan; Emrul Kayesh; Xiang-Peng Leng; Jing-Gui Fang (Molecular Biology Reports, 2012)

Biological and cytoselective anticancer properties of copper(II)-polypyridyl complexes modulated by auxiliary methylated glycine ligand - Hoi-Ling Seng; Wai-San Wang; Siew-Ming Kong; Han-Kiat Alan Ong; Yip-Foo Win; Raja Noor Zaliha Raja Abd. Rahman; Makoto Chikira; Weng-Kee Leong; Munirah Ahmad; Alan Soo-Beng Khoo; Chew-Hee Ng (BioMetals, 2012)

Value of a new post-procedural intravascular ultrasound score in predicting target vessel revascularization after coronary drug-eluting stents implantation - Kai Xu; Ya-ling Han; Quan-min Jing; Shou-li Wang; Ying-yan Ma; Xiao-zeng Wang; Geng Wang; Zu-lu Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Amino Acid Profiles of Bivalve Mollusks from Beibu Gulf, China - De-Wei Chen; Jian Su; Xiao-Ling Liu; Dong-Mei Yan; Ying Lin; Wei-Ming Jiang; Xiao-Han Chen (Journal of Aquatic Food Product Technology, 2012)

The identification of Pi50(t), a new member of the rice blast resistance Pi2/Pi9 multigene family - Xiaoyuan Zhu; Shen Chen; Jianyuan Yang; Shaochuan Zhou; Liexian Zeng; Jingluan Han; Jing Su; Ling Wang; Qinghua Pan (Theoretical and Applied Genetics, 2012)

Formaldehyde up-regulates TRPV1 through MAPK and PI3K signaling pathways in a rat model of bone cancer pain - Ying Han; Yan Li; Xing Xiao; Jia Liu; Xiang-Ling Meng; Feng-Yu Liu; Guo-Gang Xing; You Wan (Neuroscience Bulletin, 2012)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

The monitoring results of electromagnetic radiation of 110-kV high-voltage lines in one urban location in Chongqing P.R. China - Qi-zhong Qin; Yu Chen; Ting-ting Fu; Li Ding; Ling-li Han; Jian-chao Li (Environmental Monitoring and Assessment, 2012)

Timing, Conditions, and Complications of Post-operative Conception and Pregnancy in Female Renal Transplant Recipients - Long-gen Xu; Shu Han; Yong Liu; Hong-wei Wang; Yi-rong Yang; Feng Qiu; Wan-ling Peng; Li-gong Tang (Cell Biochemistry and Biophysics, 2011)

Self-compatibility of ‘Zaoguan’ (Pyrus bretschneideri Rehd.) is associated with style-part mutations - Yong-Jie Qi; Ying-Tao Wang; Yan-Xiao Han; Sheng Qiang; Jun Wu; Shu-Tian Tao; Shao-Ling Zhang; Hua-Qing Wu (Genetica, 2011)

Expression of the Integrin-Linked Kinase in a Rat Kidney Model of Chronic Allograft Nephropathy - Conghui Han; Hequn Zou; Qingqin Li; Yuxin Wang; Yanling Shi; Tianyu Lv; Ling Chen; Wenying Zhou (Cell Biochemistry and Biophysics, 2011)

Physiological significance of P2X receptor-mediated vasoconstriction in five different types of arteries in rats - Lu Li; Zhen-Hua Jia; Chao Chen; Cong Wei; Jian-Ke Han; Yi-Ling Wu; Lei-Ming Ren (Purinergic Signalling, 2011)

Effective kinetics of schisandrin B on serum/hepatic triglyceride and total cholesterol levels in mice with and without the influence of fenofibrate - Si-Yuan Pan; Hang Dong; Bao-feng Guo; Yi Zhang; Zhi-Ling Yu; Wang-Fun Fong; Yi-Fan Han; Kam-Ming Ko (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

A new method to efficiently produce transgenic embryos and mice from low-titer lentiviral vectors - Kai Miao; Min Guo; Lei An; Xiao Ling Xu; Han Wu; Dong Wang; Zhong Hong Wu; Jian Hui Tian (Transgenic Research, 2011)

Prevention of cerebral ischemia-induced memory deficits by inhibition of phosphodiesterase-4 in rats - Ling-Xia Li; Yu-Fang Cheng; Huan-Bing Lin; Chuang Wang; Jiang-Ping Xu; Han-Ting Zhang (Metabolic Brain Disease, 2011)

Disturbed tooth germ development in the absence of MINT in the cultured mouse mandibular explants - Ming-Hui Zhu; Wen-Bo Dong; Guang-Ying Dong; Ping Zhang; Yong-Jin Chen; Bu-Ling Wu; Hua Han (Molecular Biology Reports, 2011)

Study on polymerization effect of polyembryony genes by SSCP marker and family trees in Chinese goats - Guang Li; Xiaopeng An; Jinxing Hou; Ling Li; Dan Han; Mingming Yang; Yana Wang; Guangqin Zhu; Jiangang Wang; Yuxuan Song; Bin Yun Cao (Molecular Biology Reports, 2011)

Does the geographical gradient of ApoE4 allele exist in China? A systemic comparison among multiple Chinese populations - Peng Hu; Yuan Han Qin; Cheng Xue Jing; Ling Lu; Bo Hu; Peng Fei Du (Molecular Biology Reports, 2011)

Investigation of the association between all-trans-retinol dehydrogenase (RDH8) polymorphisms and high myopia in Chinese - Yan-shu Yu; Lin-ling Wang; Ye Shen; Maurice K. H. Yap; Shea-ping Yip; Wei Han (Journal of Zhejiang University-SCIENCE B, 2010)

A survey of soybean germplasm for resistance to Phytophthora sojae - Xiao-Ling Wu; Jin-Ming Zhao; Shi Sun; Feng Yang; Yuan-Chao Wang; Jun-Yi Gai; Han Xing (Euphytica, 2010)

A possible role of myristoylated alanine-rich C kinase substrate in endocytic pathway of Alzheimer’s disease - Rui Su; Zhen-Yun Han; Ji-Ping Fan; Yun-Ling Zhang (Neuroscience Bulletin, 2010)

RNA Interference-Based Transgenic Maize Resistant to Maize Dwarf Mosaic Virus - Zhi-Yong Zhang; Feng-Ling Fu; Lin Gou; Han-Guang Wang; Wan-Chen Li (Journal of Plant Biology, 2010)

Antioxidative responses related to H2O2 depletion in Hypnum plumaeforme under the combined stress induced by Pb and Ni - Shou-Qin Sun; Ming He; Tong Cao; Yusufujiang Yusuyin; Wei Han; Jin-Ling Li (Environmental Monitoring and Assessment, 2010)

Evaluation of the geology-environmental capacity of buildings based on the ANFIS model of the floor area ratio - Zhen-Dong Cui; Yi-Qun Tang; Xue-Xin Yan; Chun-Ling Yan; Han-Mei Wang; Jian-Xiu Wang (Bulletin of Engineering Geology and the Environment, 2010)

Function of Drosophila mob2 in photoreceptor morphogenesis - Ling-Yu Liu; Cheng-Han Lin; Seng-Sheen Fan (Cell and Tissue Research, 2009)

Effects of chronic 4-n-nonylphenol treatment on aortic vasoconstriction and vasorelaxation in rats - Chi-Ying Hsieh; Chang-Ling Miaw; Chien-Cheng Hsieh; Hui-Ching Tseng; Yuan-Han Yang; Chia-Hung Yen (Archives of Toxicology, 2009)

Necrostatin-1 reverts shikonin-induced necroptosis to apoptosis - Weidong Han; Jiansheng Xie; Ling Li; Zhen Liu; Xun Hu (Apoptosis, 2009)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

Efficient, reproducible Agrobacterium-mediated transformation of sorghum using heat treatment of immature embryos - Songul Gurel; Ekrem Gurel; Rajvinder Kaur; Joshua Wong; Ling Meng; Han-Qi Tan; Peggy G. Lemaux (Plant Cell Reports, 2009)

Anti-angiogenesis effect of generation 4 polyamidoamine/vascular endothelial growth factor antisense oligodeoxynucleotide on breast cancer in vitro - Shan-zhi Gu; Xin-han Zhao; Ling-xiao Zhang; Li Li; Zhi-yu Wang; Min Meng; Gai-li An (Journal of Zhejiang University-SCIENCE B, 2009)

Weak microwave can alleviate water deficit induced by osmotic stress in wheat seedlings - Yi-Ping Chen; Jing-Fen Jia; Xiao-Ling Han (Planta, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Cloning and expression study of a putative carotene biosynthesis related (cbr) gene from the halotolerant green alga Dunaliella salina - Chen Chen; Lin Han Bai; Dai Rong Qiao; Hui Xu; Gui Ling Dong; Kun Ruan; Fei Huang; Yi Cao (Molecular Biology Reports, 2008)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

The selective 5-HT1A receptor antagonist WAY-100635 inhibits neuronal activity of the ventromedial prefrontal cortex in a rodent model of Parkinson’s disease - Jian Cao; Jian Liu; Qiao-Jun Zhang; Tao Wang; Shuang Wang; Ling-Na Han; Qiang Li (Neuroscience Bulletin, 2007)

Mechanism of acute pancreatitis complicated with injury of intestinal mucosa barrier - Xi-ping Zhang; Jie Zhang; Qiao-ling Song; Han-qin Chen (Journal of Zhejiang University-SCIENCE B, 2007)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Heat shock proteins and p53 play a critical role in K+ channel-mediated tumor cell proliferation and apoptosis - Xiaobing Han; Fang Wang; Weixing Yao; Hui Xing; Danhui Weng; Xiaohong Song; Gang Chen; Ling Xi; Tao Zhu; Jianfeng Zhou; Gang Xu; Shixuan Wang; et al. (Apoptosis, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Plant regeneration via direct somatic embryogenesis in Panax japonicus - Xiang Ling You; Jung Yeon Han; Yong Eui Choi (Plant Biotechnology Reports, 2007)

Differential expression changes in K562 cells during the hemin-induced erythroid differentiation and the phorbol myristate acetate (PMA)-induced megakaryocytic differentiation - Xiao-Fang Huo; Jia Yu; Han Peng; Zhan-Wen Du; Xiao-Ling Liu; Yan-Ni Ma; Xin Zhang; Yao Zhang; Hua-Lu Zhao; Jun-Wu Zhang (Molecular and Cellular Biochemistry, 2006)

Coordination between manganese and nitrogen within the ligands in the manganese complexes facilitates the reconstitution of the water-oxidizing complex in manganese-depleted photosystem II preparations - Shuqin Li; Guiying Chen; Guangye Han; Lin Ling; Deguang Huang; A. A. Khorobrykh; S. K. Zharmukhamedov; Qiutian Liu; V. V. Klimov; Tingyun Kuang (JBIC Journal of Biological Inorganic Chemistry, 2006)

Biotransfer of persistent organic pollutants from a large site in China used for the disassembly of electronic and electrical waste - Gaofeng Zhao; Ying Xu; Guanggen Han; Bo Ling (Environmental Geochemistry and Health, 2006)

Nitrogen response efficiency increased monotonically with decreasing soil resource availability: a case study from a semiarid grassland in northern China - Zhi-You Yuan; Ling-Hao Li; Xing-Guo Han; Shi-Ping Chen; Zheng-Wen Wang; Quan-Sheng Chen; Wen-Ming Bai (Oecologia, 2006)

Foliar Nitrogen Dynamics and Nitrogen Resorption of a Sandy Shrub Salix gordejevii in Northern China - Zhi-You Yuan; Ling-Hao Li; Xing-Guo Han; Jian-Hui Huang; Shi-Qiang Wan (Plant and Soil, 2005)

Soil characteristics and nitrogen resorption in Stipa krylovii native to northern China - Zhi-You Yuan; Ling-Hao Li; Xing-Guo Han; Jian-Hui Huang; Gao-Ming Jiang; Shi-Qiang Wan (Plant and Soil, 2005)

SYNTHESIS BIODISTRIBUTION AND QSAR STUDIES OF FIVE Tc-99M LABELED NOVEL N3S PSEUDO-PEPTIDE COMPLEXES - Hua-bei Zhang; Hai-hong Ye; Ya-ling Zhang; Xuefang Zheng; Jian-sheng Han; Hua Li; Chun-ping Liu (Medicinal Chemistry Research, 2005)

Characterization of soybean genomic features by analysis of its expressed sequence tags - Ai-Guo Tian; Jun Wang; Peng Cui; Yu-Jun Han; Hao Xu; Li-Juan Cong; Xian-Gang Huang; Xiao-Ling Wang; Yong-Zhi Jiao; Bang-Jun Wang; Yong-Jun Wang; Jin-Song Zhang; et al. (Theoretical and Applied Genetics, 2004)

Growth characteristics and eicosapentaenoic acid production by Nannochloropsis sp. in mixotrophic conditions - Fang Xu; Han-hua Hu; Wei Cong; Zhao-ling Cai; Fan Ouyang (Biotechnology Letters, 2004)

Inhibitors of islet amyloid polypeptide fibrillogenesis, and the treatment of type-2 diabetes - Louise A. Scrocchi; Yan Chen; Feng Wang; Kyung Han; Katherine Ha; Ling Wu; Paul E. Fraser (International Journal of Peptide Research and Therapeutics, 2003)

Changes in intracellular metabolite pools, and acetate formation in Escherichia coli are associated with a cell-density-dependent metabolic switch - Ling Han; Sven-Olof Enfors; Lena Häggström (Biotechnology Letters, 2002)

Genetic Diversity in Crucian Carp (Carassius auratus) - Jing Luo; Ya-Ping Zhang; Chun-Ling Zhu; Wu-Han Xiao; Shun-You Huang (Biochemical Genetics, 1999)

A new species ofRhinogobius (Teleostei: Gobiidae) from Fujian Province, China - I-Shiung Chen; Han-Ling Wu; Kwang-Tsao Shao (Ichthyological Research, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)